Wound dressing

By combining negative pressure wound dressings with silver ions and carboxyalkyl cellulose fibers, the problem of poor antimicrobial agent efficacy in existing wound dressings has been solved, achieving efficient wound healing and infection prevention, reducing side effects, and meeting the microbial level requirements of regulatory agencies.

CN121079112APending Publication Date: 2025-12-05CONVATEC LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480028087.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-04-25
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing wound dressings contain antimicrobial agents that are not very effective at the wound site, and long-term use may lead to side effects. Improvements are needed to effectively prevent infection and reduce the absorption and distribution of antimicrobial agents.

Method used

The negative pressure wound dressing contains silver ions as an antimicrobial agent, combined with fibers of carboxyalkyl cellulose or its salts, especially sodium carboxymethyl cellulose, to promote wound healing through negative pressure and absorb and retain exudate through gel-forming fibers, maintaining the effectiveness of silver ions at the wound site.

Benefits of technology

It significantly reduces the number of microorganisms at the wound site, improves wound healing, reduces the risk of infection, avoids unnecessary absorption and side effects of antimicrobial agents, meets FDA-mandated microbial levels, and extends the replacement cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121079112A_ABST
    Figure CN121079112A_ABST
Patent Text Reader

Abstract

A negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer configured to detachably adhere the dressing to a skin surface, and an absorbent structure, where the backing layer comprises an aperture for connection to a negative pressure source, where the absorbent structure comprises a wound contact layer, where the adhesive skin contact layer is configured to detachably adhere the dressing to the skin surface. The wound contact layer is arranged to contact a wound when the adhesive skin contact layer adheres to skin near the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a wound dressing. In particular, the present invention relates to a negative pressure wound dressing. BACKGROUND

[0002] Wound dressings are known and are generally suitable for treating a variety of wounds, including chronic and acute wound types, such as infected wounds, venous ulcers, diabetic ulcers, burns and surgical wounds.

[0003] Wounds are often colonized by a variety of microorganisms, some of which can cause infection. It is increasingly recognized that populations of microorganisms living in a biofilm environment contribute to delayed healing and infection. Biofilms consist of extracellular polymers produced by bacteria after attachment to a surface, which help to protect the microorganisms from immune cells and antimicrobial agents. Along with the overuse of antibiotics and the associated increase in bacterial resistance, these factors are impacting the efficacy of antibiotics in the treatment of wound infections. Therefore, there is a need for effective alternatives to antibiotics.

[0004] Wound dressings generally include an adhesive skin contact layer for releasably adhering the dressing to a skin surface, a backing layer and an absorbent structure arranged between the backing layer and the adhesive skin contact layer. The absorbent structure generally includes a layer in contact with the wound, referred to as a wound contact layer, and an absorbent layer arranged between the wound contact layer and the backing layer to prevent exudate from collecting at the wound site, which would otherwise increase the risk of infection. In use, the wound contact layer absorbs wound exudate from the wound site. The exudate is then absorbed from the wound contact layer into the absorbent layer, which generally has a greater absorbent capacity than the wound contact layer. Attempts to provide effective treatment to prevent wound infection include incorporating the wound contact layer or the absorbent layer with an antimicrobial agent.

[0005] However, such attempts to incorporate antimicrobial agents into conventional wound dressings have not provided completely satisfactory results.

[0006] For example, when the antimicrobial agent is incorporated with the absorbent layer that is separated from the wound by the wound contact layer, the efficacy of the antimicrobial agent at the wound site is minimal, primarily because the arrangement of the wound contact layer between the wound site and the absorbent layer results in the absorbent layer not being in contact with the wound site.

[0007] As another example, when the antimicrobial agent is incorporated with a conventional wound contact layer having a basis weight of about 70-80 g / m 2 of the antimicrobial agent is absorbed into the wound exudate and away from the wound site towards the absorbent layer. Disadvantageously, this reduces the amount of antimicrobial agent available at the wound site to prevent infection.

[0008] Accordingly, despite the relatively small antimicrobial effect provided at the wound site by these arrangements, further improvements are needed.

[0009] A simple alternative is to increase the amount of antimicrobial agent to reduce the amount of antimicrobial agent that is absorbed into the wound exudate and absorbed from the wound site. However, disadvantageously, this can lead to unwanted side effects such as cytotoxicity, allergic reactions, skin staining and systemic effects with long term use.

[0010] It is an aim of embodiments of the present application to at least partially overcome or mitigate the above problems and / or to provide an improved wound dressing. SUMMARY

[0011] According to a broad aspect of the present application, there is provided a negative pressure wound dressing. The negative pressure wound dressing can comprise an absorbent structure. The absorbent structure can comprise a wound contact layer. The wound contact layer can comprise an antimicrobial agent. The antimicrobial agent can comprise silver ions.

[0012] The negative pressure wound dressing can comprise a backing layer. The negative pressure wound dressing can comprise an adhesive skin contact layer. The adhesive skin contact layer can be configured to releasably adhere the dressing to a skin surface. The backing layer can comprise an aperture for connection to a negative pressure source. The wound contact layer can be arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound.

[0013] According to a first aspect of the present application, there is provided a negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a negative pressure source, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions.

[0014] The wound dressing is a negative pressure wound dressing. Advantageously, negative pressure promotes wound healing through a number of mechanisms, including removal of excess exudate, reduction of oedema around the wound and increased perfusion. This can improve wound efficacy in combination with the physical force exerted by the negative pressure to draw wound edges together.

[0015] More advantageously, the silver ions eliminate or at least significantly reduce the number of microorganisms at the wound site. It has been found that the present application reduces the total viable cell count of microorganisms at the wound site by 4 log reductions within 48 hours of incubation. The present application is therefore particularly advantageous as it reduces the total viable cell count of microorganisms at the wound site to below levels prescribed by regulatory bodies (e.g. the Food and Drug Administration (FDA) in the United States).

[0016] Likewise, the present invention provides a synergistic effect of improving the wound effect (this is mainly due to the negative pressure generated at the wound site) and eliminating or at least significantly reducing microorganisms at the wound site (this is mainly due to the wound contact layer comprising silver ions).

[0017] The negative pressure wound dressing can comprise a port for connecting the hole to a source of negative pressure. The port can be arranged for connecting the source of negative pressure over the backing layer of the negative pressure wound dressing. The port can be arranged to be connected to a medical tube. The negative pressure wound dressing can comprise an airway for connecting the hole to a source of negative pressure. The airway can be arranged for disconnecting the source of negative pressure from the backing layer of the negative pressure wound dressing. Airways are more commonly used for connection to a source of negative pressure than ports because they are more low profile and cause less pain when disconnected from the wound site. The airway can be arranged to be connected to a medical tube. The airway can comprise a luer lock connector to connect to a corresponding luer lock connector on a medical tube connected to a pump device.

[0018] The backing layer can be provided with a port or airway for connection to a conduit. The port or airway can be located in a portion of the backing layer that overlaps / overlies the absorbent structure, but towards / near the outer periphery of the absorbent structure, such that it is not directly vertically aligned with the centre of the wound dressing (or wound when in use). This facilitates the spread of wound exudate across the entire extent of the absorbent layer.

[0019] The backing layer of the wound dressing can be a bacterial and viral barrier layer which preferably prevents the ingress of liquids and air, but allows the transmission of moisture. In this way, the backing layer enhances the overall fluid handling capacity of the wound dressing by allowing moisture to escape through the backing layer, whilst being able to apply negative pressure to the wound. The backing layer can be a layer having a moisture vapour transmission rate (MVTR) of at least about 10,000 g / m 2 or about 10,000 g / m 2 to about 50,000 g / m 2 per 24 hours, measured by the method described in BS EN 13726-2 2002 "Test methods for primary wound dressings Part 2 Moisture vapour transmission rate of permeable film dressings". The backing layer can be in the form of a polyurethane film.

[0020] The wound contact layer can be formed from gel-forming fibers. By gel-forming fibers is meant absorbent fibers that become wet and smooth or gel-like upon absorption of wound exudate. The gel-forming fibers can be of the type that maintain their structural integrity upon absorption of exudate or can be of the type that lose their fibrous form and become amorphous or structureless gels. The gel-forming fibers can be carboxymethyl cellulose fibers, chemically modified cellulose fibers or alkyl sulfonate modified cellulose fibers, or combinations thereof. Preferably, the gel-forming fibers are carboxymethyl cellulose fibers. The antimicrobial agent can be dispersed on the gel-forming fibers. The gel-forming fibers can be impregnated, coated or treated with the antimicrobial agent comprising silver ions.

[0021] The gel-forming fibers can have an absorbency capacity of at least 1 gram of 0.9% saline solution per gram of fiber (as measured by the free swell method).

[0022] The wound contact layer can be formed from fibers of carboxyalkyl cellulose or a salt thereof.

[0023] The carboxyalkyl cellulose or a salt thereof can be carboxymethyl cellulose, carboxyethyl cellulose, or a salt thereof, or combinations thereof. The salt can be a sodium salt or a silver salt, or combinations thereof. Advantageously, the sodium salt and / or the silver salt of the carboxyalkyl cellulose fibers each provide significant biocompatibility and antimicrobial efficacy, as well as favorable fiber strength, as compared to other gel-forming fibers and salts.

[0024] The wound contact layer can be formed from carboxymethyl cellulose sodium fibers. Advantageously, it has been found that in embodiments of the present invention comprising a wound contact layer formed from carboxymethyl cellulose sodium fibers, the negative pressure wound dressing is particularly effective at eliminating microorganisms at the wound site as compared to negative pressure wound dressings comprising a wound contact layer formed from non-gelling fibers.

[0025] Surprisingly, it has been found that in embodiments of the present invention comprising fibers of carboxyalkyl cellulose or a salt thereof, in particular carboxymethyl cellulose sodium fibers, comprising silver ions (e.g., impregnated, coated, treated with, or having silver ions dispersed thereon), the availability / effectiveness of the silver ions at the wound site is not diminished by absorption of wound exudate through the wound contact layer to the absorbent layer. In this way, the silver ions are effectively maintained in the fibers of carboxyalkyl cellulose or a salt thereof, e.g., carboxymethyl cellulose sodium fibers, of the wound contact layer when the wound dressing is in use. Advantageously, this maintains the availability / effectiveness of the silver ions as an antimicrobial agent at the wound site, such that antimicrobial activity at the wound site is maintained for a longer period of time. Advantageously, this means that the negative pressure wound dressings of the present invention do not need to be changed as frequently as prior art wound dressings (in order to replenish the antimicrobial agent at the wound site).

[0026] Notably, in the present application, particularly in the embodiments comprising the carboxyalkyl cellulose or salt thereof fiber, particularly sodium carboxymethyl cellulose fiber, the efficacy of the silver ion antimicrobial agent is not reduced despite the fact that the wound dressing of the present application is a negative pressure wound dressing which can be considered to draw the active agent incorporated in the wound dressing from the wound site toward the negative pressure source according to some theories in the prior art. Thus, the present application exhibits the advantage of reliably obtaining silver ions as an antimicrobial agent at the wound site.

[0027] The antimicrobial agent can be dispersed on the carboxyalkyl cellulose fiber. The carboxyalkyl cellulose fiber can be impregnated, coated, or treated with the antimicrobial agent comprising silver ions.

[0028] The degree of substitution of the carboxyalkyl cellulose or salt thereof fiber can be from about 0.05 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.20 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.25 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, or about 0.30 carboxyalkyl groups per glucose unit.

[0029] The degree of substitution of the carboxyalkyl cellulose or salt thereof fiber can be from about 0.05 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.30 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.25 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.20 carboxyalkyl groups per glucose unit, from about 0.05 carboxyalkyl groups per glucose unit to about 0.15 carboxyalkyl groups per glucose unit, or from about 0.05 carboxyalkyl groups per glucose unit to about 0.10 carboxyalkyl groups per glucose unit.

[0030] The carboxyalkyl cellulose or salt thereof can have a degree of substitution of from about 0.10 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.30 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.25 carboxyalkyl groups per glucose unit, from about 0.10 carboxyalkyl groups per glucose unit to about 0.20 carboxyalkyl groups per glucose unit, or from about 0.10 carboxyalkyl groups per glucose unit to about 0.15 carboxyalkyl groups per glucose unit.

[0031] The carboxyalkyl cellulose or salt thereof can have a degree of substitution of from about 0.15 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.30 carboxyalkyl groups per glucose unit, from about 0.15 carboxyalkyl groups per glucose unit to about 0.25 carboxyalkyl groups per glucose unit, or from about 0.15 carboxyalkyl groups per glucose unit to about 0.20 carboxyalkyl groups per glucose unit.

[0032] The carboxyalkyl cellulose or salt thereof can have a degree of substitution of from about 0.20 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.20 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.20 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.20 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, from about 0.20 carboxyalkyl groups per glucose unit to about 0.30 carboxyalkyl groups per glucose unit, or from about 0.20 carboxyalkyl groups per glucose unit to about 0.25 carboxyalkyl groups per glucose unit.

[0033] The carboxyalkyl cellulose or salt thereof fibers can have a degree of substitution of from about 0.25 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.25 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.25 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, from about 0.25 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit, or from about 0.25 carboxyalkyl groups per glucose unit to about 0.30 carboxyalkyl groups per glucose unit.

[0034] The carboxyalkyl cellulose or salt thereof fibers can have a degree of substitution of from about 0.30 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.30 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, from about 0.30 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit, or from about 0.30 carboxyalkyl groups per glucose unit to about 0.35 carboxyalkyl groups per glucose unit.

[0035] The carboxyalkyl cellulose or salt thereof fibers can have a degree of substitution of from about 0.35 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, from about 0.35 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit, or from about 0.35 carboxyalkyl groups per glucose unit to about 0.40 carboxyalkyl groups per glucose unit.

[0036] The carboxyalkyl cellulose or salt thereof fibers can have a degree of substitution of from about 0.40 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit, or from about 0.40 carboxyalkyl groups per glucose unit to about 0.45 carboxyalkyl groups per glucose unit.

[0037] The carboxyalkyl cellulose or salt thereof fibers can have a degree of substitution of from about 0.45 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit.

[0038] In embodiments comprising carboxyalkyl cellulose or salt thereof fibers, the fibers can have a degree of substitution of about 0.05 carboxyalkyl groups per glucose unit, about 0.10 carboxyalkyl groups per glucose unit, about 0.15 carboxyalkyl groups per glucose unit, about 0.20 carboxyalkyl groups per glucose unit, about 0.25 carboxyalkyl groups per glucose unit, about 0.30 carboxyalkyl groups per glucose unit, about 0.35 carboxyalkyl groups per glucose unit, about 0.40 carboxyalkyl groups per glucose unit, about 0.45, or about 0.50 carboxyalkyl groups per glucose unit.

[0039] In embodiments comprising fibers of carboxyalkyl cellulose or a salt thereof, the fibers can have a degree of substitution of at least about 0.05 carboxyalkyl groups per glucose unit, at least about 0.10 carboxyalkyl groups per glucose unit, at least about 0.15 carboxyalkyl groups per glucose unit, at least about 0.20 carboxyalkyl groups per glucose unit, at least about 0.25 carboxyalkyl groups per glucose unit, at least about 0.30 carboxyalkyl groups per glucose unit, at least about 0.35 carboxyalkyl groups per glucose unit, at least about 0.40 carboxyalkyl groups per glucose unit, at least about 0.45 carboxyalkyl groups per glucose unit, or at least about 0.50 carboxyalkyl groups per glucose unit.

[0040] In embodiments comprising fibers of carboxyalkyl cellulose or a salt thereof, the fibers can have a degree of substitution of at least about 0.05 carboxyalkyl groups per glucose unit, at least about 0.10 carboxyalkyl groups per glucose unit, at least about 0.15 carboxyalkyl groups per glucose unit, at least about 0.20 carboxyalkyl groups per glucose unit, at least about 0.25 carboxyalkyl groups per glucose unit, at least about 0.30 carboxyalkyl groups per glucose unit, at least about 0.35 carboxyalkyl groups per glucose unit, at least about 0.40 carboxyalkyl groups per glucose unit, at least about 0.45 carboxyalkyl groups per glucose unit, or at least about 0.50 carboxyalkyl groups per glucose unit.

[0041] The above degrees of substitution of the fibers of carboxyalkyl cellulose or a salt thereof advantageously provide a wound contact layer that is particularly effective in eliminating bacteria at the wound site and comprises relatively high-gelling fibers, i.e., more absorbent and retentive, as compared to fibers often included in prior art wound contact layers. Thus, the wound contact layer is able to absorb and retain a greater amount of wound exudate than wound contact layers not comprising fibers of carboxyalkyl cellulose or a salt thereof, without adversely affecting its adhesion to other layers within the absorbent structure. Thus, the accumulation of wound exudate at the wound site is prevented or at least significantly reduced.

[0042] Thus, in some embodiments, a negative pressure wound dressing can be provided comprising a backing layer, an adhesive skin contact layer configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, and an absorbent structure comprising a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin proximate the wound, further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, and wherein the wound contact layer is formed of fibers of carboxyalkyl cellulose or a salt thereof having a degree of substitution of about 0.05 carboxyalkyl groups per glucose unit to about 0.50 carboxyalkyl groups per glucose unit.

[0043] In preferred embodiments, the wound contact layer is formed of carboxymethylcellulose fibers, in particular sodium carboxymethylcellulose fibers.

[0044] Thus, in some embodiments, a negative pressure wound dressing can be provided comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the fibers of the carboxyalkyl cellulose or salt thereof are sodium carboxymethylcellulose fibers.

[0045] Thus, in some embodiments, a negative pressure wound dressing can be provided comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer is formed of sodium carboxymethylcellulose fibers having a degree of substitution of from about 0.05 carboxymethyl groups per anhydrous glucose unit to about 0.50 carboxymethyl groups per anhydrous glucose unit.

[0046] Thus, in some embodiments, a negative pressure wound dressing can be provided comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer is formed of sodium carboxymethylcellulose fibers having a degree of substitution of from about 0.05 carboxymethyl groups per anhydrous glucose unit to about 0.50 carboxymethyl groups per anhydrous glucose unit.

[0047] The antimicrobial agent comprising silver ions can be dispersed on the sodium carboxymethylcellulose fibers, and the sodium carboxymethylcellulose fibers can have a degree of substitution of from about 0.05 carboxymethyl groups per anhydrous glucose unit to about 0.50 carboxymethyl groups per anhydrous glucose unit, for example about 0.30 carboxymethyl groups per anhydrous glucose unit.

[0048] The degree of substitution of the sodium carboxymethylcellulose fibers can be determined by infrared spectroscopy (as defined in WO 00 / 01425).

[0049] In embodiments comprising carboxymethylcellulose sodium fibers, the fibers can be prepared by carboxymethylation of a woven or nonwoven cellulose fabric, resulting in increased absorbency. The woven or nonwoven cellulose fabric can have an absorbency capacity of about 10 g / g of a physiological saline solution (Solution A, a sodium / calcium chloride solution described below) to about 30 g / g of Solution A, about 15 g / g of Solution A to about 25 g / g of Solution A, about 15 g / g of Solution A to about 20 g / g of Solution A, or about 18 g / g of Solution A, as measured according to the method described in Section 3.2, "Free swell absorptive capacity," of BS EN 13726-1 (2002) "Test methods for primary wound dressings." Carboxymethylation is typically carried out by contacting the fabric with a base and a carboxymethylation reagent, such as chloroacetic acid, in an aqueous system.

[0050] Solution A, as described in BS EN 13726-1 (2002), consists of a solution of sodium chloride and calcium chloride as chloride salts, which contains 142 millimoles of sodium ions and 2.5 millimoles of calcium ions. The solution has an ionic composition comparable to human serum or wound exudate. It is prepared by dissolving 8.298 grams of sodium chloride and 0.368 grams of calcium chloride dihydrate in deionized water and making up to 1 liter in a volumetric flask.

[0051] The wound contact layer can comprise only cellulose fibers. The wound contact layer can comprise a proportion of non-cellulose textile fibers or gel-forming fibers, or non-gel-forming fibers. The cellulose fibers can be of a known variety and can include continuous filament yarns and / or staple fibers. The fabric can include fibers that are woven into a nonwoven fabric.

[0052] The wound contact layer can comprise a combination or blend of gel-forming fibers (i.e., gel-forming fibers) and non-gel-forming fibers. The gel-forming fibers and non-gel-forming fibers can be any such fibers disclosed herein. For example, the wound contact layer can comprise a combination or blend of fibers including gel-forming fibers, such as fibers formed from carboxymethylcellulose sodium. The wound contact layer can comprise a combination or blend of fibers including non-gel-forming fibers, such as cellulose fibers.

[0053] The gel-forming fibers can be present in the fiber combination or blend in an amount equal to about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90% of the total mass of the fiber combination or blend.

[0054] The amount of the gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0055] The amount of the gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0056] The amount of the gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0057] The amount of the non-gelling fiber present in the fiber combination or blend can be equal to about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90% of the total mass of the fiber combination or blend.

[0058] The amount of the non-gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0059] The amount of the non-gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0060] The amount of the non-gelling fiber present in the fiber combination or blend can be at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, or at least about 90% of the total mass of the fiber combination or blend.

[0061] The wound contact layer can be stitched / sewn using cotton, nylon, polyester or any non-gelling fibre, or a cellulosic yarn such as lyocell yarn. In particular, the wound contact layer can be sewn using lyocell yarn as this advantageously results in highly aligned cellulosic fibres with a high degree of crystallinity, such that the cellulosic fibres are generally stronger and therefore they are able to withstand the manufacturing process and provide a stronger, non-degrading in use, wound contact layer. This also enhances the strength of the absorbent structure of the wound dressing.

[0062] The wound contact layer can be, for example, a Hydrofiber (RTM) material available from ConvaTec Ltd. of Deeside.

[0063] The wound contact layer can have a basis weight of from about 160 g / m 2 to about 480 g / m 2 , about 160 g / m 2 to about 470 g / m 2 , about 160 g / m 2 to about 460 g / m 2 , about 160 g / m 2 to about 450 g / m 2 , about 160 g / m 2 to about 440 g / m 2 , about 160 g / m 2 to about 430 g / m 2 , about 160 g / m 2 to about 420 g / m 2 , about 160 g / m 2 to about 410 g / m 2 , about 160 g / m 2 to about 400 g / m 2 , about 160 g / m 2 to about 390 g / m 2 , about 160 g / m 2 to about 380 g / m 2 , about 160 g / m 2 to about 370 g / m 2 , about 160 g / m 2 to about 360 g / m 2 , about 160 g / m 2 to about 350 g / m 2 , about 160 g / m 2 to about 340 g / m 2 , about 160 g / m 2 to about 330 g / m 2 , about 160 g / m2 from about 320 g / m 2 , about 160 g / m 2 from about 310 g / m 2 , about 160 g / m 2 from about 300 g / m 2 , about 160 g / m 2 from about 290 g / m 2 , about 160 g / m 2 from about 280 g / m 2 , about 160 g / m 2 from about 270 g / m 2 , about 160 g / m 2 from about 260 g / m 2 , about 160 g / m 2 from about 250 g / m 2 , about 160 g / m 2 from about 240 g / m 2 , about 170 g / m 2 from about 230 g / m 2 , about 180 g / m 2 from about 220 g / m 2 , about 190 g / m 2 from about 210 g / m 2 , or about 200 g / m 2 .

[0064] The basis weight of the wound contact layer can be about 160 g / m 2 , about 170 g / m 2 , about 180 g / m 2 , about 190 g / m 2 , about 200 g / m 2 , about 210 g / m 2 , about 220 g / m 2 , about 230 g / m 2 , about 240 g / m 2 , about 250 g / m 2 , about 260 g / m 2 , about 270 g / m 2 , about 280 g / m 2 , about 290 g / m 2 , about 300 g / m 2 , about 310 g / m 2 , about 320 g / m 2 , about 330 g / m 2 , about 340 g / m 2about 350 g / m 2 about 360 g / m 2 about 370 g / m 2 about 380 g / m 2 about 390 g / m 2 about 400 g / m 2 about 410 g / m 2 about 420 g / m 2 about 430 g / m 2 about 440 g / m 2 about 450 g / m 2 about 460 g / m 2 about 470 g / m 2 about 480 g / m 2 .

[0065] The basis weight of the wound contact layer can be at least about 160 g / m 2 at least about 170 g / m 2 at least about 180 g / m 2 at least about 190 g / m 2 at least about 200 g / m 2 at least about 210 g / m 2 at least about 220 g / m 2 at least about 230 g / m 2 at least about 240 g / m 2 at least about 250 g / m 2 at least about 260 g / m 2 at least about 270 g / m 2 at least about 280 g / m 2 at least about 290 g / m 2 at least about 300 g / m 2 at least about 310 g / m 2 at least about 320 g / m 2 at least about 330 g / m 2 at least about 340 g / m 2 at least about 350 g / m 2 at least about 360 g / m 2 at least about 370 g / m 2 at least about 380 g / m 2 at least about 390 g / m 2 at least about 400 g / m 2 at least about 410 g / m 2 at least about 420 g / m 2at least about 430 g / m 2 at least about 440 g / m 2 at least about 450 g / m 2 at least about 460 g / m 2 at least about 470 g / m 2 at least about 480 g / m 2 .

[0066] The wound contact layer can have a basis weight of no more than about 160 g / m 2 no more than about 170 g / m 2 no more than about 180 g / m 2 no more than about 190 g / m 2 no more than about 200 g / m 2 no more than about 210 g / m 2 no more than about 220 g / m 2 no more than about 230 g / m 2 no more than about 240 g / m 2 no more than about 250 g / m 2 no more than about 260 g / m 2 no more than about 270 g / m 2 no more than about 280 g / m 2 no more than about 290 g / m 2 no more than about 300 g / m 2 no more than about 310 g / m 2 no more than about 320 g / m 2 no more than about 330 g / m 2 no more than about 340 g / m 2 no more than about 350 g / m 2 no more than about 360 g / m 2 no more than about 370 g / m 2 no more than about 380 g / m 2 no more than about 390 g / m 2 no more than about 400 g / m 2 no more than about 410 g / m 2 no more than about 420 g / m 2 no more than about 430 g / m 2 no more than about 440 g / m 2 no more than about 450 g / m 2 no more than about 460 g / m 2 no more than about 470 g / m 2 no more than about 480 g / m2 .

[0067] Thus, the basis weight of the wound contact layer can advantageously be greater than the basis weight of typical wound contact layers of known wound dressings (i.e. about 70 g / m 2 to 100 g / m 2 ). This means that the area concentration of the antimicrobial agent - silver ions - according to the present invention is increased relative to prior art wound dressings comprising a wound contact layer having a basis weight of e.g. about 70 g / m 2 to 100 g / m 2 .

[0068] By increasing the basis weight of the wound contact layer relative to prior art wound contact layers, the area concentration of silver ions is increased without increasing the weight concentration of silver ions. Advantageously, this means that the antimicrobial effect of the negative pressure wound dressing of the present invention can be achieved without increasing the concentration of silver ions to a level that can have adverse effects on the user (e.g. by causing adverse effects through cytotoxicity, allergic reactions, skin staining and systemic effects).

[0069] The wound contact layer can comprise a single layer formed from fibres of carboxyalkyl cellulose or a salt thereof. The wound contact layer can comprise a plurality of layers, each layer being formed from fibres of carboxyalkyl cellulose or a salt thereof.

[0070] Thus, in some embodiments, there is provided a negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer comprises a plurality of layers, each layer being formed from fibres of carboxyalkyl cellulose or a salt thereof.

[0071] Advantageously, providing a wound contact layer comprising a single layer or a plurality of layers (each layer being formed from fibres of carboxyalkyl cellulose or a salt thereof) is an effective method of increasing the basis weight of the wound contact layer. This is because a plurality of relatively low basis weight layers can be combined to provide a wound contact layer having a total basis weight of e.g. about 160 g / m 2 to about 480 g / m 2 .

[0072] Each layer formed from fibres of carboxyalkyl cellulose or a salt thereof can have a basis weight of about 40 g / m 2 to about 240 g / m 2 , about 45 g / m 2 to about 230 g / m 2about 50 g / m 2 to about 220 g / m 2 about 55 g / m 2 to about 210 g / m 2 about 60 g / m 2 to about 200 g / m 2 about 65 g / m 2 to about 190 g / m 2 about 70 g / m 2 to about 180 g / m 2 about 75 g / m 2 to about 170 g / m 2 about 80 g / m 2 to about 160 g / m 2 about 85 g / m 2 to about 150 g / m 2 about 90 g / m 2 to about 140 g / m 2 about 90 g / m 2 to about 130 g / m 2 about 90 g / m 2 to about 120 g / m 2 about 95 g / m 2 to about 110 g / m 2 or about 100 g / m 2 .

[0073] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 40 g / m 2 to about 240 g / m 2 about 40 g / m 2 to about 230 g / m 2 about 40 g / m 2 to about 220 g / m 2 about 40 g / m 2 to about 210 g / m 2 about 40 g / m 2 to about 200 g / m 2 about 40 g / m 2 to about 190 g / m 2 about 40 g / m 2 to about 180 g / m 2 about 40 g / m 2 to about 170 g / m 2 about 40 g / m 2 to about 160 g / m 2 about 40 g / m 2from about 150 g / m 2 , about 40 g / m 2 from about 140 g / m 2 , about 40 g / m 2 from about 130 g / m 2 , about 40 g / m 2 from about 120 g / m 2 , about 40 g / m 2 from about 110 g / m 2 , about 40 g / m 2 from about 100 g / m 2 , about 40 g / m 2 from about 90 g / m 2 , about 40 g / m 2 from about 80 g / m 2 , about 40 g / m 2 from about 70 g / m 2 , about 40 g / m 2 from about 60 g / m 2 , or about 40 g / m 2 from about 50 g / m 2 .

[0074] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 50 g / m 2 to about 240 g / m 2 , about 50 g / m 2 to about 230 g / m 2 , about 50 g / m 2 to about 220 g / m 2 , about 50 g / m 2 to about 210 g / m 2 , about 50 g / m 2 to about 200 g / m 2 , about 50 g / m 2 to about 190 g / m 2 , about 50 g / m 2 to about 180 g / m 2 , about 50 g / m 2 to about 170 g / m 2 , about 50 g / m 2 to about 160 g / m 2 , about 50 g / m 2 to about 150 g / m 2 , about 50 g / m 2 to about 140 g / m 2 , about 50 g / m 2 to about 130 g / m2 about 50 g / m 2 to about 120 g / m 2 about 50 g / m 2 to about 110 g / m 2 about 50 g / m 2 to about 100 g / m 2 about 50 g / m 2 to about 90 g / m 2 about 50 g / m 2 to about 80 g / m 2 about 50 g / m 2 to about 70 g / m 2 about 50 g / m 2 to about 60 g / m 2 .

[0075] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 60 g / m 2 to about 240 g / m 2 about 60 g / m 2 to about 230 g / m 2 about 60 g / m 2 to about 220 g / m 2 about 60 g / m 2 to about 210 g / m 2 about 60 g / m 2 to about 200 g / m 2 about 60 g / m 2 to about 190 g / m 2 about 60 g / m 2 to about 180 g / m 2 about 60 g / m 2 to about 170 g / m 2 about 60 g / m 2 to about 160 g / m 2 about 60 g / m 2 to about 150 g / m 2 about 60 g / m 2 to about 140 g / m 2 about 60 g / m 2 to about 130 g / m 2 about 60 g / m 2 to about 120 g / m 2 about 60 g / m 2 to about 110 g / m 2 about 60 g / m 2 to about 100 g / m2 about 60 g / m 2 to about 90 g / m 2 about 60 g / m 2 to about 80 g / m 2 about 60 g / m 2 to about 70 g / m 2 .

[0076] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 70 g / m 2 to about 240 g / m 2 about 70 g / m 2 to about 230 g / m 2 about 70 g / m 2 to about 220 g / m 2 about 70 g / m 2 to about 210 g / m 2 about 70 g / m 2 to about 200 g / m 2 about 70 g / m 2 to about 190 g / m 2 about 70 g / m 2 to about 180 g / m 2 about 70 g / m 2 to about 170 g / m 2 about 70 g / m 2 to about 160 g / m 2 about 70 g / m 2 to about 150 g / m 2 about 70 g / m 2 to about 140 g / m 2 about 70 g / m 2 to about 130 g / m 2 about 70 g / m 2 to about 120 g / m 2 about 70 g / m 2 to about 110 g / m 2 about 70 g / m 2 to about 100 g / m 2 about 70 g / m 2 to about 90 g / m 2 about 70 g / m 2 to about 80 g / m 2 .

[0077] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 80 g / m 2 to about 240 g / m2 about 80 g / m 2 to about 230 g / m 2 about 80 g / m 2 to about 220 g / m 2 about 80 g / m 2 to about 210 g / m 2 about 80 g / m 2 to about 200 g / m 2 about 80 g / m 2 to about 190 g / m 2 about 80 g / m 2 to about 180 g / m 2 about 80 g / m 2 to about 170 g / m 2 about 80 g / m 2 to about 160 g / m 2 about 80 g / m 2 to about 150 g / m 2 about 80 g / m 2 to about 140 g / m 2 about 80 g / m 2 to about 130 g / m 2 about 80 g / m 2 to about 120 g / m 2 about 80 g / m 2 to about 110 g / m 2 about 80 g / m 2 to about 100 g / m 2 about 80 g / m 2 to about 90 g / m 2 .

[0078] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 90 g / m 2 to about 240 g / m 2 about 90 g / m 2 to about 230 g / m 2 about 90 g / m 2 to about 220 g / m 2 about 90 g / m 2 to about 210 g / m 2 about 90 g / m 2 to about 200 g / m 2 about 90 g / m 2 to about 190 g / m 2 about 90 g / m 2 to about 180 g / m2 about 90 g / m 2 to about 170 g / m 2 about 90 g / m 2 to about 160 g / m 2 about 90 g / m 2 to about 150 g / m 2 about 90 g / m 2 to about 140 g / m 2 about 90 g / m 2 to about 130 g / m 2 about 90 g / m 2 to about 120 g / m 2 about 90 g / m 2 to about 110 g / m 2 about 90 g / m 2 to about 100 g / m 2 .

[0079] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 100 g / m 2 to about 240 g / m 2 about 100 g / m 2 to about 230 g / m 2 about 100 g / m 2 to about 220 g / m 2 about 100 g / m 2 to about 210 g / m 2 about 100 g / m 2 to about 200 g / m 2 about 100 g / m 2 to about 190 g / m 2 about 100 g / m 2 to about 180 g / m 2 about 100 g / m 2 to about 170 g / m 2 about 100 g / m 2 to about 160 g / m 2 about 100 g / m 2 to about 150 g / m 2 about 100 g / m 2 to about 140 g / m 2 about 100 g / m 2 to about 130 g / m 2 about 100 g / m 2 to about 120 g / m 2 about 100 g / m 2from about 110 g / m 2 .

[0080] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 110 g / m 2 to about 240 g / m 2 , about 110 g / m 2 to about 230 g / m 2 , about 110 g / m 2 to about 220 g / m 2 , about 110 g / m 2 to about 210 g / m 2 , about 110 g / m 2 to about 200 g / m 2 , about 110 g / m 2 to about 190 g / m 2 , about 110 g / m 2 to about 180 g / m 2 , about 110 g / m 2 to about 170 g / m 2 , about 110 g / m 2 to about 160 g / m 2 , about 110 g / m 2 to about 150 g / m 2 , about 110 g / m 2 to about 140 g / m 2 , about 110 g / m 2 to about 130 g / m 2 , or about 110 g / m 2 to about 120 g / m 2 .

[0081] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 120 g / m 2 to about 240 g / m 2 , about 120 g / m 2 to about 230 g / m 2 , about 120 g / m 2 to about 220 g / m 2 , about 120 g / m 2 to about 210 g / m 2 , about 120 g / m 2 to about 200 g / m 2 , about 120 g / m 2 to about 190 g / m 2 , about 120 g / m 2 to about 180 g / m 2about 120 g / m 2 about 160 g / m 2 about 120 g / m 2 about 160 g / m 2 about 120 g / m 2 about 150 g / m 2 about 120 g / m 2 about 140 g / m 2 about 120 g / m 2 about 130 g / m 2 .

[0082] about 130 g / m 2 about 240 g / m 2 about 130 g / m 2 about 230 g / m 2 about 130 g / m 2 about 220 g / m 2 about 130 g / m 2 about 210 g / m 2 about 130 g / m 2 about 200 g / m 2 about 130 g / m 2 about 190 g / m 2 about 130 g / m 2 about 180 g / m 2 about 130 g / m 2 about 170 g / m 2 about 130 g / m 2 about 160 g / m 2 about 130 g / m 2 about 150 g / m 2 about 130 g / m 2 about 140 g / m 2 .

[0083] about 140 g / m 2 about 240 g / m 2 about 140 g / m 2 about 230 g / m 2 about 140 g / m 2 about 220 g / m 2 about 140 g / m 2 about 210 g / m 2 about 140 g / m 2from about 200 g / m 2 , about 140 g / m 2 from about 190 g / m 2 , about 140 g / m 2 from about 180 g / m 2 , about 140 g / m 2 from about 170 g / m 2 , about 140 g / m 2 from about 160 g / m 2 , or about 140 g / m 2 from about 150 g / m 2 .

[0084] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 150 g / m 2 to about 240 g / m 2 , about 150 g / m 2 to about 230 g / m 2 , about 150 g / m 2 to about 220 g / m 2 , about 150 g / m 2 to about 210 g / m 2 , about 150 g / m 2 to about 200 g / m 2 , about 150 g / m 2 to about 190 g / m 2 , about 150 g / m 2 to about 180 g / m 2 , about 150 g / m 2 to about 170 g / m 2 , or about 150 g / m 2 to about 160 g / m 2 .

[0085] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 160 g / m 2 to about 240 g / m 2 , about 160 g / m 2 to about 230 g / m 2 , about 160 g / m 2 to about 220 g / m 2 , about 160 g / m 2 to about 210 g / m 2 , about 160 g / m 2 to about 200 g / m 2 , about 160 g / m 2 to about 190 g / m 2, about 160 g / m 2 to about 180 g / m 2 , or about 160 g / m 2 to about 170 g / m 2 .

[0086] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 170 g / m 2 to about 240 g / m 2 , about 170 g / m 2 to about 230 g / m 2 , about 170 g / m 2 to about 220 g / m 2 , about 170 g / m 2 to about 210 g / m 2 , about 170 g / m 2 to about 200 g / m 2 , about 170 g / m 2 to about 190 g / m 2 , or about 170 g / m 2 to about 180 g / m 2 .

[0087] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 180 g / m 2 to about 240 g / m 2 , about 180 g / m 2 to about 230 g / m 2 , about 180 g / m 2 to about 220 g / m 2 , about 180 g / m 2 to about 210 g / m 2 , about 180 g / m 2 to about 200 g / m 2 , or about 180 g / m 2 to about 190 g / m 2 .

[0088] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be about 190 g / m 2 to about 240 g / m 2 , about 190 g / m 2 to about 230 g / m 2 , about 190 g / m 2 to about 220 g / m 2 , about 190 g / m 2 to about 210 g / m 2 , or about 190 g / m2 from about 200 g / m 2 .

[0089] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 200 g / m 2 to about 240 g / m 2 , from about 200 g / m 2 to about 230 g / m 2 , from about 200 g / m 2 to about 220 g / m 2 , or from about 200 g / m 2 to about 210 g / m 2 .

[0090] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 210 g / m 2 to about 240 g / m 2 , from about 210 g / m 2 to about 230 g / m 2 , or from about 210 g / m 2 to about 220 g / m 2 .

[0091] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 220 g / m 2 to about 240 g / m 2 , or from about 220 g / m 2 to about 230 g / m 2 .

[0092] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 230 g / m 2 to about 240 g / m 2 .

[0093] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be from about 40 g / m 2 , from about 45 g / m 2 , from about 50 g / m 2 , from about 55 g / m 2 , from about 60 g / m 2 , from about 65 g / m 2 , from about 70 g / m 2 , from about 75 g / m 2 , from about 80 g / m 2 , from about 85 g / m 2 , from about 90 g / m 2 , from about 95 g / m 2 , from about 100 g / m 2about 105 g / m 2 about 110 g / m 2 about 115 g / m 2 about 120 g / m 2 about 125 g / m 2 about 130 g / m 2 about 135 g / m 2 about 140 g / m 2 about 145 g / m 2 about 150 g / m 2 about 155 g / m 2 about 160 g / m 2 about 165 g / m 2 about 170 g / m 2 about 175 g / m 2 about 180 g / m 2 about 185 g / m 2 about 190 g / m 2 about 195 g / m 2 about 200 g / m 2 about 205 g / m 2 about 210 g / m 2 about 215 g / m 2 about 220 g / m 2 about 225 g / m 2 about 230 g / m 2 about 235 g / m 2 or about 240 g / m 2 .

[0094] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be at least about 40 g / m 2 at least about 45 g / m 2 at least about 50 g / m 2 at least about 55 g / m 2 at least about 60 g / m 2 at least about 65 g / m 2 at least about 70 g / m 2 at least about 75 g / m 2 at least about 80 g / m 2 at least about 85 g / m 2 at least about 90 g / m 2 at least about 95 g / m 2 at least about 100 g / m 2 at least about 105 g / m 2at least about 110 g / m 2 at least about 115 g / m 2 at least about 120 g / m 2 at least about 125 g / m 2 at least about 130 g / m 2 at least about 135 g / m 2 at least about 140 g / m 2 at least about 145 g / m 2 at least about 150 g / m 2 at least about 155 g / m 2 at least about 160 g / m 2 at least about 165 g / m 2 at least about 170 g / m 2 at least about 175 g / m 2 at least about 180 g / m 2 at least about 185 g / m 2 at least about 190 g / m 2 at least about 195 g / m 2 at least about 200 g / m 2 at least about 205 g / m 2 at least about 210 g / m 2 at least about 215 g / m 2 at least about 220 g / m 2 at least about 225 g / m 2 at least about 230 g / m 2 at least about 235 g / m 2 or at least about 240 g / m 2 .

[0095] The basis weight of each layer formed from fibers of carboxyalkyl cellulose or a salt thereof can be no more than about 40 g / m 2 no more than about 45 g / m 2 no more than about 50 g / m 2 no more than about 55 g / m 2 no more than about 60 g / m 2 no more than about 65 g / m 2 no more than about 70 g / m 2 no more than about 75 g / m 2 no more than about 80 g / m 2 no more than about 85 g / m 2 no more than about 90 g / m 2 no more than about 95 g / m 2 no more than about 100 g / m2 , not more than about 105 g / m 2 , not more than about 110 g / m 2 , not more than about 115 g / m 2 , not more than about 120 g / m 2 , not more than about 125 g / m 2 , not more than about 130 g / m 2 , not more than about 135 g / m 2 , not more than about 140 g / m 2 , not more than about 145 g / m 2 , not more than about 150 g / m 2 , not more than about 155 g / m 2 , not more than about 160 g / m 2 , not more than about 165 g / m 2 , not more than about 170 g / m 2 , not more than about 175 g / m 2 , not more than about 180 g / m 2 , not more than about 185 g / m 2 , not more than about 190 g / m 2 , not more than about 195 g / m 2 , not more than about 200 g / m 2 , not more than about 205 g / m 2 , not more than about 210 g / m 2 , not more than about 215 g / m 2 , not more than about 220 g / m 2 , not more than about 225 g / m 2 , not more than about 230 g / m 2 , not more than about 235 g / m 2 , or not more than about 240 g / m 2 .

[0096] Thus, in some embodiments, a negative pressure wound dressing can be provided comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer comprises a plurality of layers, each layer formed from fibers of a carboxyalkyl cellulose or a salt thereof, further wherein the basis weight of each layer is in the range of 80 g / m 2 to 160 g / m 2 .

[0097] The combined basis weight of the plurality of layers of fibers composed of carboxyalkyl cellulose or a salt thereof can be from about 160 g / m 2 to about 480 g / m 2 , about 160 g / m 2 to about 470 g / m 2 , about 160 g / m 2 to about 460 g / m 2 , about 160 g / m 2 to about 450 g / m 2 , about 160 g / m 2 to about 440 g / m 2 , about 160 g / m 2 to about 430 g / m 2 , about 160 g / m 2 to about 420 g / m 2 , about 160 g / m 2 to about 410 g / m 2 , about 160 g / m 2 to about 400 g / m 2 , about 160 g / m 2 to about 390 g / m 2 , about 160 g / m 2 to about 380 g / m 2 , about 160 g / m 2 to about 370 g / m 2 , about 160 g / m 2 to about 360 g / m 2 , about 160 g / m 2 to about 350 g / m 2 , about 160 g / m 2 to about 340 g / m 2 , about 160 g / m 2 to about 330 g / m 2 , about 160 g / m 2 to about 320 g / m 2 , about 160 g / m 2 to about 310 g / m 2 , about 160 g / m 2 to about 300 g / m 2 , about 160 g / m 2 to about 290 g / m 2 , about 160 g / m 2 to about 280 g / m 2 , about 160 g / m 2from about 270 g / m 2 , about 160 g / m 2 from about 260 g / m 2 , about 160 g / m 2 from about 250 g / m 2 , about 160 g / m 2 from about 240 g / m 2 , about 170 g / m 2 from about 230 g / m 2 , about 180 g / m 2 from about 220 g / m 2 , about 190 g / m 2 from about 210 g / m 2 , or about 200 g / m 2 .

[0098] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 160 g / m 2 to about 480 g / m 2 , about 160 g / m 2 to about 470 g / m 2 , about 160 g / m 2 to about 460 g / m 2 , about 160 g / m 2 to about 450 g / m 2 , about 160 g / m 2 to about 440 g / m 2 , about 160 g / m 2 to about 430 g / m 2 , about 160 g / m 2 to about 420 g / m 2 , about 160 g / m 2 to about 410 g / m 2 , about 160 g / m 2 to about 400 g / m 2 , about 160 g / m 2 to about 390 g / m 2 , about 160 g / m 2 to about 380 g / m 2 , about 160 g / m 2 to about 370 g / m 2 , about 160 g / m 2 to about 360 g / m 2 , about 160 g / m 2 to about 350 g / m 2 , about 160 g / m 2from about 340 g / m 2 , about 160 g / m 2 from about 330 g / m 2 , about 160 g / m 2 from about 320 g / m 2 , about 160 g / m 2 from about 310 g / m 2 , about 160 g / m 2 from about 300 g / m 2 , about 160 g / m 2 from about 280 g / m 2 , about 160 g / m 2 from about 270 g / m 2 , about 160 g / m 2 from about 260 g / m 2 , about 160 g / m 2 from about 250 g / m 2 , about 160 g / m 2 from about 240 g / m 2 , about 160 g / m 2 from about 230 g / m 2 , about 160 g / m 2 from about 220 g / m 2 , about 160 g / m 2 from about 210 g / m 2 , about 160 g / m 2 from about 200 g / m 2 , about 160 g / m 2 from about 190 g / m 2 , about 160 g / m 2 from about 180 g / m 2 , or about 160 g / m 2 from about 170 g / m 2 .

[0099] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 170 g / m 2 to about 480 g / m 2 , about 170 g / m 2 to about 470 g / m 2 , about 170 g / m 2 to about 460 g / m 2 , about 170 g / m 2 to about 450 g / m 2 , about 170 g / m 2 to about 440 g / m 2, about 170 g / m 2 to about 430 g / m 2 , about 170 g / m 2 to about 420 g / m 2 , about 170 g / m 2 to about 410 g / m 2 , about 170 g / m 2 to about 400 g / m 2 , about 170 g / m 2 to about 390 g / m 2 , about 170 g / m 2 to about 380 g / m 2 , about 170 g / m 2 to about 370 g / m 2 , about 170 g / m 2 to about 360 g / m 2 , about 170 g / m 2 to about 350 g / m 2 , about 170 g / m 2 to about 340 g / m 2 , about 170 g / m 2 to about 330 g / m 2 , about 170 g / m 2 to about 320 g / m 2 , about 170 g / m 2 to about 310 g / m 2 , about 170 g / m 2 to about 300 g / m 2 , about 170 g / m 2 to about 280 g / m 2 , about 170 g / m 2 to about 270 g / m 2 , about 170 g / m 2 to about 260 g / m 2 , about 170 g / m 2 to about 250 g / m 2 , about 170 g / m 2 to about 240 g / m 2 , about 170 g / m 2 to about 230 g / m 2 , about 170 g / m 2 to about 220 g / m 2 , about 170 g / m 2 to about 210 g / m 2 , about 170 g / m 2 to about 200 g / m2 about 170 g / m 2 to about 190 g / m 2 about 170 g / m 2 to about 180 g / m 2 .

[0100] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 180 g / m 2 to about 480 g / m 2 about 180 g / m 2 to about 470 g / m 2 about 180 g / m 2 to about 460 g / m 2 about 180 g / m 2 to about 450 g / m 2 about 180 g / m 2 to about 440 g / m 2 about 180 g / m 2 to about 430 g / m 2 about 180 g / m 2 to about 420 g / m 2 about 180 g / m 2 to about 410 g / m 2 about 180 g / m 2 to about 400 g / m 2 about 180 g / m 2 to about 390 g / m 2 about 180 g / m 2 to about 380 g / m 2 about 180 g / m 2 to about 370 g / m 2 about 180 g / m 2 to about 360 g / m 2 about 180 g / m 2 to about 350 g / m 2 about 180 g / m 2 to about 340 g / m 2 about 180 g / m 2 to about 330 g / m 2 about 180 g / m 2 to about 320 g / m 2 about 180 g / m 2 to about 310 g / m 2 about 180 g / m 2 to about 300 g / m 2 about 180 g / m2 from about 280 g / m 2 , about 180 g / m 2 from about 270 g / m 2 , about 180 g / m 2 from about 260 g / m 2 , about 180 g / m 2 from about 250 g / m 2 , about 180 g / m 2 from about 240 g / m 2 , about 180 g / m 2 from about 230 g / m 2 , about 180 g / m 2 from about 220 g / m 2 , about 180 g / m 2 from about 210 g / m 2 , about 180 g / m 2 from about 200 g / m 2 , or about 180 g / m 2 from about 190 g / m 2 .

[0101] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 190 g / m 2 to about 480 g / m 2 , about 190 g / m 2 to about 470 g / m 2 , about 190 g / m 2 to about 460 g / m 2 , about 190 g / m 2 to about 450 g / m 2 , about 190 g / m 2 to about 440 g / m 2 , about 190 g / m 2 to about 430 g / m 2 , about 190 g / m 2 to about 420 g / m 2 , about 190 g / m 2 to about 410 g / m 2 , about 190 g / m 2 to about 400 g / m 2 , about 190 g / m 2 to about 390 g / m 2 , about 190 g / m 2 to about 380 g / m 2 , about 190 g / m 2 to about 370 g / m2 about 190 g / m 2 to about 360 g / m 2 about 190 g / m 2 to about 350 g / m 2 about 190 g / m 2 to about 340 g / m 2 about 190 g / m 2 to about 330 g / m 2 about 190 g / m 2 to about 320 g / m 2 about 190 g / m 2 to about 310 g / m 2 about 190 g / m 2 to about 300 g / m 2 about 190 g / m 2 to about 280 g / m 2 about 190 g / m 2 to about 270 g / m 2 about 190 g / m 2 to about 260 g / m 2 about 190 g / m 2 to about 250 g / m 2 about 190 g / m 2 to about 240 g / m 2 about 190 g / m 2 to about 230 g / m 2 about 190 g / m 2 to about 220 g / m 2 about 190 g / m 2 to about 210 g / m 2 about 190 g / m 2 to about 200 g / m 2 .

[0102] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 200 g / m 2 to about 480 g / m 2 about 200 g / m 2 to about 470 g / m 2 about 200 g / m 2 to about 460 g / m 2 about 200 g / m 2 to about 450 g / m 2 about 200 g / m 2 to about 440 g / m 2 about 200 g / m2 to about 430 g / m 2 , about 200 g / m 2 to about 420 g / m 2 , about 200 g / m 2 to about 410 g / m 2 , about 200 g / m 2 to about 400 g / m 2 , about 200 g / m 2 to about 390 g / m 2 , about 200 g / m 2 to about 380 g / m 2 , about 200 g / m 2 to about 370 g / m 2 , about 200 g / m 2 to about 360 g / m 2 , about 200 g / m 2 to about 350 g / m 2 , about 200 g / m 2 to about 340 g / m 2 , about 200 g / m 2 to about 330 g / m 2 , about 200 g / m 2 to about 320 g / m 2 , about 200 g / m 2 to about 310 g / m 2 , about 200 g / m 2 to about 300 g / m 2 , about 200 g / m 2 to about 280 g / m 2 , about 200 g / m 2 to about 270 g / m 2 , about 200 g / m 2 to about 260 g / m 2 , about 200 g / m 2 to about 250 g / m 2 , about 200 g / m 2 to about 240 g / m 2 , about 200 g / m 2 to about 230 g / m 2 , about 200 g / m 2 to about 220 g / m 2 , or about 200 g / m 2 to about 210 g / m 2 .

[0103] The combined basis weight of the plurality of layers of fibers composed of carboxyalkyl cellulose or a salt thereof can be from about 210 g / m2to about 480 g / m2 2 to about 470 g / m2 2 , about 210 g / m2to about 460 g / m2 2 to about 450 g / m2 2 , about 210 g / m2to about 440 g / m2 2 to about 430 g / m2 2 , about 210 g / m2to about 420 g / m2 2 to about 410 g / m2 2 , about 210 g / m2to about 400 g / m2 2 to about 390 g / m2 2 , about 210 g / m2to about 380 g / m2 2 to about 370 g / m2 2 , about 210 g / m2to about 360 g / m2 2 to about 350 g / m2 2 , about 210 g / m2to about 340 g / m2 2 to about 330 g / m2 2 , about 210 g / m2to about 320 g / m2 2 to about 310 g / m2 2 , about 210 g / m2to about 300 g / m2 2 to about 280 g / m2 2 , about 210 g / m2to about 270 g / m2 2 to about 260 g / m2 2 , about 210 g / m2to about 250 g / m2 2 to about 240 g / m2 2 , about 210 g / m2to about 230 g / m2 2 to about 220 g / m2 2 , about 210 g / m2to about 210 g / m2 2 to about 200 g / m2 2 , about 210 g / m2to about 190 g / m2 2 to about 180 g / m2 2 , about 210 g / m2to about 170 g / m2 2 to about 160 g / m2 2 , about 210 g / m2to about 150 g / m2 2 to about 140 g / m2 2 , about 210 g / m2to about 130 g / m2 2 to about 120 g / m2 2 , about 210 g / m2to about 110 g / m2 2 to about 100 g / m2 2 , about 210 g / m2to about 90 g / m2 2 to about 80 g / m2 2 , about 210 g / m2to about 70 g / m2 2 to about 60 g / m2 2 , about 210 g / m2to about 50 g / m2 2 to about 40 g / m2 2about 210 g / m 2 about 240 g / m 2 about 210 g / m 2 about 230 g / m 2 about 210 g / m 2 about 220 g / m 2 about 210 g / m 2 about 210 g / m 2 .

[0104] about 220 g / m 2 about 480 g / m 2 about 220 g / m 2 about 470 g / m 2 about 220 g / m 2 about 460 g / m 2 about 220 g / m 2 about 450 g / m 2 about 220 g / m 2 about 440 g / m 2 about 220 g / m 2 about 430 g / m 2 about 220 g / m 2 about 420 g / m 2 about 220 g / m 2 about 410 g / m 2 about 220 g / m 2 about 400 g / m 2 about 220 g / m 2 about 390 g / m 2 about 220 g / m 2 about 380 g / m 2 about 220 g / m 2 about 370 g / m 2 about 220 g / m 2 about 360 g / m 2 about 220 g / m 2 about 350 g / m 2 about 220 g / m 2 about 340 g / m 2 about 220 g / m 2 about 330 g / m 2 about 220 g / m 2 about 320 g / m 2 about 220 g / m 2from about 310 g / m 2 , about 220 g / m 2 from about 300 g / m 2 , about 220 g / m 2 from about 280 g / m 2 , about 220 g / m 2 from about 270 g / m 2 , about 220 g / m 2 from about 260 g / m 2 , about 220 g / m 2 from about 250 g / m 2 , about 220 g / m 2 from about 240 g / m 2 , or about 220 g / m 2 from about 230 g / m 2 .

[0105] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 230 g / m 2 to about 480 g / m 2 , about 230 g / m 2 to about 470 g / m 2 , about 230 g / m 2 to about 460 g / m 2 , about 230 g / m 2 to about 450 g / m 2 , about 230 g / m 2 to about 440 g / m 2 , about 230 g / m 2 to about 430 g / m 2 , about 230 g / m 2 to about 420 g / m 2 , about 230 g / m 2 to about 410 g / m 2 , about 230 g / m 2 to about 400 g / m 2 , about 230 g / m 2 to about 390 g / m 2 , about 230 g / m 2 to about 380 g / m 2 , about 230 g / m 2 to about 370 g / m 2 , about 230 g / m 2 to about 360 g / m 2 , about 230 g / m 2 to about 350 g / m 2, about 230 g / m 2 to about 340 g / m 2 , about 230 g / m 2 to about 330 g / m 2 , about 230 g / m 2 to about 320 g / m 2 , about 230 g / m 2 to about 310 g / m 2 , about 230 g / m 2 to about 300 g / m 2 , about 230 g / m 2 to about 280 g / m 2 , about 230 g / m 2 to about 270 g / m 2 , about 230 g / m 2 to about 260 g / m 2 , about 230 g / m 2 to about 250 g / m 2 , or about 230 g / m 2 to about 240 g / m 2 .

[0106] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 240 g / m 2 to about 480 g / m 2 , about 240 g / m 2 to about 470 g / m 2 , about 240 g / m 2 to about 460 g / m 2 , about 240 g / m 2 to about 450 g / m 2 , about 240 g / m 2 to about 440 g / m 2 , about 240 g / m 2 to about 430 g / m 2 , about 240 g / m 2 to about 420 g / m 2 , about 240 g / m 2 to about 410 g / m 2 , about 240 g / m 2 to about 400 g / m 2 , about 240 g / m 2 to about 390 g / m 2 , about 240 g / m 2 to about 380 g / m 2 , about 240 g / m 2from about 370 g / m 2 , about 240 g / m 2 from about 360 g / m 2 , about 240 g / m 2 from about 350 g / m 2 , about 240 g / m 2 from about 340 g / m 2 , about 240 g / m 2 from about 330 g / m 2 , about 240 g / m 2 from about 320 g / m 2 , about 240 g / m 2 from about 310 g / m 2 , about 240 g / m 2 from about 300 g / m 2 , about 240 g / m 2 from about 280 g / m 2 , about 240 g / m 2 from about 270 g / m 2 , about 240 g / m 2 from about 260 g / m 2 , or about 240 g / m 2 from about 250 g / m 2 .

[0107] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 250 g / m 2 to about 480 g / m 2 , about 250 g / m 2 to about 470 g / m 2 , about 250 g / m 2 to about 460 g / m 2 , about 250 g / m 2 to about 450 g / m 2 , about 250 g / m 2 to about 440 g / m 2 , about 250 g / m 2 to about 430 g / m 2 , about 250 g / m 2 to about 420 g / m 2 , about 250 g / m 2 to about 410 g / m 2 , about 250 g / m 2 to about 400 g / m 2 , about 250 g / m 2 to about 390 g / m 2, about 250 g / m 2 to about 380 g / m 2 , about 250 g / m 2 to about 370 g / m 2 , about 250 g / m 2 to about 360 g / m 2 , about 250 g / m 2 to about 350 g / m 2 , about 250 g / m 2 to about 340 g / m 2 , about 250 g / m 2 to about 330 g / m 2 , about 250 g / m 2 to about 320 g / m 2 , about 250 g / m 2 to about 310 g / m 2 , about 250 g / m 2 to about 300 g / m 2 , about 250 g / m 2 to about 280 g / m 2 , about 250 g / m 2 to about 270 g / m 2 , or about 250 g / m 2 to about 260 g / m 2 .

[0108] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 260 g / m 2 to about 480 g / m 2 , about 260 g / m 2 to about 470 g / m 2 , about 260 g / m 2 to about 460 g / m 2 , about 260 g / m 2 to about 450 g / m 2 , about 260 g / m 2 to about 440 g / m 2 , about 260 g / m 2 to about 430 g / m 2 , about 260 g / m 2 to about 420 g / m 2 , about 260 g / m 2 to about 410 g / m 2 , about 260 g / m 2 to about 400 g / m 2 , about 260 g / m 2to about 390 g / m 2 , about 260 g / m 2 to about 380 g / m 2 , about 260 g / m 2 to about 370 g / m 2 , about 260 g / m 2 to about 360 g / m 2 , about 260 g / m 2 to about 350 g / m 2 , about 260 g / m 2 to about 340 g / m 2 , about 260 g / m 2 to about 330 g / m 2 , about 260 g / m 2 to about 320 g / m 2 , about 260 g / m 2 to about 310 g / m 2 , about 260 g / m 2 to about 300 g / m 2 , about 260 g / m 2 to about 280 g / m 2 , or about 260 g / m 2 to about 270 g / m 2 .

[0109] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 270 g / m 2 to about 480 g / m 2 , about 270 g / m 2 to about 470 g / m 2 , about 270 g / m 2 to about 460 g / m 2 , about 270 g / m 2 to about 450 g / m 2 , about 270 g / m 2 to about 440 g / m 2 , about 270 g / m 2 to about 430 g / m 2 , about 270 g / m 2 to about 420 g / m 2 , about 270 g / m 2 to about 410 g / m 2 , about 270 g / m 2 to about 400 g / m 2 , about 270 g / m 2 to about 390 g / m 2, about 270 g / m 2 to about 380 g / m 2 , about 270 g / m 2 to about 370 g / m 2 , about 270 g / m 2 to about 360 g / m 2 , about 270 g / m 2 to about 350 g / m 2 , about 270 g / m 2 to about 340 g / m 2 , about 270 g / m 2 to about 330 g / m 2 , about 270 g / m 2 to about 320 g / m 2 , about 270 g / m 2 to about 310 g / m 2 , about 270 g / m 2 to about 300 g / m 2 , or about 270 g / m 2 to about 280 g / m 2 .

[0110] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 280 g / m 2 to about 480 g / m 2 , about 280 g / m 2 to about 470 g / m 2 , about 280 g / m 2 to about 460 g / m 2 , about 280 g / m 2 to about 450 g / m 2 , about 280 g / m 2 to about 440 g / m 2 , about 280 g / m 2 to about 430 g / m 2 , about 280 g / m 2 to about 420 g / m 2 , about 280 g / m 2 to about 410 g / m 2 , about 280 g / m 2 to about 400 g / m 2 , about 280 g / m 2 to about 390 g / m 2 , about 280 g / m 2 to about 380 g / m 2 , about 280 g / m 2to about 370 g / m 2 , about 280 g / m 2 to about 360 g / m 2 , about 280 g / m 2 to about 350 g / m 2 , about 280 g / m 2 to about 340 g / m 2 , about 280 g / m 2 to about 330 g / m 2 , about 280 g / m 2 to about 320 g / m 2 , about 280 g / m 2 to about 310 g / m 2 , about 280 g / m 2 to about 300 g / m 2 , or about 280 g / m 2 to about 290 g / m 2 .

[0111] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 290 g / m 2 to about 480 g / m 2 , about 290 g / m 2 to about 470 g / m 2 , about 290 g / m 2 to about 460 g / m 2 , about 290 g / m 2 to about 450 g / m 2 , about 290 g / m 2 to about 440 g / m 2 , about 290 g / m 2 to about 430 g / m 2 , about 290 g / m 2 to about 420 g / m 2 , about 290 g / m 2 to about 410 g / m 2 , about 290 g / m 2 to about 400 g / m 2 , about 290 g / m 2 to about 390 g / m 2 , about 290 g / m 2 to about 380 g / m 2 , about 290 g / m 2 to about 370 g / m 2 , about 290 g / m 2 to about 360 g / m 2, about 290 g / m 2 to about 350 g / m 2 , about 290 g / m 2 to about 340 g / m 2 , about 290 g / m 2 to about 330 g / m 2 , about 290 g / m 2 to about 320 g / m 2 , about 290 g / m 2 to about 310 g / m 2 , or about 290 g / m 2 to about 300 g / m 2 .

[0112] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 300 g / m 2 to about 480 g / m 2 , about 300 g / m 2 to about 470 g / m 2 , about 300 g / m 2 to about 460 g / m 2 , about 300 g / m 2 to about 450 g / m 2 , about 300 g / m 2 to about 440 g / m 2 , about 300 g / m 2 to about 430 g / m 2 , about 300 g / m 2 to about 420 g / m 2 , about 300 g / m 2 to about 410 g / m 2 , about 300 g / m 2 to about 400 g / m 2 , about 300 g / m 2 to about 390 g / m 2 , about 300 g / m 2 to about 380 g / m 2 , about 300 g / m 2 to about 370 g / m 2 , about 300 g / m 2 to about 360 g / m 2 , about 300 g / m 2 to about 350 g / m 2 , about 300 g / m 2 to about 340 g / m 2 , about 300 g / m 2from about 330 g / m 2 , about 300 g / m 2 from about 320 g / m 2 , or about 300 g / m 2 from about 310 g / m 2 .

[0113] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 310 g / m 2 to about 480 g / m 2 , about 310 g / m 2 to about 470 g / m 2 , about 310 g / m 2 to about 460 g / m 2 , about 310 g / m 2 to about 450 g / m 2 , about 310 g / m 2 to about 440 g / m 2 , about 310 g / m 2 to about 430 g / m 2 , about 310 g / m 2 to about 420 g / m 2 , about 310 g / m 2 to about 410 g / m 2 , about 310 g / m 2 to about 400 g / m 2 , about 310 g / m 2 to about 390 g / m 2 , about 310 g / m 2 to about 380 g / m 2 , about 310 g / m 2 to about 370 g / m 2 , about 310 g / m 2 to about 360 g / m 2 , about 310 g / m 2 to about 350 g / m 2 , about 310 g / m 2 to about 340 g / m 2 , about 310 g / m 2 to about 330 g / m 2 , or about 310 g / m 2 to about 320 g / m 2 .

[0114] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 320 g / m 2 to about 480 g / m2 about 320 g / m 2 to about 470 g / m 2 about 320 g / m 2 to about 460 g / m 2 about 320 g / m 2 to about 450 g / m 2 about 320 g / m 2 to about 440 g / m 2 about 320 g / m 2 to about 430 g / m 2 about 320 g / m 2 to about 420 g / m 2 about 320 g / m 2 to about 410 g / m 2 about 320 g / m 2 to about 400 g / m 2 about 320 g / m 2 to about 390 g / m 2 about 320 g / m 2 to about 380 g / m 2 about 320 g / m 2 to about 370 g / m 2 about 320 g / m 2 to about 360 g / m 2 about 320 g / m 2 to about 350 g / m 2 about 320 g / m 2 to about 340 g / m 2 about 320 g / m 2 to about 330 g / m 2 .

[0115] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 330 g / m 2 to about 480 g / m 2 about 330 g / m 2 to about 470 g / m 2 about 330 g / m 2 to about 460 g / m 2 about 330 g / m 2 to about 450 g / m 2 about 330 g / m 2 to about 440 g / m 2 about 330 g / m 2 to about 430 g / m 2 about 330 g / m2 from about 420 g / m 2 , about 330 g / m 2 from about 410 g / m 2 , about 330 g / m 2 from about 400 g / m 2 , about 330 g / m 2 from about 390 g / m 2 , about 330 g / m 2 from about 380 g / m 2 , about 330 g / m 2 from about 370 g / m 2 , about 330 g / m 2 from about 360 g / m 2 , about 330 g / m 2 from about 350 g / m 2 , or about 330 g / m 2 from about 340 g / m 2 .

[0116] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 340 g / m 2 from about 480 g / m 2 , about 340 g / m 2 from about 470 g / m 2 , about 340 g / m 2 from about 460 g / m 2 , about 340 g / m 2 from about 450 g / m 2 , about 340 g / m 2 from about 440 g / m 2 , about 340 g / m 2 from about 430 g / m 2 , about 340 g / m 2 from about 420 g / m 2 , about 340 g / m 2 from about 410 g / m 2 , about 340 g / m 2 from about 400 g / m 2 , about 340 g / m 2 from about 390 g / m 2 , about 340 g / m 2 from about 380 g / m 2 , about 340 g / m 2 from about 370 g / m 2 , about 340 g / m 2 from about 360 g / m2 , or about 340 g / m 2 to about 350 g / m 2 .

[0117] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 350 g / m 2 to about 480 g / m 2 , about 350 g / m 2 to about 470 g / m 2 , about 350 g / m 2 to about 460 g / m 2 , about 350 g / m 2 to about 450 g / m 2 , about 350 g / m 2 to about 440 g / m 2 , about 350 g / m 2 to about 430 g / m 2 , about 350 g / m 2 to about 420 g / m 2 , about 350 g / m 2 to about 410 g / m 2 , about 350 g / m 2 to about 400 g / m 2 , about 350 g / m 2 to about 390 g / m 2 , about 350 g / m 2 to about 380 g / m 2 , about 350 g / m 2 to about 370 g / m 2 , or about 350 g / m 2 to about 360 g / m 2 .

[0118] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 360 g / m 2 to about 480 g / m 2 , about 360 g / m 2 to about 470 g / m 2 , about 360 g / m 2 to about 460 g / m 2 , about 360 g / m 2 to about 450 g / m 2 , about 360 g / m 2 to about 440 g / m 2 , about 360 g / m 2 to about 430 g / m 2about 360 g / m 2 to about 420 g / m 2 about 360 g / m 2 to about 410 g / m 2 about 360 g / m 2 to about 400 g / m 2 about 360 g / m 2 to about 390 g / m 2 about 360 g / m 2 to about 380 g / m 2 about 360 g / m 2 to about 370 g / m 2 .

[0119] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 370 g / m 2 to about 480 g / m 2 about 370 g / m 2 to about 470 g / m 2 about 370 g / m 2 to about 460 g / m 2 about 370 g / m 2 to about 450 g / m 2 about 370 g / m 2 to about 440 g / m 2 about 370 g / m 2 to about 430 g / m 2 about 370 g / m 2 to about 420 g / m 2 about 370 g / m 2 to about 410 g / m 2 about 370 g / m 2 to about 400 g / m 2 about 370 g / m 2 to about 390 g / m 2 about 370 g / m 2 to about 380 g / m 2 .

[0120] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about 380 g / m 2 to about 480 g / m 2 about 380 g / m 2 to about 470 g / m 2 about 380 g / m 2 to about 460 g / m 2 about 380 g / m2 from about 450 g / m 2 , about 380 g / m 2 from about 440 g / m 2 , about 380 g / m 2 from about 430 g / m 2 , about 380 g / m 2 from about 420 g / m 2 , about 380 g / m 2 from about 410 g / m 2 , about 380 g / m 2 from about 400 g / m 2 , or about 380 g / m 2 from about 390 g / m 2 .

[0121] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 390 g / m 2 from about 480 g / m 2 , about 390 g / m 2 from about 470 g / m 2 , about 390 g / m 2 from about 460 g / m 2 , about 390 g / m 2 from about 450 g / m 2 , about 390 g / m 2 from about 440 g / m 2 , about 390 g / m 2 from about 430 g / m 2 , about 390 g / m 2 from about 420 g / m 2 , about 390 g / m 2 from about 410 g / m 2 , or about 390 g / m 2 from about 400 g / m 2 .

[0122] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 400 g / m 2 from about 480 g / m 2 , about 400 g / m 2 from about 470 g / m 2 , about 400 g / m 2 from about 460 g / m 2 , about 400 g / m 2 from about 450 g / m 2 , about 400 g / m 2from about 440 g / m 2 , about 400 g / m 2 from about 430 g / m 2 , about 400 g / m 2 from about 420 g / m 2 , or about 400 g / m 2 from about 410 g / m 2 .

[0123] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 410 g / m 2 to about 480 g / m 2 , about 410 g / m 2 to about 470 g / m 2 , about 410 g / m 2 to about 460 g / m 2 , about 410 g / m 2 to about 450 g / m 2 , about 410 g / m 2 to about 440 g / m 2 , about 410 g / m 2 to about 430 g / m 2 , or about 410 g / m 2 to about 420 g / m 2 .

[0124] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 420 g / m 2 to about 480 g / m 2 , about 420 g / m 2 to about 470 g / m 2 , about 420 g / m 2 to about 460 g / m 2 , about 420 g / m 2 to about 450 g / m 2 , about 420 g / m 2 to about 440 g / m 2 , or about 420 g / m 2 to about 430 g / m 2 .

[0125] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 430 g / m 2 to about 480 g / m 2 , about 430 g / m 2 to about 470 g / m 2 , about 430 g / m 2from about 460 g / m 2 , or about 430 g / m 2 from about 450 g / m 2 , or about 430 g / m 2 from about 440 g / m 2 .

[0126] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 440 g / m 2 to about 480 g / m 2 , about 440 g / m 2 to about 470 g / m 2 , about 440 g / m 2 to about 460 g / m 2 , or about 440 g / m 2 to about 450 g / m 2 .

[0127] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 450 g / m 2 to about 480 g / m 2 , about 450 g / m 2 to about 470 g / m 2 , or about 450 g / m 2 to about 460 g / m 2 .

[0128] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 460 g / m 2 to about 480 g / m 2 , or about 460 g / m 2 to about 470 g / m 2 .

[0129] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 470 g / m 2 to about 480 g / m 2 .

[0130] The combined basis weight of the multiple layers of fibers of carboxyalkyl cellulose or a salt thereof can be from about 140 g / m 2 , about 145 g / m 2 , about 150 g / m 2 , about 155 g / m 2 , about 160 g / m 2 , about 165 g / m 2 , about 170 g / m 2 , about 175 g / m 2about 180 g / m 2 about 185 g / m 2 about 190 g / m 2 about 195 g / m 2 about 200 g / m 2 about 205 g / m 2 about 210 g / m 2 about 215 g / m 2 about 220 g / m 2 about 225 g / m 2 about 230 g / m 2 about 235 g / m 2 about 240 g / m 2 about 245 g / m 2 about 250 g / m 2 about 255 g / m 2 about 260 g / m 2 about 270 g / m 2 about 280 g / m 2 about 290 g / m 2 about 300 g / m 2 about 310 g / m 2 about 320 g / m 2 about 330 g / m 2 about 340 g / m 2 about 350 g / m 2 about 360 g / m 2 about 370 g / m 2 about 380 g / m 2 about 390 g / m 2 about 400 g / m 2 about 410 g / m 2 about 420 g / m 2 about 430 g / m 2 about 440 g / m 2 about 450 g / m 2 about 460 g / m 2 about 470 g / m 2 or about 480 g / m 2 .

[0131] The combined basis weight of the plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof can be about at least about 140 g / m 2 at least about 145 g / m 2 at least about 150 g / m 2 at least about 155 g / m2 at least about 160 g / m2 2 at least about 165 g / m2 2 at least about 170 g / m2 2 at least about 175 g / m2 2 at least about 180 g / m2 2 at least about 185 g / m2 2 at least about 190 g / m2 2 at least about 195 g / m2 2 at least about 200 g / m2 2 at least about 205 g / m2 2 at least about 210 g / m2 2 at least about 215 g / m2 2 at least about 220 g / m2 2 at least about 225 g / m2 2 at least about 230 g / m2 2 at least about 235 g / m2 2 at least about 240 g / m2 2 at least about 245 g / m2 2 at least about 250 g / m2 2 at least about 255 g / m2 2 at least about 260 g / m2 2 at least about 270 g / m2 2 at least about 280 g / m2 2 at least about 290 g / m2 2 at least about 300 g / m2 2 at least about 310 g / m2 2 at least about 320 g / m2 2 at least about 330 g / m2 2 at least about 340 g / m2 2 at least about 350 g / m2 2 at least about 360 g / m2 2 at least about 370 g / m2 2 at least about 380 g / m2 2 at least about 390 g / m2 2 at least about 400 g / m2 2 at least about 410 g / m2 2 at least about 420 g / m2 2 at least about 430 g / m2 2 at least about 440 g / m2 2 at least about 450 g / m2 2 at least about 460 g / m2 2, at least about 470 g / m 2 2, at least about 480 g / m 2 2.

[0132] The combined basis weight of the plurality of layers of fibers composed of carboxyalkyl cellulose or a salt thereof can be no more than about 140 g / m 2 2, no more than about 145 g / m 2 2, no more than about 150 g / m 2 2, no more than about 155 g / m 2 2, no more than about 160 g / m 2 2, no more than about 165 g / m 2 2, no more than about 170 g / m 2 2, no more than about 175 g / m 2 2, no more than about 180 g / m 2 2, no more than about 185 g / m 2 2, no more than about 190 g / m 2 2, no more than about 195 g / m 2 2, no more than about 200 g / m 2 2, no more than about 205 g / m 2 2, no more than about 210 g / m 2 2, no more than about 215 g / m 2 2, no more than about 220 g / m 2 2, no more than about 225 g / m 2 2, no more than about 230 g / m 2 2, no more than about 235 g / m 2 2, no more than about 240 g / m 2 2, no more than about 245 g / m 2 2, no more than about 250 g / m 2 2, no more than about 255 g / m 2 2, no more than about 260 g / m 2 2, no more than about 270 g / m 2 2, no more than about 280 g / m 2 2, no more than about 290 g / m 2 2, no more than about 300 g / m 2 2, no more than about 310 g / m 2 2, no more than about 320 g / m 2 2, no more than about 330 g / m 2 2, no more than about 340 g / m 2 2, no more than about 350 g / m 2 2, no more than about 360 g / m 2 2, no more than about 370 g / m 2 2, no more than about 380 g / m 2 , no more than about 390 g / m 2 , no more than about 400 g / m 2 , no more than about 410 g / m 2 , no more than about 420 g / m 2 , no more than about 430 g / m 2 , no more than about 440 g / m 2 , no more than about 450 g / m 2 , no more than about 460 g / m 2 , no more than about 470 g / m 2 , or no more than about 480 g / m 2 .

[0133] Thus, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises a silver ion-containing antimicrobial agent, wherein the wound contact layer includes a plurality of layers, each layer formed of fibers of carboxyalkyl cellulose or a salt thereof, and further wherein the combined basis weight of the plurality of layers is in the range of 160 g / m 2 to 240 g / m 2 .

[0134] The wound contact layer can include any number of layers formed of fibers of carboxyalkyl cellulose or a salt thereof. For example, the wound contact layer can include one, two, three, four, five, six, seven, eight, nine, ten, eleven, twelve, or more layers formed of fibers of carboxyalkyl cellulose or a salt thereof.

[0135] Thus, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises a silver ion-containing antimicrobial agent, wherein the wound contact layer includes a plurality of layers, each layer formed of fibers of carboxyalkyl cellulose or a salt thereof, and further wherein the wound contact layer includes only two layers.

[0136] In a preferred embodiment, the wound contact layer comprises two layers of fibers of carboxyalkyl cellulose or a salt thereof, each layer having a basis weight of about 100 g / m 2 Thus, the combined basis weight of the layers of the wound contact layer is about 200 g / m 2 .

[0137] Thus, in some embodiments, there is provided a negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises a silver ion containing antimicrobial agent, wherein the wound contact layer comprises a plurality of layers, each layer being formed of fibers of carboxyalkyl cellulose or a salt thereof, and further wherein the wound contact layer comprises only two layers, and further wherein each layer has a basis weight of 100 g / m 2 .

[0138] In embodiments comprising a plurality of layers of fibers of carboxyalkyl cellulose or a salt thereof, at least two of the plurality of layers can be reinforced / bonded by stitching / sewing or lamination. The at least two layers can be reinforced / bonded using cellulose yarn, such as Lyocell yarn. Advantageously, this results in highly aligned cellulose fibers with a high degree of crystallinity, such that the cellulose fibers are generally stronger, and thus they are able to withstand the manufacturing process and provide a stronger, non-degrading in use, wound contact layer. This also enhances the strength of the absorbent structure of the wound dressing.

[0139] Thus, in some embodiments, there is provided a negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises a silver ion containing antimicrobial agent, wherein the wound contact layer comprises a plurality of layers, each layer being formed of fibers of carboxyalkyl cellulose or a salt thereof, and further wherein the plurality of layers are reinforced by stitching or lamination.

[0140] Thus, in some embodiments, a negative pressure wound dressing is provided comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer comprises two layers each formed of fibers of carboxyalkyl cellulose or a salt thereof, further wherein the plurality of layers are reinforced by stitching.

[0141] The silver ions can be bound to the polymer backbone of the fibers of carboxyalkyl cellulose or a salt thereof.

[0142] The silver ions can be in the form of any silver (Ag+) salt, such as in the form of silver nitrate, silver sulfate, silver chloride, silver sulfadiazine, or a combination thereof.

[0143] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.10 wt.% to about 10.0 wt.%, from about 0.10 wt.% to about 9.0 wt.%, from about 0.10 wt.% to about 8.0 wt.%, from about 0.10 wt.% to about 7.0 wt.%, from about 0.10 wt.% to about 6.0 wt.%, from about 0.10 wt.% to about 5.0 wt.%, from about 0.10 wt.% to about 4.0 wt.%, from about 0.10 wt.% to about 3.0 wt.%, from about 0.10 wt.% to about 2.0 wt.%, from about 0.10 wt.% to about 1.80 wt.%, from about 0.10 wt.% to about 1.60 wt.%, from about 0.10 wt.% to about 1.50 wt.%, from about 0.10 wt.% to about 1.40 wt.%, from about 0.10 wt.% to about 1.35 wt.%, from about 0.10 wt.% to about 1.30 wt.%, from about 0.10 wt.% to about 1.25 wt.%, from about 0.10 wt.% to about 1.20 wt.%, from about 0.10 wt.% to about 1.15 wt.%, from about 0.10 wt.% to about 1.10 wt.%, from about 0.10 wt.% to about 1.05 wt.%, from about 0.10 wt.% to about 1.00 wt.%, from about 0.10 wt.% to about 0.95 wt.%, from about 0.10 wt.% to about 0.90 wt.%, from about 0.10 wt.% to about 0.85 wt.%, from about 0.10 wt.% to about 0.80 wt.%, from about 0.10 wt.% to about 0.75 wt.%, from about 0.10 wt.% to about 0.70 wt.%, from about 0.10 wt.% to about 0.65 wt.%, from about 0.10 wt.% to about 0.60 wt.%, from about 0.10 wt.% to about 0.55 wt.%, from about 0.10 wt.% to about 0.50 wt.%, from about 0.10 wt.% to about 0.45 wt.%, from about 0.10 wt.% to about 0.40 wt.%, from about 0.10 wt.% to about 0.35 wt.%, from about 0.10 wt.% to about 0.30 wt.%, from about 0.10 wt.% to about 0.25 wt.%, from about 0.10 wt.% to about 0.20 wt.%, or from about 0.10 wt.% to about 0.15 wt.%.

[0144] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.15 wt.% to about 10.0 wt.%, from about 0.15 wt.% to about 9.0 wt.%, from about 0.15 wt.% to about 8.0 wt.%, from about 0.15 wt.% to about 7.0 wt.%, from about 0.15 wt.% to about 6.0 wt.%, from about 0.15 wt.% to about 5.0 wt.%, from about 0.15 wt.% to about 4.0 wt.%, from about 0.15 wt.% to about 3.0 wt.%, from about 0.15 wt.% to about 2.0 wt.%, from about 0.15 wt.% to about 1.80 wt.%, from about 0.15 wt.% to about 1.60 wt.%, from about 0.15 wt.% to about 1.50 wt.%, from about 0.15 wt.% to about 1.40 wt.%, from about 0.15 wt.% to about 1.35 wt.%, from about 0.15 wt.% to about 1.30 wt.%, from about 0.15 wt.% to about 1.25 wt.%, from about 0.15 wt.% to about 1.20 wt.%, from about 0.15 wt.% to about 1.15 wt.%, from about 0.15 wt.% to about 1.10 wt.%, from about 0.15 wt.% to about 1.05 wt.%, from about 0.15 wt.% to about 1.00 wt.%, from about 0.15 wt.% to about 0.95 wt.%, from about 0.15 wt.% to about 0.90 wt.%, from about 0.15 wt.% to about 0.85 wt.%, from about 0.15 wt.% to about 0.80 wt.%, from about 0.15 wt.% to about 0.75 wt.%, from about 0.15 wt.% to about 0.70 wt.%, from about 0.15 wt.% to about 0.65 wt.%, from about 0.15 wt.% to about 0.60 wt.%, from about 0.15 wt.% to about 0.55 wt.%, from about 0.15 wt.% to about 0.50 wt.%, from about 0.15 wt.% to about 0.45 wt.%, from about 0.15 wt.% to about 0.40 wt.%, from about 0.15 wt.% to about 0.35 wt.%, from about 0.15 wt.% to about 0.30 wt.%, from about 0.15 wt.% to about 0.25 wt.%, or from about 0.15 wt.% to about 0.20 wt.%.

[0145] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.20 wt.% to about 10.0 wt.%, from about 0.20 wt.% to about 9.0 wt.%, from about 0.20 wt.% to about 8.0 wt.%, from about 0.20 wt.% to about 7.0 wt.%, from about 0.20 wt.% to about 6.0 wt.%, from about 0.20 wt.% to about 5.0 wt.%, from about 0.20 wt.% to about 4.0 wt.%, from about 0.20 wt.% to about 3.0 wt.%, from about 0.20 wt.% to about 2.0 wt.%, from about 0.20 wt.% to about 1.80 wt.%, from about 0.20 wt.% to about 1.60 wt.%, from about 0.20 wt.% to about 1.50 wt.%, from about 0.20 wt.% to about 1.40 wt.%, from about 0.20 wt.% to about 1.35 wt.%, from about 0.20 wt.% to about 1.30 wt.%, from about 0.20 wt.% to about 1.25 wt.%, from about 0.20 wt.% to about 1.20 wt.%, from about 0.20 wt.% to about 1.15 wt.%, from about 0.20 wt.% to about 1.10 wt.%, from about 0.20 wt.% to about 1.05 wt.%, from about 0.20 wt.% to about 1.00 wt.%, from about 0.20 wt.% to about 0.95 wt.%, from about 0.20 wt.% to about 0.90 wt.%, from about 0.20 wt.% to about 0.85 wt.%, from about 0.20 wt.% to about 0.80 wt.%, from about 0.20 wt.% to about 0.75 wt.%, from about 0.20 wt.% to about 0.70 wt.%, from about 0.20 wt.% to about 0.65 wt.%, from about 0.20 wt.% to about 0.60 wt.%, from about 0.20 wt.% to about 0.55 wt.%, from about 0.20 wt.% to about 0.50 wt.%, from about 0.20 wt.% to about 0.45 wt.%, from about 0.20 wt.% to about 0.40 wt.%, from about 0.20 wt.% to about 0.35 wt.%, from about 0.20 wt.% to about 0.30 wt.%, or from about 0.20 wt.% to about 0.25 wt.%.

[0146] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.25 wt.% to about 10.0 wt.%, from about 0.25 wt.% to about 9.0 wt.%, from about 0.25 wt.% to about 8.0 wt.%, from about 0.25 wt.% to about 7.0 wt.%, from about 0.25 wt.% to about 6.0 wt.%, from about 0.25 wt.% to about 5.0 wt.%, from about 0.25 wt.% to about 4.0 wt.%, from about 0.25 wt.% to about 3.0 wt.%, from about 0.25 wt.% to about 2.0 wt.%, from about 0.25 wt.% to about 1.80 wt.%, from about 0.25 wt.% to about 1.60 wt.%, from about 0.25 wt.% to about 1.50 wt.%, from about 0.25 wt.% to about 1.40 wt.%, from about 0.25 wt.% to about 1.35 wt.%, from about 0.25 wt.% to about 1.30 wt.%, from about 0.25 wt.% to about 1.25 wt.%, from about 0.25 wt.% to about 1.20 wt.%, from about 0.25 wt.% to about 1.15 wt.%, from about 0.25 wt.% to about 1.10 wt.%, from about 0.25 wt.% to about 1.05 wt.%, from about 0.25 wt.% to about 1.00 wt.%, from about 0.25 wt.% to about 0.95 wt.%, from about 0.25 wt.% to about 0.90 wt.%, from about 0.25 wt.% to about 0.85 wt.%, from about 0.25 wt.% to about 0.80 wt.%, from about 0.25 wt.% to about 0.75 wt.%, from about 0.25 wt.% to about 0.70 wt.%, from about 0.25 wt.% to about 0.65 wt.%, from about 0.25 wt.% to about 0.60 wt.%, from about 0.25 wt.% to about 0.55 wt.%, from about 0.25 wt.% to about 0.50 wt.%, from about 0.25 wt.% to about 0.45 wt.%, from about 0.25 wt.% to about 0.40 wt.%, from about 0.25 wt.% to about 0.35 wt.%, or from about 0.25 wt.% to about 0.30 wt.%.

[0147] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.30 wt.% to about 10.0 wt.%, from about 0.30 wt.% to about 9.0 wt.%, from about 0.30 wt.% to about 8.0 wt.%, from about 0.30 wt.% to about 7.0 wt.%, from about 0.30 wt.% to about 6.0 wt.%, from about 0.30 wt.% to about 5.0 wt.%, from about 0.30 wt.% to about 4.0 wt.%, from about 0.30 wt.% to about 3.0 wt.%, from about 0.30 wt.% to about 2.0 wt.%, from about 0.30 wt.% to about 1.80 wt.%, from about 0.30 wt.% to about 1.60 wt.%, from about 0.30 wt.% to about 1.50 wt.%, from about 0.30 wt.% to about 1.40 wt.%, from about 0.30 wt.% to about 1.35 wt.%, from about 0.30 wt.% to about 1.30 wt.%, from about 0.30 wt.% to about 1.25 wt.%, from about 0.30 wt.% to about 1.20 wt.%, from about 0.30 wt.% to about 1.15 wt.%, from about 0.30 wt.% to about 1.10 wt.%, from about 0.30 wt.% to about 1.05 wt.%, from about 0.30 wt.% to about 1.00 wt.%, from about 0.30 wt.% to about 0.95 wt.%, from about 0.30 wt.% to about 0.90 wt.%, from about 0.30 wt.% to about 0.85 wt.%, from about 0.30 wt.% to about 0.80 wt.%, from about 0.30 wt.% to about 0.75 wt.%, from about 0.30 wt.% to about 0.70 wt.%, from about 0.30 wt.% to about 0.65 wt.%, from about 0.30 wt.% to about 0.60 wt.%, from about 0.30 wt.% to about 0.55 wt.%, from about 0.30 wt.% to about 0.50 wt.%, from about 0.30 wt.% to about 0.45 wt.%, from about 0.30 wt.% to about 0.40 wt.%, or from about 0.30 wt.% to about 0.35 wt.%.

[0148] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.35 wt.% to about 10.0 wt.%, from about 0.35 wt.% to about 9.0 wt.%, from about 0.35 wt.% to about 8.0 wt.%, from about 0.35 wt.% to about 7.0 wt.%, from about 0.35 wt.% to about 6.0 wt.%, from about 0.35 wt.% to about 5.0 wt.%, from about 0.35 wt.% to about 4.0 wt.%, from about 0.35 wt.% to about 3.0 wt.%, from about 0.35 wt.% to about 2.0 wt.%, from about 0.35 wt.% to about 1.80 wt.%, from about 0.35 wt.% to about 1.60 wt.%, from about 0.35 wt.% to about 1.50 wt.%, from about 0.35 wt.% to about 1.40 wt.%, from about 0.35 wt.% to about 1.35 wt.%, from about 0.35 wt.% to about 1.30 wt.%, from about 0.35 wt.% to about 1.25 wt.%, from about 0.35 wt.% to about 1.20 wt.%, from about 0.35 wt.% to about 1.15 wt.%, from about 0.35 wt.% to about 1.10 wt.%, from about 0.35 wt.% to about 1.05 wt.%, from about 0.35 wt.% to about 1.00 wt.%, from about 0.35 wt.% to about 0.95 wt.%, from about 0.35 wt.% to about 0.90 wt.%, from about 0.35 wt.% to about 0.85 wt.%, from about 0.35 wt.% to about 0.80 wt.%, from about 0.35 wt.% to about 0.75 wt.%, from about 0.35 wt.% to about 0.70 wt.%, from about 0.35 wt.% to about 0.65 wt.%, from about 0.35 wt.% to about 0.60 wt.%, from about 0.35 wt.% to about 0.55 wt.%, from about 0.35 wt.% to about 0.50 wt.%, from about 0.35 wt.% to about 0.45 wt.%, or from about 0.35 wt.% to about 0.40 wt.%.

[0149] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.40 wt.% to about 10.0 wt.%, from about 0.40 wt.% to about 9.0 wt.%, from about 0.40 wt.% to about 8.0 wt.%, from about 0.40 wt.% to about 7.0 wt.%, from about 0.40 wt.% to about 6.0 wt.%, from about 0.40 wt.% to about 5.0 wt.%, from about 0.40 wt.% to about 4.0 wt.%, from about 0.40 wt.% to about 3.0 wt.%, from about 0.40 wt.% to about 2.0 wt.%, from about 0.40 wt.% to about 1.80 wt.%, from about 0.40 wt.% to about 1.60 wt.%, from about 0.40 wt.% to about 1.50 wt.%, from about 0.40 wt.% to about 1.40 wt.%, from about 0.40 wt.% to about 1.35 wt.%, from about 0.40 wt.% to about 1.30 wt.%, from about 0.40 wt.% to about 1.25 wt.%, from about 0.40 wt.% to about 1.20 wt.%, from about 0.40 wt.% to about 1.15 wt.%, from about 0.40 wt.% to about 1.10 wt.%, from about 0.40 wt.% to about 1.05 wt.%, from about 0.40 wt.% to about 1.00 wt.%, from about 0.40 wt.% to about 0.95 wt.%, from about 0.40 wt.% to about 0.90 wt.%, from about 0.40 wt.% to about 0.85 wt.%, from about 0.40 wt.% to about 0.80 wt.%, from about 0.40 wt.% to about 0.75 wt.%, from about 0.40 wt.% to about 0.70 wt.%, from about 0.40 wt.% to about 0.65 wt.%, from about 0.40 wt.% to about 0.60 wt.%, from about 0.40 wt.% to about 0.55 wt.%, from about 0.40 wt.% to about 0.50 wt.%, or from about 0.40 wt.% to about 0.45 wt.%.

[0150] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.45 wt.% to about 10.0 wt.%, from about 0.45 wt.% to about 9.0 wt.%, from about 0.45 wt.% to about 8.0 wt.%, from about 0.45 wt.% to about 7.0 wt.%, from about 0.45 wt.% to about 6.0 wt.%, from about 0.45 wt.% to about 5.0 wt.%, from about 0.45 wt.% to about 4.0 wt.%, from about 0.45 wt.% to about 3.0 wt.%, from about 0.45 wt.% to about 2.0 wt.%, from about 0.45 wt.% to about 1.80 wt.%, from about 0.45 wt.% to about 1.60 wt.%, from about 0.45 wt.% to about 1.50 wt.%, from about 0.45 wt.% to about 1.40 wt.%, from about 0.45 wt.% to about 1.35 wt.%, from about 0.45 wt.% to about 1.30 wt.%, from about 0.45 wt.% to about 1.25 wt.%, from about 0.45 wt.% to about 1.20 wt.%, from about 0.45 wt.% to about 1.15 wt.%, from about 0.45 wt.% to about 1.10 wt.%, from about 0.45 wt.% to about 1.05 wt.%, from about 0.45 wt.% to about 1.00 wt.%, from about 0.45 wt.% to about 0.95 wt.%, from about 0.45 wt.% to about 0.90 wt.%, from about 0.45 wt.% to about 0.85 wt.%, from about 0.45 wt.% to about 0.80 wt.%, from about 0.45 wt.% to about 0.75 wt.%, from about 0.45 wt.% to about 0.70 wt.%, from about 0.45 wt.% to about 0.65 wt.%, from about 0.45 wt.% to about 0.60 wt.%, from about 0.45 wt.% to about 0.55 wt.%, or from about 0.45 wt.% to about 0.50 wt.%.

[0151] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.50 wt.% to about 10.0 wt.%, from about 0.50 wt.% to about 9.0 wt.%, from about 0.50 wt.% to about 8.0 wt.%, from about 0.50 wt.% to about 7.0 wt.%, from about 0.50 wt.% to about 6.0 wt.%, from about 0.50 wt.% to about 5.0 wt.%, from about 0.50 wt.% to about 4.0 wt.%, from about 0.50 wt.% to about 3.0 wt.%, from about 0.50 wt.% to about 2.0 wt.%, from about 0.50 wt.% to about 1.80 wt.%, from about 0.50 wt.% to about 1.60 wt.%, from about 0.50 wt.% to about 1.50 wt.%, from about 0.50 wt.% to about 1.40 wt.%, from about 0.50 wt.% to about 1.35 wt.%, from about 0.50 wt.% to about 1.30 wt.%, from about 0.50 wt.% to about 1.25 wt.%, from about 0.50 wt.% to about 1.20 wt.%, from about 0.50 wt.% to about 1.15 wt.%, from about 0.50 wt.% to about 1.10 wt.%, from about 0.50 wt.% to about 1.05 wt.%, from about 0.50 wt.% to about 1.00 wt.%, from about 0.50 wt.% to about 0.95 wt.%, from about 0.50 wt.% to about 0.90 wt.%, from about 0.50 wt.% to about 0.85 wt.%, from about 0.50 wt.% to about 0.80 wt.%, from about 0.50 wt.% to about 0.75 wt.%, from about 0.50 wt.% to about 0.70 wt.%, from about 0.50 wt.% to about 0.65 wt.%, from about 0.50 wt.% to about 0.60 wt.%, or from about 0.50 wt.% to about 0.55 wt.%.

[0152] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.55 wt.% to about 10.0 wt.%, from about 0.55 wt.% to about 9.0 wt.%, from about 0.55 wt.% to about 8.0 wt.%, from about 0.55 wt.% to about 7.0 wt.%, from about 0.55 wt.% to about 6.0 wt.%, from about 0.55 wt.% to about 5.0 wt.%, from about 0.55 wt.% to about 4.0 wt.%, from about 0.55 wt.% to about 3.0 wt.%, from about 0.55 wt.% to about 2.0 wt.%, from about 0.55 wt.% to about 1.80 wt.%, from about 0.55 wt.% to about 1.60 wt.%, from about 0.55 wt.% to about 1.50 wt.%, from about 0.55 wt.% to about 1.40 wt.%, from about 0.55 wt.% to about 1.35 wt.%, from about 0.55 wt.% to about 1.30 wt.%, from about 0.55 wt.% to about 1.25 wt.%, from about 0.55 wt.% to about 1.20 wt.%, from about 0.55 wt.% to about 1.15 wt.%, from about 0.55 wt.% to about 1.10 wt.%, from about 0.55 wt.% to about 1.05 wt.%, from about 0.55 wt.% to about 1.00 wt.%, from about 0.55 wt.% to about 0.95 wt.%, from about 0.55 wt.% to about 0.90 wt.%, from about 0.55 wt.% to about 0.85 wt.%, from about 0.55 wt.% to about 0.80 wt.%, from about 0.55 wt.% to about 0.75 wt.%, from about 0.55 wt.% to about 0.70 wt.%, from about 0.55 wt.% to about 0.65 wt.%, or from about 0.55 wt.% to about 0.60 wt.%.

[0153] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.60 wt.% to about 10.0 wt.%, from about 0.60 wt.% to about 9.0 wt.%, from about 0.60 wt.% to about 8.0 wt.%, from about 0.60 wt.% to about 7.0 wt.%, from about 0.60 wt.% to about 6.0 wt.%, from about 0.60 wt.% to about 5.0 wt.%, from about 0.60 wt.% to about 4.0 wt.%, from about 0.60 wt.% to about 3.0 wt.%, from about 0.60 wt.% to about 2.0 wt.%, from about 0.60 wt.% to about 1.80 wt.%, from about 0.60 wt.% to about 1.60 wt.%, from about 0.60 wt.% to about 1.50 wt.%, from about 0.60 wt.% to about 1.40 wt.%, from about 0.60 wt.% to about 1.35 wt.%, from about 0.60 wt.% to about 1.30 wt.%, from about 0.60 wt.% to about 1.25 wt.%, from about 0.60 wt.% to about 1.20 wt.%, from about 0.60 wt.% to about 1.15 wt.%, from about 0.60 wt.% to about 1.10 wt.%, from about 0.60 wt.% to about 1.05 wt.%, from about 0.60 wt.% to about 1.00 wt.%, from about 0.60 wt.% to about 0.95 wt.%, from about 0.60 wt.% to about 0.90 wt.%, from about 0.60 wt.% to about 0.85 wt.%, from about 0.60 wt.% to about 0.80 wt.%, from about 0.60 wt.% to about 0.75 wt.%, from about 0.60 wt.% to about 0.70 wt.%, or from about 0.60 wt.% to about 0.65 wt.%.

[0154] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.65 wt.% to about 10.0 wt.%, from about 0.65 wt.% to about 9.0 wt.%, from about 0.65 wt.% to about 8.0 wt.%, from about 0.65 wt.% to about 7.0 wt.%, from about 0.65 wt.% to about 6.0 wt.%, from about 0.65 wt.% to about 5.0 wt.%, from about 0.65 wt.% to about 4.0 wt.%, from about 0.65 wt.% to about 3.0 wt.%, from about 0.65 wt.% to about 2.0 wt.%, from about 0.65 wt.% to about 1.80 wt.%, from about 0.65 wt.% to about 1.60 wt.%, from about 0.65 wt.% to about 1.50 wt.%, from about 0.65 wt.% to about 1.40 wt.%, from about 0.65 wt.% to about 1.35 wt.%, from about 0.65 wt.% to about 1.30 wt.%, from about 0.65 wt.% to about 1.25 wt.%, from about 0.65 wt.% to about 1.20 wt.%, from about 0.65 wt.% to about 1.15 wt.%, from about 0.65 wt.% to about 1.10 wt.%, from about 0.65 wt.% to about 1.05 wt.%, from about 0.65 wt.% to about 1.00 wt.%, from about 0.65 wt.% to about 0.95 wt.%, from about 0.65 wt.% to about 0.90 wt.%, from about 0.65 wt.% to about 0.85 wt.%, from about 0.65 wt.% to about 0.80 wt.%, from about 0.65 wt.% to about 0.75 wt.%, or from about 0.65 wt.% to about 0.70 wt.%.

[0155] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.70 wt.% to about 10.0 wt.%, from about 0.70 wt.% to about 9.0 wt.%, from about 0.70 wt.% to about 8.0 wt.%, from about 0.70 wt.% to about 7.0 wt.%, from about 0.70 wt.% to about 6.0 wt.%, from about 0.70 wt.% to about 5.0 wt.%, from about 0.70 wt.% to about 4.0 wt.%, from about 0.70 wt.% to about 3.0 wt.%, from about 0.70 wt.% to about 2.0 wt.%, from about 0.70 wt.% to about 1.80 wt.%, from about 0.70 wt.% to about 1.60 wt.%, from about 0.70 wt.% to about 1.50 wt.%, from about 0.70 wt.% to about 1.40 wt.%, from about 0.70 wt.% to about 1.35 wt.%, from about 0.70 wt.% to about 1.30 wt.%, from about 0.70 wt.% to about 1.25 wt.%, from about 0.70 wt.% to about 1.20 wt.%, from about 0.70 wt.% to about 1.15 wt.%, from about 0.70 wt.% to about 1.10 wt.%, from about 0.70 wt.% to about 1.05 wt.%, from about 0.70 wt.% to about 1.00 wt.%, from about 0.70 wt.% to about 0.95 wt.%, from about 0.70 wt.% to about 0.90 wt.%, from about 0.70 wt.% to about 0.85 wt.%, from about 0.70 wt.% to about 0.80 wt.%, or from about 0.70 wt.% to about 0.75 wt.%.

[0156] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.75 wt.% to about 10.0 wt.%, from about 0.75 wt.% to about 9.0 wt.%, from about 0.75 wt.% to about 8.0 wt.%, from about 0.75 wt.% to about 7.0 wt.%, from about 0.75 wt.% to about 6.0 wt.%, from about 0.75 wt.% to about 5.0 wt.%, from about 0.75 wt.% to about 4.0 wt.%, from about 0.75 wt.% to about 3.0 wt.%, from about 0.75 wt.% to about 2.0 wt.%, from about 0.75 wt.% to about 1.80 wt.%, from about 0.75 wt.% to about 1.60 wt.%, from about 0.75 wt.% to about 1.50 wt.%, from about 0.75 wt.% to about 1.40 wt.%, from about 0.75 wt.% to about 1.35 wt.%, from about 0.75 wt.% to about 1.30 wt.%, from about 0.75 wt.% to about 1.25 wt.%, from about 0.75 wt.% to about 1.20 wt.%, from about 0.75 wt.% to about 1.15 wt.%, from about 0.75 wt.% to about 1.10 wt.%, from about 0.75 wt.% to about 1.05 wt.%, from about 0.75 wt.% to about 1.00 wt.%, from about 0.75 wt.% to about 0.95 wt.%, from about 0.75 wt.% to about 0.90 wt.%, from about 0.75 wt.% to about 0.85 wt.%, or from about 0.75 wt.% to about 0.80 wt.%.

[0157] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.80 wt.% to about 10.0 wt.%, from about 0.80 wt.% to about 9.0 wt.%, from about 0.80 wt.% to about 8.0 wt.%, from about 0.80 wt.% to about 7.0 wt.%, from about 0.80 wt.% to about 6.0 wt.%, from about 0.80 wt.% to about 5.0 wt.%, from about 0.80 wt.% to about 4.0 wt.%, from about 0.80 wt.% to about 3.0 wt.%, from about 0.80 wt.% to about 2.0 wt.%, from about 0.80 wt.% to about 1.80 wt.%, from about 0.80 wt.% to about 1.60 wt.%, from about 0.80 wt.% to about 1.50 wt.%, from about 0.80 wt.% to about 1.40 wt.%, from about 0.80 wt.% to about 1.35 wt.%, from about 0.80 wt.% to about 1.30 wt.%, from about 0.80 wt.% to about 1.25 wt.%, from about 0.80 wt.% to about 1.20 wt.%, from about 0.80 wt.% to about 1.15 wt.%, from about 0.80 wt.% to about 1.10 wt.%, from about 0.80 wt.% to about 1.05 wt.%, from about 0.80 wt.% to about 1.00 wt.%, from about 0.80 wt.% to about 0.95 wt.%, from about 0.80 wt.% to about 0.90 wt.%, or from about 0.80 wt.% to about 0.85 wt.%.

[0158] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.85 wt.% to about 10.0 wt.%, from about 0.85 wt.% to about 9.0 wt.%, from about 0.85 wt.% to about 8.0 wt.%, from about 0.85 wt.% to about 7.0 wt.%, from about 0.85 wt.% to about 6.0 wt.%, from about 0.85 wt.% to about 5.0 wt.%, from about 0.85 wt.% to about 4.0 wt.%, from about 0.85 wt.% to about 3.0 wt.%, from about 0.85 wt.% to about 2.0 wt.%, from about 0.85 wt.% to about 1.80 wt.%, from about 0.85 wt.% to about 1.60 wt.%, from about 0.85 wt.% to about 1.50 wt.%, from about 0.85 wt.% to about 1.40 wt.%, from about 0.85 wt.% to about 1.35 wt.%, from about 0.85 wt.% to about 1.30 wt.%, from about 0.85 wt.% to about 1.25 wt.%, from about 0.85 wt.% to about 1.20 wt.%, from about 0.85 wt.% to about 1.15 wt.%, from about 0.85 wt.% to about 1.10 wt.%, from about 0.85 wt.% to about 1.05 wt.%, from about 0.85 wt.% to about 1.00 wt.%, from about 0.85 wt.% to about 0.95 wt.%, or from about 0.85 wt.% to about 0.90 wt.%.

[0159] The concentration of silver ions present in the antimicrobial agent can be from about 0.90 wt.% to about 10.0 wt.%, from about 0.90 wt.% to about 9.0 wt.%, from about 0.90 wt.% to about 8.0 wt.%, from about 0.90 wt.% to about 7.0 wt.%, from about 0.90 wt.% to about 6.0 wt.%, from about 0.90 wt.% to about 5.0 wt.%, from about 0.90 wt.% to about 4.0 wt.%, from about 0.90 wt.% to about 3.0 wt.%, from about 0.90 wt.% to about 2.0 wt.%, from about 0.90 wt.% to about 1.80 wt.%, from about 0.90 wt.% to about 1.60 wt.%, from about 0.90 wt.% to about 1.50 wt.%, from about 0.90 wt.% to about 1.40 wt.%, from about 0.90 wt.% to about 1.35 wt.%, from about 0.90 wt.% to about 1.30 wt.%, from about 0.90 wt.% to about 1.25 wt.%, from about 0.90 wt.% to about 1.20 wt.%, from about 0.90 wt.% to about 1.15 wt.%, from about 0.90 wt.% to about 1.10 wt.%, from about 0.90 wt.% to about 1.05 wt.%, from about 0.90 wt.% to about 1.00 wt.%, or from about 0.90 wt.% to about 0.95 wt.%.

[0160] The concentration of silver ions present in the antimicrobial agent can be from about 0.95 wt.% to about 10.0 wt.%, from about 0.95 wt.% to about 9.0 wt.%, from about 0.95 wt.% to about 8.0 wt.%, from about 0.95 wt.% to about 7.0 wt.%, from about 0.95 wt.% to about 6.0 wt.%, from about 0.95 wt.% to about 5.0 wt.%, from about 0.95 wt.% to about 4.0 wt.%, from about 0.95 wt.% to about 3.0 wt.%, from about 0.95 wt.% to about 2.0 wt.%, from about 0.95 wt.% to about 1.80 wt.%, from about 0.95 wt.% to about 1.60 wt.%, from about 0.95 wt.% to about 1.50 wt.%, from about 0.95 wt.% to about 1.40 wt.%, from about 0.95 wt.% to about 1.35 wt.%, from about 0.95 wt.% to about 1.30 wt.%, from about 0.95 wt.% to about 1.25 wt.%, from about 0.95 wt.% to about 1.20 wt.%, from about 0.95 wt.% to about 1.15 wt.%, from about 0.95 wt.% to about 1.10 wt.%, from about 0.95 wt.% to about 1.05 wt.%, or from about 0.95 wt.% to about 1.00 wt.%.

[0161] The concentration of silver ions in antimicrobial agents can be from about 1.00 wt.% to about 10.0 wt.%, from about 1.00 wt.% to about 9.0 wt.%, from about 1.00 wt.% to about 8.0 wt.%, from about 1.00 wt.% to about 7.0 wt.%, from about 1.00 wt.% to about 6.0 wt.%, from about 1.00 wt.% to about 5.0 wt.%, from about 1.00 wt.% to about 4.0 wt.%, from about 1.00 wt.% to about 3.0 wt.%, from about 1.00 wt.% to about 2.0 wt.%, from about 1.00 wt.% to about 1.80 wt.%, from about 1.00 wt.% to about 1.60 wt.%, from about 1.00 wt.% to about 1.50 wt.%, from about 1.00 wt.% to about 1.40 wt.%, from about 1.00 wt.% to about 1.00 wt.% to about 1.50 wt.% to about 1.00 wt.% to about 1.40 wt.%. wt.% to about 1.35 wt.%, about 1.00 wt.% to about 1.30 wt.%, about 1.00 wt.% to about 1.25 wt.%, about 1.00 wt.% to about 1.20 wt.%, about 1.00 wt.% to about 1.15 wt.%, about 1.00 wt.% to about 1.10 wt.%, or about 1.00 wt.% to about 1.05 wt.%.

[0162] The concentration of silver ions in the antimicrobial agent can be from about 1.05 wt.% to about 10.0 wt.%, from about 1.05 wt.% to about 9.0 wt.%, from about 1.05 wt.% to about 8.0 wt.%, from about 1.05 wt.% to about 7.0 wt.%, from about 1.05 wt.% to about 6.0 wt.%, from about 1.05 wt.% to about 5.0 wt.%, from about 1.05 wt.% to about 4.0 wt.%, from about 1.05 wt.% to about 3.0 wt.%, from about 1.05 wt.% to about 2.0 wt.%, from about 1.05 wt.% to about 1.80 wt.%, from about 1.05 wt.% to about 1.60 wt.%, from about 1.05 wt.% to about 1.50 wt.%, from about 1.05 wt.% to about 1.40 wt.%, from about 1.05 wt.% to about 1.05 wt.% to about 1.05 wt.% to about 1.50 wt.% to about 1.05 wt.% to about 1.40 wt.% to about 1.05 wt.% to about 1.05 wt.% to about 1.60 ... wt.% to about 1.35 wt.%, about 1.05 wt.% to about 1.30 wt.%, about 1.05 wt.% to about 1.25 wt.%, about 1.05 wt.% to about 1.20 wt.%, about 1.05 wt.% to about 1.15 wt.%, or about 1.05 wt.% to about 1.10 wt.%.

[0163] The concentration of silver ions present in the antimicrobial agent can be from about 1.10 wt.% to about 10.0 wt.%, from about 1.10 wt.% to about 9.0 wt.%, from about 1.10 wt.% to about 8.0 wt.%, from about 1.10 wt.% to about 7.0 wt.%, from about 1.10 wt.% to about 6.0 wt.%, from about 1.10 wt.% to about 5.0 wt.%, from about 1.10 wt.% to about 4.0 wt.%, from about 1.10 wt.% to about 3.0 wt.%, from about 1.10 wt.% to about 2.0 wt.%, from about 1.10 wt.% to about 1.80 wt.%, from about 1.10 wt.% to about 1.60 wt.%, from about 1.10 wt.% to about 1.50 wt.%, from about 1.10 wt.% to about 1.40 wt.%, from about 1.10 wt.% to about 1.35 wt.%, from about 1.10 wt.% to about 1.30 wt.%, from about 1.10 wt.% to about 1.25 wt.%, from about 1.10 wt.% to about 1.20 wt.%, or from about 1.10 wt.% to about 1.15 wt.%.

[0164] The concentration of silver ions present in the antimicrobial agent can be from about 1.15 wt.% to about 10.0 wt.%, from about 1.15 wt.% to about 9.0 wt.%, from about 1.15 wt.% to about 8.0 wt.%, from about 1.15 wt.% to about 7.0 wt.%, from about 1.15 wt.% to about 6.0 wt.%, from about 1.15 wt.% to about 5.0 wt.%, from about 1.15 wt.% to about 4.0 wt.%, from about 1.15 wt.% to about 3.0 wt.%, from about 1.15 wt.% to about 2.0 wt.%, from about 1.15 wt.% to about 1.80 wt.%, from about 1.15 wt.% to about 1.60 wt.%, from about 1.15 wt.% to about 1.50 wt.%, from about 1.15 wt.% to about 1.40 wt.%, from about 1.15 wt.% to about 1.35 wt.%, from about 1.15 wt.% to about 1.30 wt.%, from about 1.15 wt.% to about 1.25 wt.%, or from about 1.15 wt.% to about 1.20 wt.%.

[0165] The concentration at which silver ions are present in the antimicrobial agent can be from about 1.20 wt.% to about 10.0 wt.%, from about 1.20 wt.% to about 9.0 wt.%, from about 1.20 wt.% to about 8.0 wt.%, from about 1.20 wt.% to about 7.0 wt.%, from about 1.20 wt.% to about 6.0 wt.%, from about 1.20 wt.% to about 5.0 wt.%, from about 1.20 wt.% to about 4.0 wt.%, from about 1.20 wt.% to about 3.0 wt.%, from about 1.20 wt.% to about 2.0 wt.%, from about 1.20 wt.% to about 1.80 wt.%, from about 1.20 wt.% to about 1.60 wt.%, from about 1.20 wt.% to about 1.50 wt.%, from about 1.20 wt.% to about 1.40 wt.%, from about 1.20 wt.% to about 1.35 wt.%, from about 1.20 wt.% to about 1.30 wt.%, or from about 1.20 wt.% to about 1.25 wt.%.

[0166] The concentration at which silver ions are present in the antimicrobial agent can be from about 1.25 wt.% to about 10.0 wt.%, from about 1.25 wt.% to about 9.0 wt.%, from about 1.25 wt.% to about 8.0 wt.%, from about 1.25 wt.% to about 7.0 wt.%, from about 1.25 wt.% to about 6.0 wt.%, from about 1.25 wt.% to about 5.0 wt.%, from about 1.25 wt.% to about 4.0 wt.%, from about 1.25 wt.% to about 3.0 wt.%, from about 1.25 wt.% to about 2.0 wt.%, from about 1.25 wt.% to about 1.80 wt.%, from about 1.25 wt.% to about 1.60 wt.%, from about 1.25 wt.% to about 1.50 wt.%, from about 1.25 wt.% to about 1.40 wt.%, from about 1.25 wt.% to about 1.35 wt.%, or from about 1.25 wt.% to about 1.30 wt.%.

[0167] The concentration of silver ions present in the antimicrobial agent can be from about 1.30 wt.% to about 10.0 wt.%, from about 1.30 wt.% to about 9.0 wt.%, from about 1.30 wt.% to about 8.0 wt.%, from about 1.30 wt.% to about 7.0 wt.%, from about 1.30 wt.% to about 6.0 wt.%, from about 1.30 wt.% to about 5.0 wt.%, from about 1.30 wt.% to about 4.0 wt.%, from about 1.30 wt.% to about 3.0 wt.%, from about 1.30 wt.% to about 2.0 wt.%, from about 1.30 wt.% to about 1.80 wt.%, from about 1.30 wt.% to about 1.60 wt.%, from about 1.30 wt.% to about 1.50 wt.%, from about 1.30 wt.% to about 1.40 wt.%, or from about 1.30 wt.% to about 1.35 wt.%.

[0168] The concentration of silver ions present in the antimicrobial agent can be from about 1.35 wt.% to about 10.0 wt.%, from about 1.35 wt.% to about 9.0 wt.%, from about 1.35 wt.% to about 8.0 wt.%, from about 1.35 wt.% to about 7.0 wt.%, from about 1.35 wt.% to about 6.0 wt.%, from about 1.35 wt.% to about 5.0 wt.%, from about 1.35 wt.% to about 4.0 wt.%, from about 1.35 wt.% to about 3.0 wt.%, from about 1.35 wt.% to about 2.0 wt.%, from about 1.35 wt.% to about 1.80 wt.%, from about 1.35 wt.% to about 1.60 wt.%, from about 1.35 wt.% to about 1.50 wt.%, or from about 1.35 wt.% to about 1.40 wt.%.

[0169] The concentration of silver ions present in the antimicrobial agent can be from about 1.40 wt.% to about 10.0 wt.%, from about 1.40 wt.% to about 9.0 wt.%, from about 1.40 wt.% to about 8.0 wt.%, from about 1.40 wt.% to about 7.0 wt.%, from about 1.40 wt.% to about 6.0 wt.%, from about 1.40 wt.% to about 5.0 wt.%, from about 1.40 wt.% to about 4.0 wt.%, from about 1.40 wt.% to about 3.0 wt.%, from about 1.40 wt.% to about 2.0 wt.%, from about 1.40 wt.% to about 1.80 wt.%, from about 1.40 wt.% to about 1.60 wt.%, or from about 1.40 wt.% to about 1.50 wt.%.

[0170] The concentration of silver ions present in the antimicrobial agent can be from about 1.50 wt.% to about 10.0 wt.%, from about 1.50 wt.% to about 9.0 wt.%, from about 1.50 wt.% to about 8.0 wt.%, from about 1.50 wt.% to about 7.0 wt.%, from about 1.50 wt.% to about 6.0 wt.%, from about 1.50 wt.% to about 5.0 wt.%, from about 1.50 wt.% to about 4.0 wt.%, from about 1.50 wt.% to about 3.0 wt.%, from about 1.50 wt.% to about 2.0 wt.%, from about 1.50 wt.% to about 1.80 wt.%, or from about 1.50 wt.% to about 1.60 wt.%.

[0171] The concentration of silver ions present in the antimicrobial agent can be from about 1.60 wt.% to about 10.0 wt.%, from about 1.60 wt.% to about 9.0 wt.%, from about 1.60 wt.% to about 8.0 wt.%, from about 1.60 wt.% to about 7.0 wt.%, from about 1.60 wt.% to about 6.0 wt.%, from about 1.60 wt.% to about 5.0 wt.%, from about 1.60 wt.% to about 4.0 wt.%, from about 1.60 wt.% to about 3.0 wt.%, from about 1.60 wt.% to about 2.0 wt.%, or from about 1.60 wt.% to about 1.80 wt.%.

[0172] The concentration of silver ions present in the antimicrobial agent can be from about 1.80 wt.% to about 10.0 wt.%, from about 1.80 wt.% to about 9.0 wt.%, from about 1.80 wt.% to about 8.0 wt.%, from about 1.80 wt.% to about 7.0 wt.%, from about 1.80 wt.% to about 6.0 wt.%, from about 1.80 wt.% to about 5.0 wt.%, from about 1.80 wt.% to about 4.0 wt.%, from about 1.80 wt.% to about 3.0 wt.%, or from about 1.80 wt.% to about 2.0 wt.%.

[0173] The concentration of silver ions present in the antimicrobial agent can be from about 2.0 wt.% to about 10.0 wt.%, from about 2.0 wt.% to about 9.0 wt.%, from about 2.0 wt.% to about 8.0 wt.%, from about 2.0 wt.% to about 7.0 wt.%, from about 2.0 wt.% to about 6.0 wt.%, from about 2.0 wt.% to about 5.0 wt.%, from about 2.0 wt.% to about 4.0 wt.%, or from about 2.0 wt.% to about 3.0 wt.%.

[0174] The concentration of silver ions present in the antimicrobial agent can be from about 3.0 wt.% to about 10.0 wt.%, from about 3.0 wt.% to about 9.0 wt.%, from about 3.0 wt.% to about 8.0 wt.%, from about 3.0 wt.% to about 7.0 wt.%, from about 3.0 wt.% to about 6.0 wt.%, from about 3.0 wt.% to about 5.0 wt.%, or from about 3.0 wt.% to about 4.0 wt.%.

[0175] The concentration of silver ions present in the antimicrobial agent can be from about 4.0 wt.% to about 10.0 wt.%, from about 4.0 wt.% to about 9.0 wt.%, from about 4.0 wt.% to about 8.0 wt.%, from about 4.0 wt.% to about 7.0 wt.%, from about 4.0 wt.% to about 6.0 wt.%, or from about 4.0 wt.% to about 5.0 wt.%.

[0176] The concentration of silver ions present in the antimicrobial agent can be from about 5.0 wt.% to about 10.0 wt.%, from about 5.0 wt.% to about 9.0 wt.%, from about 5.0 wt.% to about 8.0 wt.%, from about 5.0 wt.% to about 7.0 wt.%, or from about 5.0 wt.% to about 6.0 wt.%.

[0177] The concentration of silver ions present in the antimicrobial agent can be from about 6.0 wt.% to about 10.0 wt.%, from about 6.0 wt.% to about 9.0 wt.%, from about 6.0 wt.% to about 8.0 wt.%, or from about 6.0 wt.% to about 7.0 wt.%.

[0178] The concentration of silver ions present in the antimicrobial agent can be from about 7.0 wt.% to about 10.0 wt.%, from about 7.0 wt.% to about 9.0 wt.%, or from about 7.0 wt.% to about 8.0 wt.%.

[0179] The concentration of silver ions present in the antimicrobial agent can be from about 8.0 wt.% to about 10.0 wt.%, or from about 8.0 wt.% to about 9.0 wt.%.

[0180] The concentration of silver ions present in the antimicrobial agent can be from about 9.0 wt.% to about 10.0 wt.%.

[0181] The concentration at which silver ions are present in the antimicrobial agent can be from about 0.10 wt.% to about 10 wt.%, from about 0.15 wt.% to about 9.0 wt.%, from about 0.20 wt.% to about 8.0 wt.%, from about 0.25 wt.% to about 7.0 wt.%, from about 0.30 wt.% to about 6.0 wt.%, from about 0.35 wt.% to about 5.0 wt.%, from about 0.40 wt.% to about 4.0 wt.%, from about 0.45 wt.% to about 3.0 wt.%, from about 0.50 wt.% to about 2.0 wt.%, from about 0.50 wt.% to about 1.8 wt.%, from about 0.60 wt.% to about 1.6 wt.%, from about 0.70 wt.% to about 1.5 wt.%, from about 0.80 wt.% to about 1.4 wt.%, from about 0.90 wt.% to about 1.35 wt.%, from about 0.95 wt.% to about 1.30 wt.%, from about 1.00 wt.% to about 1.25 wt.%, from about 1.05 wt.% to about 1.25 wt.%, from about 1.10 wt.% to about 1.25 wt.%, from about 1.15 wt.% to about 1.25 wt.%, or about 1.20 wt.%.

[0182] The concentration at which silver ions are present in the antimicrobial agent can be about 0.10 wt.%, about 0.15 wt.%, about 0.20 wt.%, about 0.25 wt.%, about 0.30 wt.%, about 0.35 wt.%, about 0.40 wt.%, about 0.45 wt.%, about 0.50 wt.%, about 0.55 wt.%, about 0.60 wt.%, about 0.65 wt.%, about 0.70 wt.%, about 0.75 wt.%, about 0.80 wt.%, about 0.85 wt.%, about 0.90 wt.%, about 0.95 wt.%, about 1.00 wt.%, about 1.05 wt.%, about 1.10 wt.%, about 1.15 wt.%, about 1.20 wt.%, about 1.25 wt.%, about 1.30 wt.%, about 1.35 wt.%, about 1.40 wt.%, about 1.45 wt.%, about 1.50 wt.%, about 1.60 wt.%, about 1.70 wt.%, about 1.80 wt.%, about 1.90 wt.%, about 2.00 wt.%, about 2.10 wt.%, about 2.20 wt.%, about 2.30 wt.%, about 2.40 wt.%, about 2.50 wt.%, about 2.75 wt.%, about 3.00 wt.%, about 3.25 wt.%, about 3.50 wt.%, about 3.75 wt.%, about 4.00 wt.%, about 4.25 wt.%, about 4.50 wt.%, about 4.75 wt.%, about 5.00 wt.%, about 5.25 wt.%, about 5.50 wt.%, about 5.75 wt.%, about 6.00 wt.%, about 6.25 wt.%, about 6.50 wt.%, about 6.75 wt.%, about 7.00 wt.%, about 7.50 wt.%, about 8.00 wt.%, about 8.50 wt.%, about 9.00 wt.%, about 9.50 wt.%, or about 10.0 wt.%.

[0183] The concentration at which silver ions are present in the antimicrobial agent can be at least about 0.10 wt.%, at least about 0.15 wt.%, at least about 0.20 wt.%, at least about 0.25 wt.%, at least about 0.30 wt.%, at least about 0.35 wt.%, at least about 0.40 wt.%, at least about 0.45 wt.%, at least about 0.50 wt.%, at least about 0.55 wt.%, at least about 0.60 wt.%, at least about 0.65 wt.%, at least about 0.70 wt.%, at least about 0.75 wt.%, at least about 0.80 wt.%, at least about 0.85 wt.%, at least about 0.90 wt.%, at least about 0.95 wt.%, at least about 1.00 wt.%, at least about 1.05 wt.%, at least about 1.10 wt.%, at least about 1.15 wt.%, at least about 1.20 wt.%, at least about 1.25 wt.%, at least about 1.30 wt.%, at least about 1.35 wt.%, at least about 1.40 wt.%, at least about 1.45 wt.%, at least about 1.50 wt.%, at least about 1.60 wt.%, at least about 1.70 wt.%, at least about 1.80 wt.%, at least about 1.90 wt.%, at least about 2.00 wt.%, at least about 2.10 wt.%, at least about 2.20 wt.%, at least about 2.30 wt.%, at least about 2.40 wt.%, at least about 2.50 wt.%, at least about 2.75 wt.%, at least about 3.00 wt.%, at least about 3.25 wt.%, at least about 3.50 wt.%, at least about 3.75 wt.%, at least about 4.00 wt.%, at least about 4.25 wt.%, at least about 4.50 wt.%, at least about 4.75 wt.%, at least about 5.00 wt.%, at least about 5.25 wt.%, at least about 5.50 wt.%, at least about 5.75 wt.%, at least about 6.00 wt.%, at least about 6.25 wt.%, at least about 6.50 wt.%, at least about 6.75 wt.%, at least about 7.00 wt.%, at least about 7.50 wt.%, at least about 8.00 wt.%, at least about 8.50 wt.%, at least about 9.00 wt.%, at least about 9.50 wt.%, or at least about 10.0 wt.%.

[0184] The silver ion can be present in the antimicrobial agent at a concentration of no more than about 0.10 wt.%, no more than about 0.15 wt.%, no more than about 0.20 wt.%, no more than about 0.25 wt.%, no more than about 0.30 wt.%, no more than about 0.35 wt.%, no more than about 0.40 wt.%, no more than about 0.45 wt.%, no more than about 0.50 wt.%, no more than about 0.55 wt.%, no more than about 0.60 wt.%, no more than about 0.65 wt.%, no more than about 0.70 wt.%, no more than about 0.75 wt.%, no more than about 0.80 wt.%, no more than about 0.85 wt.%, no more than about 0.90 wt.%, no more than about 0.95 wt.%, no more than about 1.00 wt.%, no more than about 1.05 wt.%, no more than about 1.10 wt.%, no more than about 1.15 wt.%, no more than about 1.20 wt.%, no more than about 1.25 wt.%, no more than about 1.30 wt.%, no more than about 1.35 wt.%, no more than about 1.40 wt.%, no more than about 1.45 wt.%, no more than about 1.50 wt.%, no more than about 1.60 wt.%, no more than about 1.70 wt.%, no more than about 1.80 wt.%, no more than about 1.90 wt.%, no more than about 2.00 wt.%, no more than about 2.10 wt.%, no more than about 2.20 wt.%, no more than about 2.30 wt.%, no more than about 2.40 wt.%, no more than about 2.50 wt.%, no more than about 2.75 wt.%, no more than about 3.00 wt.%, no more than about 3.25 wt.%, no more than about 3.50 wt.%, no more than about 3.75 wt.%, no more than about 4.00 wt.%, no more than about 4.25 wt.%, no more than about 4.50 wt.%, no more than about 4.75 wt.%, no more than about 5.00 wt.%, no more than about 5.25 wt.%, no more than about 5.50 wt.%, no more than about 5.75 wt.%, no more than about 6.00 wt.%, no more than about 6.25 wt.%, no more than about 6.50 wt.%, no more than about 6.75 wt.%, no more than about 7.00 wt.%, no more than about 7.50 wt.%, no more than about 8.00 wt.%, no more than about 8.50 wt.%, no more than about 9.00 wt.%, no more than about 9.50 wt.%, or no more than about 10.0 wt.%.

[0185] Thus, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin proximate the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the silver ions are present in the antimicrobial agent at a concentration of 0.10 wt.% to 10.0 wt.%.

[0186] Thus, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin proximate the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the silver ions are present in the antimicrobial agent at a concentration of 0.50 wt.% to 1.80 wt.%.

[0187] Thus, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin proximate the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the silver ions are present in the antimicrobial agent at a concentration of 1.20 wt.%.

[0188] The wound contact layer can also comprise an anti-biofilm agent. Advantageously, the efficacy of an antimicrobial agent can be reduced by a biofilm matrix produced by bacteria at the wound site, and thus, a strategy to disrupt the biofilm and expose the microorganisms therein can help to increase the level of activity of the antimicrobial agent, thereby reducing the concentration of the antimicrobial agent needed to make an effective composition.

[0189] Accordingly, in some embodiments, a negative pressure wound dressing can be provided that includes a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer includes an aperture for connection to a source of negative pressure, wherein the absorbent structure includes a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin proximate the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions, wherein the wound contact layer further comprises an anti-biofilm agent.

[0190] The anti-biofilm agent can comprise a chelating agent.

[0191] The chelating agent can include ethylenediaminetetraacetic acid (EDTA) or a salt thereof. The salt of EDTA can be any di-, tri- or tetra-alkali salt of EDTA, such as a disodium salt, a trisodium salt, a tetrasodium salt, or a calcium disodium salt, or a combination thereof. Surprisingly, it has been found that chelating agents, in particular EDTA, are effective in disrupting biofilms by chelating metal ions, calcium and magnesium, which maintain the integrity of the biofilm matrix. The presence of the chelating agent, such as EDTA, enhances the effectiveness of the antimicrobial agent, such that the concentration of the antimicrobial agent (silver ions) can be reduced, but still achieve the desired antimicrobial effect. By increasing the effectiveness of the antimicrobial agent, its concentration in the composition can be reduced, thereby reducing the potential for adverse reactions.

[0192] The chelating agent can be present in an amount of about 0.5 wt.% to about 10.0 wt.%, about 0.6 wt.% to about 9.0 wt.%, about 0.7 wt.% to about 8.0 wt.%, about 0.8 wt.% to about 7.0 wt.%, about 0.9 wt.% to about 6.0 wt.%, about 1.0 wt.% to about 5.0 wt.%, about 1.0 wt.% to about 5.0 wt.%, about 1.0 wt.% to about 4.0 wt.%, about 1.0 wt.% to about 3.0 wt.%, about 1.5 wt.% to about 2.5 wt.%, or about 2.0 wt.%.

[0193] The chelating agent can be present in a concentration of about 0.10 wt.%, about 0.15 wt.%, about 0.20 wt.%, about 0.25 wt.%, about 0.30 wt.%, about 0.35 wt.%, about 0.40 wt.%, about 0.45 wt.%, about 0.50 wt.%, about 0.55 wt.%, about 0.60 wt.%, about 0.65 wt.%, about 0.70 wt.%, about 0.75 wt.%, about 0.80 wt.%, about 0.85 wt.%, about 0.90 wt.%, about 0.95 wt.%, about 1.00 wt.%, about 1.05 wt.%, about 1.10 wt.%, about 1.15 wt.%, about 1.20 wt.%, about 1.25 wt.%, about 1.30 wt.%, about 1.35 wt.%, about 1.40 wt.%, about 1.45 wt.%, about 1.50 wt.%, about 1.60 wt.%, about 1.70 wt.%, about 1.80 wt.%, about 1.90 wt.%, about 2.00 wt.%, about 2.10 wt.%, about 2.20 wt.%, about 2.30 wt.%, about 2.40 wt.%, about 2.50 wt.%, about 2.75 wt.%, about 3.00 wt.%, about 3.25 wt.%, about 3.50 wt.%, about 3.75 wt.%, about 4.00 wt.%, about 4.25 wt.%, about 4.50 wt.%, about 4.75 wt.%, about 5.00 wt.%, about 5.25 wt.%, about 5.50 wt.%, about 5.75 wt.%, about 6.00 wt.%, about 6.25 wt.%, about 6.50 wt.%, about 6.75 wt.%, about 7.00 wt.%, about 7.50 wt.%, about 8.00 wt.%, about 8.50 wt.%, about 9.00 wt.%, about 9.50 wt.%, or about 10.0 wt.%.

[0194] The chelating agent can be present in a concentration of at least about 0.10 wt.%, at least about 0.15 wt.%, at least about 0.20 wt.%, at least about 0.25 wt.%, at least about 0.30 wt.%, at least about 0.35 wt.%, at least about 0.40 wt.%, at least about 0.45 wt.%, at least about 0.50 wt.%, at least about 0.55 wt.%, at least about 0.60 wt.%, at least about 0.65 wt.%, at least about 0.70 wt.%, at least about 0.75 wt.%, at least about 0.80 wt.%, at least about 0.85 wt.%, at least about 0.90 wt.%, at least about 0.95 wt.%, at least about 1.00 wt.%, at least about 1.05 wt.%, at least about 1.10 wt.%, at least about 1.15 wt.%, at least about 1.20 wt.%, at least about 1.25 wt.%, at least about 1.30 wt.%, at least about 1.35 wt.%, at least about 1.40 wt.%, at least about 1.45 wt.%, at least about 1.50 wt.%, at least about 1.60 wt.%, at least about 1.70 wt.%, at least about 1.80 wt.%, at least about 1.90 wt.%, at least about 2.00 wt.%, at least about 2.10 wt.%, at least about 2.20 wt.%, at least about 2.30 wt.%, at least about 2.40 wt.%, at least about 2.50 wt.%, at least about 2.75 wt.%, at least about 3.00 wt.%, at least about 3.25 wt.%, at least about 3.50 wt.%, at least about 3.75 wt.%, at least about 4.00 wt.%, at least about 4.25 wt.%, at least about 4.50 wt.%, at least about 4.75 wt.%, at least about 5.00 wt.%, at least about 5.25 wt.%, at least about 5.50 wt.%, at least about 5.75 wt.%, at least about 6.00 wt.%, at least about 6.25 wt.%, at least about 6.50 wt.%, at least about 6.75 wt.%, at least about 7.00 wt.%, at least about 7.50 wt.%, at least about 8.00 wt.%, at least about 8.50 wt.%, at least about 9.00 wt.%, at least about 9.50 wt.%, or at least about 10.0 wt.%.

[0195] The chelator can be present in a concentration of not more than about 0.10 wt.%, not more than about 0.15 wt.%, not more than about 0.20 wt.%, not more than about 0.25 wt.%, not more than about 0.30 wt.%, not more than about 0.35 wt.%, not more than about 0.40 wt.%, not more than about 0.45 wt.%, not more than about 0.50 wt.%, not more than about 0.55 wt.%, not more than about 0.60 wt.%, not more than about 0.65 wt.%, not more than about 0.70 wt.%, not more than about 0.75 wt.%, not more than about 0.80 wt.%, not more than about 0.85 wt.%, not more than about 0.90 wt.%, not more than about 0.95 wt.%, not more than about 1.00 wt.%, not more than about 1.05 wt.%, not more than about 1.10 wt.%, not more than about 1.15 wt.%, not more than about 1.20 wt.%, not more than about 1.25 wt.%, not more than about 1.30 wt.%, not more than about 1.35 wt.%, not more than about 1.40 wt.%, not more than about 1.45 wt.%, not more than about 1.50 wt.%, not more than about 1.60 wt.%, not more than about 1.70 wt.%, not more than about 1.80 wt.%, not more than about 1.90 wt.%, not more than about 2.00 wt.%, not more than about 2.10 wt.%, not more than about 2.20 wt.%, not more than about 2.30 wt.%, not more than about 2.40 wt.%, not more than about 2.50 wt.%, not more than about 2.75 wt.%, not more than about 3.00 wt.%, not more than about 3.25 wt.%, not more than about 3.50 wt.%, not more than about 3.75 wt.%, not more than about 4.00 wt.%, not more than about 4.25 wt.%, not more than about 4.50 wt.%, not more than about 4.75 wt.%, not more than about 5.00 wt.%, not more than about 5.25 wt.%, not more than about 5.50 wt.%, not more than about 5.75 wt.%, not more than about 6.00 wt.%, not more than about 6.25 wt.%, not more than about 6.50 wt.%, not more than about 6.75 wt.%, not more than about 7.00 wt.%, not more than about 7.50 wt.%, not more than about 8.00 wt.%, not more than about 8.50 wt.%, not more than about 9.00 wt.%, not more than about 9.50 wt.%, or not more than about 10.0 wt.%.

[0196] In embodiments comprising EDTA as a chelating agent, the EDTA can be present as a di-, tri- or tetra- basic salt of EDTA. It has been found that these salts, alone or in the presence of an antimicrobial agent, are effective for eradicating microorganisms in free floating or planktonic state and in biofilm state. For example, it has been found that a volume of EDTA at a concentration of 0.1-40 wt.% can effectively kill a variety of microorganisms in planktonic and biofilm state. Microorganisms effectively killed by EDTA include Pseudomonas aeruginosa, Serratia marcescens, Vancomycin Resistant Enterococci (VRE) and Methicillin Resistant Staphylococcus aureus (MRSA).

[0197] The anti-biofilm agent can comprise a quaternary cationic surfactant.

[0198] The quaternary cationic surfactant can be a quaternary ammonium salt, for example an alkyl or aryl quaternary ammonium salt.

[0199] The quaternary cationic surfactant can be a quaternary ammonium salt of the following structure:

[0200]

[0201] where R 1 to R 4 each independently of one another represents -CH3, a straight-chain or branched saturated alkyl residue having 2 to 18 carbon atoms, a straight-chain or branched mono- or poly-unsaturated alkenyl residue having 2 to 18 carbon atoms, a substituted or unsubstituted aryl group such as benzyl or ethylbenzyl, or an organic radical, an alkyl or alkenyl residue substituted by -NH2, -OH or -COOH, or represents -COOH or -COOR, R being a straight-chain or branched saturated or unsaturated hydrocarbon radical having 1 to 18 carbon atoms, wherein X is an anion, for example a halide such as chloride, a sulfate, a nitrate, a carbonate or other similar.

[0202] The quaternary ammonium salt can be a single long-chain quaternary ammonium salt, for example alkyl dimethyl benzyl ammonium chloride and alkyl dimethyl ethyl benzyl ammonium chloride, where R 1 to R 4 Only one of R1to R4is a long-chain alkyl, i.e. comprising a chain of C6or more, for example C8to C18. Preferably, the quaternary ammonium salt is alkyl dimethyl benzyl ammonium chloride, where the alkyl group has the formula C n H 2n+1 , n is 8, 10, 12, 14, 16 or 18, for example benzyl ammonium chloride.

[0203] The quaternary ammonium salt can be a double long-chain quaternary ammonium salt, for example dialkyl dimethyl ammonium chloride, where the dialkyl is two independent alkyl groups having a chain length of C6or more, for example C6to C18.

[0204] The double long chain quaternary ammonium salt can be one or more selected from the group consisting of didecyldimethylammonium chloride, dioctyldimethylammonium chloride, octyldidecyldimethylammonium chloride, didodecyldimethylammonium chloride, ditetradecyldimethylammonium chloride, and dihexadecyldimethylammonium chloride, didecyldimethylammonium chloride, dioctyldimethylammonium chloride, octyldidecyldimethylammonium chloride, and didodecyldimethylammonium chloride, didecyldimethylammonium chloride, dioctyldimethylammonium chloride, and octyldidecyldimethylammonium chloride. Surprisingly, it has been found that an anti-biofilm agent comprising a quaternary cationic surfactant such as benzyl ammonium chloride enhances the effect of the foregoing EDTA to disrupt a biofilm, and thus the effect of the antimicrobial agent.

[0205] The quaternary cationic surfactant can be present in an amount of about 0.025 wt.% to about 4.0 wt.%, about 0.050 wt.% to about 3.5 wt.%, about 0.10 wt.% to about 3.0 wt.%, about 0.15 wt.% to about 2.5 wt.%, about 0.20 wt.% to about 2.25 wt.%, about 0.25 wt.% to about 2.0 wt.%, about 0.30 wt.% to about 1.75 wt.%, about 0.35 wt.% to about 1.50 wt.%, about 0.40 wt.% to about 1.25 wt.%, about 0.45 wt.% to about 1.0 wt.%, about 0.50 wt.% to about 0.95 wt.%, about 0.55 wt.% to about 0.90 wt.%, about 0.60 wt.% to about 0.85 wt.%, about 0.70 wt.% to about 0.80 wt.%, or about 0.75 wt.%.

[0206] The quaternary cationic surfactant can be present in an amount of about 0.025 wt.%, about 0.05 wt.%, about 0.10 wt.%, about 0.15 wt.%, about 0.20 wt.%, about 0.25 wt.%, about 0.30 wt.%, about 0.35 wt.%, about 0.40 wt.%, about 0.45 wt.%, about 0.50 wt.%, about 0.55 wt.%, about 0.60 wt.%, about 0.65 wt.%, about 0.70 wt.%, about 0.75 wt.%, about 0.80 wt.%, about 0.85 wt.%, about 0.90 wt.%, about 0.95 wt.%, about 1.00 wt.%, about 1.05 wt.%, about 1.10 wt.%, about 1.15 wt.%, about 1.20 wt.%, about 1.25 wt.%, about 1.30 wt.%, about 1.35 wt.%, about 1.40 wt.%, about 1.45 wt.%, about 1.50 wt.%, about 1.60 wt.%, about 1.70 wt.%, about 1.80 wt.%, about 1.90 wt.%, about 2.00 wt.%, about 2.10 wt.%, about 2.20 wt.%, about 2.30 wt.%, about 2.40 wt.%, about 2.50 wt.%, about 2.75 wt.%, about 3.00 wt.%, about 3.25 wt.%, about 3.50 wt.%, about 3.75 wt.%, or about 4.00 wt.%.

[0207] The quaternary cationic surfactant can be present in an amount of at least about 0.025 wt.%, at least about 0.05 wt.%, at least about 0.10 wt.%, at least about 0.15 wt.%, at least about 0.20 wt.%, at least about 0.25 wt.%, at least about 0.30 wt.%, at least about 0.35 wt.%, at least about 0.40 wt.%, at least about 0.45 wt.%, at least about 0.50 wt.%, at least about 0.55 wt.%, at least about 0.60 wt.%, at least about 0.65 wt.%, at least about 0.70 wt.%, at least about 0.75 wt.%, at least about 0.80 wt.%, at least about 0.85 wt.%, at least about 0.90 wt.%, at least about 0.95 wt.%, at least about 1.00 wt.%, at least about 1.05 wt.%, at least about 1.10 wt.%, at least about 1.15 wt.%, at least about 1.20 wt.%, at least about 1.25 wt.%, at least about 1.30 wt.%, at least about 1.35 wt.%, at least about 1.40 wt.%, at least about 1.45 wt.%, at least about 1.50 wt.%, at least about 1.60 wt.%, at least about 1.70 wt.%, at least about 1.80 wt.%, at least about 1.90 wt.%, at least about 2.00 wt.%, at least about 2.10 wt.%, at least about 2.20 wt.%, at least about 2.30 wt.%, at least about 2.40 wt.%, at least about 2.50 wt.%, at least about 2.75 wt.%, at least about 3.00 wt.%, at least about 3.25 wt.%, at least about 3.50 wt.%, at least about 3.75 wt.%, or at least about 4.00 wt.%.

[0208] The quaternary cationic surfactant can be present in an amount of no more than about 0.025 wt.%, no more than about 0.05 wt.%, no more than about 0.10 wt.%, no more than about 0.15 wt.%, no more than about 0.20 wt.%, no more than about 0.25 wt.%, no more than about 0.30 wt.%, no more than about 0.35 wt.%, no more than about 0.40 wt.%, no more than about 0.45 wt.%, no more than about 0.50 wt.%, no more than about 0.55 wt.%, no more than about 0.60 wt.%, no more than about 0.65 wt.%, no more than about 0.70 wt.%, no more than about 0.75 wt.%, no more than about 0.80 wt.%, no more than about 0.85 wt.%, no more than about 0.90 wt.%, no more than about 0.95 wt.%, no more than about 1.00 wt.%, no more than about 1.05 wt.%, no more than about 1.10 wt.%, no more than about 1.15 wt.%, no more than about 1.20 wt.%, no more than about 1.25 wt.%, no more than about 1.30 wt.%, no more than about 1.35 wt.%, no more than about 1.40 wt.%, no more than about 1.45 wt.%, no more than about 1.50 wt.%, no more than about 1.60 wt.%, no more than about 1.70 wt.%, no more than about 1.80 wt.%, no more than about 1.90 wt.%, no more than about 2.00 wt.%, no more than about 2.10 wt.%, no more than about 2.20 wt.%, no more than about 2.30 wt.%, no more than about 2.40 wt.%, no more than about 2.50 wt.%, no more than about 2.75 wt.%, no more than about 3.00 wt.%, no more than about 3.25 wt.%, no more than about 3.50 wt.%, no more than about 3.75 wt.%, or no more than about 4.00 wt.%.

[0209] The antimicrobial agent can include a buffer.

[0210] The buffer can be selected from the group including citric acid, disodium hydrogen phosphate, sodium citrate, acetic acid and sodium acetate, or combinations thereof.

[0211] The buffer can be present in an amount of about 1 wt.% to about 20 wt.%, about 4 wt.% to about 6 wt.%, or about 5 wt.% of the antimicrobial agent, so as to provide an isotonic composition.

[0212] The polysiloxane / silicone / silicone contained in the wound contact layer may be less than about 95 wt.%, less than about 94 wt.%, less than about 93 wt.%, less than about 92 wt.%, less than about 91 wt.%, less than about 90 wt.%, less than about 88 wt.%, less than about 86 wt.%, less than about 84 wt.%, less than about 82 wt.%, less than about 80 wt.%, less than about 75 wt.%, less than about 70 wt.%, less than about 65 wt.%, less than about 60 wt.%, less than about 50 wt.%, less than about 40 wt.%, less than about 30 wt.%, less than about 20 wt.%, less than about 10 wt.%, less than about 8 wt.%, less than about 6 wt.%, less than about 4 wt.%, less than about 2 wt.%, or about 0 wt.%.

[0213] The polysiloxane contained in the wound contact layer may not exceed about 1 wt.%, not exceed about 0.8 wt.%, not exceed about 0.6 wt.%, not exceed about 0.4 wt.%, not exceed about 0.2 wt.%, or be about 0 wt.%. Advantageously, in embodiments comprising a wound contact layer containing not more than about 1 wt.%, preferably about 0 wt.%, of polysiloxane, the antimicrobial agent efficacy is stronger. This is because the polysiloxane acts as a barrier between the antimicrobial agent and the wound site. Therefore, in embodiments of the invention having a wound contact layer containing not more than about 1 wt.%, preferably about 0 wt.%, of polysiloxane, the barrier between the antimicrobial agent and the wound site is eliminated, or at least significantly reduced.

[0214] The thickness of the wound contact layer can be from about 1 mm to about 5 mm, from about 1.5 mm to about 4.5 mm, from about 2.0 mm to about 4.0 mm, from about 2.5 mm to about 3.5 mm, or about 3.0 mm.

[0215] The thickness of the wound contact layer can be approximately 1 mm, approximately 1.5 mm, approximately 2.0 mm, approximately 2.5 mm, approximately 3.0 mm, approximately 3.5 mm, approximately 4.0 mm, approximately 4.5 mm, or approximately 5.0 mm.

[0216] The thickness of the wound contact layer can be at least about 1 mm, at least about 1.5 mm, at least about 2.0 mm, at least about 2.5 mm, at least about 3.0 mm, at least about 3.5 mm, at least about 4.0 mm, at least about 4.5 mm, or at least about 5.0 mm.

[0217] The wound contact layer can have a thickness of no more than about 1 mm, no more than about 1.5 mm, no more than about 2.0 mm, no more than about 2.5 mm, no more than about 3.0 mm, no more than about 3.5 mm, no more than about 4.0 mm, no more than about 4.5 mm, or no more than about 5.0 mm.

[0218] The adhesive skin contact layer can be a perforated mesh comprising a plurality of perforations, each perforation having a diameter in the range of 1.25 mm to 5.00 mm. Advantageously, this means that the perforations have a sufficient diameter to provide breathability to the wound dressing in the event that the diameter of some of the perforations decreases after the perforations are formed. In this way, the adhesive skin contact layer maintains an environment that is optimal for wound healing.

[0219] The perforations comprise through holes in the adhesive skin contact layer that enable fluid to flow through the layer. Thus, in use, if the adhesive skin contact layer is arranged to cover and contact a wound, the adhesive skin contact layer prevents or at least substantially prevents tissue ingrowth into other materials of the wound dressing.

[0220] Beneficially, the adhesive skin contact layer helps to maintain the integrity of the wound dressing whilst also forming an airtight or substantially airtight seal around the absorbent structure to maintain the negative pressure at the wound site.

[0221] The absorbent structure can be arranged between the backing layer and the adhesive skin contact layer. Advantageously, this means that wound exudate is absorbed by the absorbent structure before it contacts the backing layer.

[0222] The adhesive skin contact layer can have a weight of about 40 gsm, about 50 gsm, about 60 gsm, about 70 gsm, about 80 gsm, about 100 gsm, about 110 gsm, about 120 gsm, about 130 gsm, about 140 gsm, about 150 gsm, about 155 gsm, about 160 gsm, about 165 gsm, about 170 gsm, about 175 gsm, about 180 gsm, about 185 gsm, about 190 gsm, about 195 gsm, about 200 gsm, about 205 gsm, about 210 gsm, about 215 gsm, about 220 gsm, about 225 gsm, about 230 gsm, about 235 gsm, about 240 gsm, about 245 gsm, or about 250 gsm.

[0223] The weight of the adhesive skin contact layer can be at least about 40 gsm, at least about 50 gsm, at least about 60 gsm, at least about 70 gsm, at least about 80 gsm, at least about 90 gsm, at least about 100 gsm, at least about 110 gsm, at least about 120 gsm, at least about 130 gsm, at least about 140 gsm, at least about 150 gsm, at least about 155 gsm, at least about 160 gsm, at least about 165 gsm, at least about 170 gsm, at least about 175 gsm, at least about 180 gsm, at least about 185 gsm, at least about 190 gsm, at least about 195 gsm, at least about 200 gsm, at least about 205 gsm, at least about 210 gsm, at least about 215 gsm, at least about 220 gsm, at least about 225 gsm, at least about 230 gsm, at least about 235 gsm, at least about 240 gsm, at least about 245 gsm, or at least about 250 gsm.

[0224] The weight of the adhesive skin contact layer can be no more than about 40 gsm, no more than about 50 gsm, no more than about 60 gsm, no more than about 70 gsm, no more than about 80 gsm, no more than about 90 gsm, no more than about 100 gsm, no more than about 110 gsm, no more than about 120 gsm, no more than about 130 gsm, no more than about 140 gsm, no more than about 150 gsm, no more than about 155 gsm, no more than about 160 gsm, no more than about 165 gsm, no more than about 170 gsm, no more than about 175 gsm, no more than about 180 gsm, no more than about 185 gsm, no more than about 190 gsm, no more than about 195 gsm, no more than about 200 gsm, no more than about 205 gsm, no more than about 210 gsm, no more than about 215 gsm, no more than about 220 gsm, no more than about 225 gsm, no more than about 230 gsm, no more than about 235 gsm, no more than about 240 gsm, no more than about 245 gsm, or no more than about 250 gsm.

[0225] The weight of the adhesive skin contact layer can be from about 40 gsm to about 250 gsm, from about 50 gsm to about 250 gsm, from about 60 gsm to about 250 gsm, from about 70 gsm to about 250 gsm, from about 80 gsm to about 250 gsm, from about 90 gsm to about 250 gsm, from about 100 gsm to about 250 gsm, from 125 gsm to about 245 gsm, from about 135 gsm to about 240 gsm, from about 150 gsm to about 235 gsm, from about 160 gsm to about 230 gsm, from about 170 gsm to about 230 gsm, from about 175 gsm to about 225 gsm, from about 180 gsm to about 220 gsm, from about 185 gsm to about 215 gsm, from about 190 gsm to about 210 gsm, from about 195 gsm to about 205 gsm, or about 200 gsm.

[0226] Advantageously, adhesive skin contact layers having a weight of from about 100 gsm to about 250 gsm provide a more extensible gelled structure, and thus, in the event of an air leak, the layer can seal the leak more readily than layers having a weight of less than 100 gsm, particularly less than 40 gsm. Further, adhesive skin contact layers having a weight greater than 250 gsm exhibit processing problems, such as the adhesive can "run out" of the cut shape, rendering the adhesive skin contact layer unusable.

[0227] The adhesive skin contact layer can include perforations, each perforation having a diameter of about 1.25 mm, about 1.30 mm, about 1.35 mm, about 1.40 mm, about 1.45 mm, about 1.50 mm, about 1.55 mm, about 1.60 mm, about 1.65 mm, about 1.70 mm, about 1.75 mm, about 1.80 mm, about 1.85 mm, about 1.90 mm, about 1.95 mm, about 2.00 mm, about 2.05 mm, about 2.10 mm, about 2.15 mm, about 2.20 mm, about 2.25 mm, about 2.30 mm, about 2.35 mm, about 2.40 mm, about 2.45 mm, about 2.50 mm, about 2.55 mm, about 2.60 mm, about 2.65 mm, about 2.70 mm, about 2.75 mm, about 2.80 mm, about 2.85 mm, about 2.90 mm, about 2.95 mm, about 3.00 mm, about 3.10 mm, about 3.20 mm, about 3.30 mm, about 3.40 mm, about 3.50 mm, about 3.60 mm, about 3.70 mm, about 3.80 mm, about 3.90 mm, about 4.00 mm, about 4.10 mm, about 4.20 mm, about 4.30 mm, about 4.40 mm, about 4.50 mm, about 4.60 mm, about 4.70 mm, about 4.80 mm, about 4.90 mm, or about 5.00 mm.

[0228] The adhesive skin contact layer can include perforations each having a diameter of at least about 1.25 mm, at least about 1.30 mm, at least about 1.35 mm, at least about 1.40 mm, at least about 1.45 mm, at least about 1.50 mm, at least about 1.55 mm, at least about 1.60 mm, at least about 1.65 mm, at least about 1.70 mm, at least about 1.75 mm, at least about 1.80 mm, at least about 1.85 mm, at least about 1.90 mm, at least about 1.95 mm, at least about 2.00 mm, at least about 2.05 mm, at least about 2.10 mm, at least about 2.15 mm, at least about 2.20 mm, at least about 2.25 mm, at least about 2.30 mm, at least about 2.35 mm, at least about 2.40 mm, at least about 2.45 mm, at least about 2.50 mm, at least about 2.55 mm, at least about 2.60 mm, at least about 2.65 mm, at least about 2.70 mm, at least about 2.75 mm, at least about 2.80 mm, at least about 2.85 mm, at least about 2.90 mm, at least about 2.95 mm, at least about 3.00 mm, at least about 3.10 mm, at least about 3.20 mm, at least about 3.30 mm, at least about 3.40 mm, at least about 3.50 mm, at least about 3.60 mm, at least about 3.70 mm, at least about 3.80 mm, at least about 3.90 mm, at least about 4.00 mm, at least about 4.10 mm, at least about 4.20 mm, at least about 4.30 mm, at least about 4.40 mm, at least about 4.50 mm, at least about 4.60 mm, at least about 4.70 mm, at least about 4.80 mm, at least about 4.90 mm, or at least about 5.00 mm.

[0229] The adhesive skin contact layer can include perforations each having a diameter of no more than about 1.25 mm, no more than about 1.30 mm, no more than about 1.35 mm, no more than about 1.40 mm, no more than about 1.45 mm, no more than about 1.50 mm, no more than about 1.55 mm, no more than about 1.60 mm, no more than about 1.65 mm, no more than about 1.70 mm, no more than about 1.75 mm, no more than about 1.80 mm, no more than about 1.85 mm, no more than about 1.90 mm, no more than about 1.95 mm, no more than about 2.00 mm, no more than about 2.05 mm, no more than about 2.10 mm, no more than about 2.15 mm, no more than about 2.20 mm, no more than about 2.25 mm, no more than about 2.30 mm, no more than about 2.35 mm, no more than about 2.40 mm, no more than about 2.45 mm, no more than about 2.50 mm, no more than about 2.55 mm, no more than about 2.60 mm, no more than about 2.65 mm, no more than about 2.70 mm, no more than about 2.75 mm, no more than about 2.80 mm, no more than about 2.85 mm, no more than about 2.90 mm, no more than about 2.95 mm, no more than about 3.00 mm, no more than about 3.10 mm, no more than about 3.20 mm, no more than about 3.30 mm, no more than about 3.40 mm, no more than about 3.50 mm, no more than about 3.60 mm, no more than about 3.70 mm, no more than about 3.80 mm, no more than about 3.90 mm, no more than about 4.00 mm, no more than about 4.10 mm, no more than about 4.20 mm, no more than about 4.30 mm, no more than about 4.40 mm, no more than about 4.50 mm, no more than about 4.60 mm, no more than about 4.70 mm, no more than about 4.80 mm, no more than about 4.90 mm, or no more than about 5.00 mm.

[0230] The adhesive skin contact layer can include perforations each having a diameter of about 1.25 mm to about 5.00 mm, about 1.50 mm to about 4.50 mm, about 1.75 mm to about 4.00 mm, about 1.90 mm to about 3.50 mm, about 2.00 mm to about 3.00 mm, about 2.05 mm to about 2.80 mm, about 2.10 mm to about 2.60 mm, about 2.15 mm to about 2.50 mm, about 2.18 mm to about 2.40 mm, about 2.19 mm to about 2.30 mm, or about 2.20 mm.

[0231] The adhesive skin contact layer can include perforations each having a diameter of about 1.75 mm to about 4.00 mm, about 2.00 mm to about 3.50 mm, about 2.10 mm to about 3.00 mm, about 2.15 mm to about 2.50 mm, or about 2.20 mm.

[0232] The perforations can be arranged in a square arrangement or a triangular arrangement.

[0233] Square arrangement means that all or a majority, e.g., at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 95%, of the perforations are arranged in parallel rows and columns.

[0234] Triangular arrangement means that all or a majority, e.g., at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 95%, of the perforations are arranged in adjacent rows of perforations that are offset from one another. This means that the perforations in a first row are not arranged adjacent to the perforations in an adjacent second row, but rather the perforations in the first row are arranged adjacent to the gaps between the perforations in the second row, or adjacent to a portion of the gaps and a portion of the perforations in the second row.

[0235] Each perforation can comprise an opening comprising a 2D shape selected from the group comprising a circle, an ellipse, a triangle, a square, a rectangle, a hexagon, or an octagon.

[0236] One skilled in the art will appreciate that the size of the opening can be defined according to the shape of the opening. In some embodiments, the size of a circle is the diameter. In a plurality of other embodiments, the size of an ellipse is the longer diameter. In a further plurality of embodiments, the size of a hexagon is the longest diagonal; and, the size of a triangle, square, rectangle, octagon, or any other polygonal perforation is the longest side.

[0237] The pitch of the perforations in the first direction (i.e., the distance between the center point of one perforation and the center point of an adjacent one) can be about 6.0 mm, about 6.5 mm, about 7.0 mm, about 7.5 mm, about 8.0 mm, about 8.5 mm, about 9.0 mm, about 9.5 mm, about 10.0 mm, about 10.5 mm, about 11.0 mm, about 11.5 mm, or about 12.0 mm.

[0238] The pitch of the perforations in the first direction can be at least about 6.0 mm, at least about 6.5 mm, at least about 7.0 mm, at least about 7.5 mm, at least about 8.0 mm, at least about 8.5 mm, at least about 9.0 mm, at least about 9.5 mm, at least about 10.0 mm, at least about 10.5 mm, at least about 11.0 mm, at least about 11.5 mm, or at least about 12.0 mm.

[0239] The pitch of the perforations in the first direction can be no more than about 6.0 mm, no more than about 6.5 mm, no more than about 7.0 mm, no more than about 7.5 mm, no more than about 8.0 mm, no more than about 8.5 mm, no more than about 9.0 mm, no more than about 9.5 mm, no more than about 10.0 mm, no more than about 10.5 mm, no more than about 11.0 mm, no more than about 11.5 mm, or no more than about 12.0 mm.

[0240] The pitch of the perforations in the first direction can be about 6.0 mm to about 10.0 mm, about 6.5 mm to about 9.5 mm, about 7.0 mm to about 9.0 mm, about 7.5 mm to about 8.5 mm, about 7.75 mm to about 8.25 mm, or about 8.0 mm.

[0241] The pitch of the perforations in the second direction can be about 3.0 mm, about 3.5 mm, about 4.0 mm, about 4.5 mm, about 5.0 mm, about 5.5 mm, about 5.6 mm, about 6.0 mm, about 6.5 mm, about 7.0 mm, about 7.5 mm, about 8.0 mm, about 8.5 mm, about 9.0 mm, about 9.5 mm, or about 10.0 mm.

[0242] The pitch of the perforations in the second direction can be at least about 3.0 mm, at least about 3.5 mm, at least about 4.0 mm, at least about 4.5 mm, at least about 5.0 mm, at least about 5.5 mm, at least about 5.6 mm, at least about 6.0 mm, at least about 6.5 mm, at least about 7.0 mm, at least about 7.5 mm, at least about 8.0 mm, at least about 8.5 mm, at least about 9.0 mm, at least about 9.5 mm, or at least about 10.0 mm.

[0243] The pitch of the perforations in the second direction can be no more than about 3.0 mm, no more than about 3.5 mm, no more than about 4.0 mm, no more than about 4.5 mm, no more than about 5.0 mm, no more than about 5.5 mm, no more than about 5.6 mm, no more than about 6.0 mm, no more than about 6.5 mm, no more than about 7.0 mm, no more than about 7.5 mm, no more than about 8.0 mm, no more than about 8.5 mm, no more than about 9.0 mm, no more than about 9.5 mm, or no more than about 10.0 mm.

[0244] The pitch of the perforations in the second direction can be about 4.00 mm to about 7.00 mm, about 4.25 mm to about 6.75 mm, about 4.50 mm to about 6.50 mm, about 4.75 mm to about 6.25 mm, about 5.00 mm to about 6.00 mm, about 5.25 mm to about 5.75 mm, about 5.40 mm to about 5.70 mm, about 5.50 mm to about 5.65 mm, about 5.55 mm to about 5.62 mm, or about 5.60 mm.

[0245] Advantageously, the spacing of the perforations of the present application, particularly in embodiments wherein the spacing in the first direction is about 7 mm to 90 mm, particularly about 8 mm and the spacing in the second direction is about 5.00 mm to about 6.00 mm, particularly about 5.6 mm, provides a good perforated / non-perforated ratio of the adhesive skin contact layer. Beneficially, this provides effective moisture evaporation (e.g. prevents pooling) and strong adhesion to the patient. Surprisingly and advantageously, it has been found that the adhesive skin contact layer of the present application, particularly in embodiments having the above perforation spacing, remains adhered to the user for at least seven days.

[0246] The total area of the perforations can be about 1300 mm 2 , about 1350 mm 2 , about 1400 mm 2 , about 1450 mm 2 , about 1500 mm 2 , about 1550 mm 2 , about 1600 mm 2 , about 1650 mm 2 , about 1700 mm 2 , about 1750 mm 2 , about 1800 mm 2 , about 1850 mm 2 , about 1900 mm 2 , about 1950 mm 2 , about 2000 mm 2 , about 2050 mm 2 , about 2100 mm 2 , about 2150 mm 2 , about 2200 mm 2 , about 2250 mm 2 , about 2300 mm 2 , about 2350 mm 2 , about 2400 mm 2 , about 2450 mm 2 , or about 2500 mm 2 .

[0247] The total area of the perforations can be about 1300 mm 2 to about 2500 mm 2 , about 1400 mm 2 to about 2450 mm 2 , about 1500 mm 2 to about 2400 mm 2 , about 1600 mm 2 to about 2350 mm2 about 1700 mm 2 to about 2300 mm 2 about 1800 mm 2 to about 2250 mm 2 about 1900 mm 2 to about 2200 mm 2 about 2000 mm 2 to about 2150 mm 2 about 2100 mm 2 .

[0248] The degree of perforation can be about 5% to about 50%, about 6% to about 45%, about 7% to about 40%, about 8% to about 35%, about 9% to about 30%, about 10% to about 25%, about 10% to about 20%, about 10% to about 15%, or about 12% of the area of the adhesive skin contact layer.

[0249] The degree of perforation can be about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 12%, about 14%, about 16%, about 18%, about 20%, about 22%, about 24%, about 26%, about 28%, about 30%, about 32%, about 34%, about 36%, about 38%, about 40%, about 42%, about 44%, about 46%, about 48%, or about 50% of the area of the adhesive skin contact layer.

[0250] The degree of perforation can be about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 12%, about 14%, about 16%, about 18%, about 20%, about 22%, about 24%, about 26%, about 28%, about 30%, about 32%, about 34%, about 36%, about 38%, about 40%, about 42%, about 44%, about 46%, about 48%, or at least about 50% of the area of the adhesive skin contact layer.

[0251] The degree of perforation can be no more than about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 12%, about 14%, about 16%, about 18%, about 20%, about 22%, about 24%, about 26%, about 28%, about 30%, about 32%, about 34%, about 36%, about 38%, about 40%, about 42%, about 44%, about 46%, about 48%, or no more than about 50% of the area of the adhesive skin contact layer.

[0252] The thickness of the adhesive skin contact layer can be about 0.5 mm, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1.0 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, or about 1.5 mm.

[0253] The thickness of the adhesive skin contact layer can be at least about 0.5 mm, at least about 0.6 mm, at least about 0.7 mm, at least about 0.8 mm, at least about 0.9 mm, at least about 1.0 mm, at least about 1.1 mm, at least about 1.2 mm, at least about 1.3 mm, at least about 1.4 mm, or at least about 1.5 mm.

[0254] The thickness of the adhesive skin contact layer can be no more than about 0.5 mm, no more than about 0.6 mm, no more than about 0.7 mm, no more than about 0.8 mm, no more than about 0.9 mm, no more than about 1.0 mm, no more than about 1.1 mm, no more than about 1.2 mm, no more than about 1.3 mm, no more than about 1.4 mm, or no more than about 1.5 mm.

[0255] The thickness of the adhesive skin contact layer can be from about 0.5 mm to about 1.5 mm, from about 0.6 mm to about 1.4 mm, from about 0.7 mm to about 1.3 mm, from about 0.8 mm to about 1.2 mm, from about 0.9 mm to about 1.1 mm, or about 1.0 mm.

[0256] The perforations can be formed by a punch perforation, a hot needle process, a laser ablation process, or an ultrasonic process. In particular, the perforations can be formed by a mechanical punch perforation. Advantageously, the mechanical punch perforation prevents or at least significantly reduces the formation of a donut or volcano-like structure around the perforations after the perforations are formed. The perforations can be formed by mechanically punch perforating the adhesive layer, which includes a release liner covering at least one surface of the adhesive layer. After the adhesive layer is mechanically punch perforated, the release liner can be removed from the at least one surface of the adhesive layer to remove any "waste" that remains after the mechanical punch perforation.

[0257] The adhesive skin contact layer can be any shape, such as a circle, an ellipse, a triangle, a square, a rectangle, a hexagon, an octagon, or any irregular shape, such as an irregular quadrilateral.

[0258] The adhesive skin contact layer can comprise a window. Thus, the adhesive skin contact layer can be an adhesive skin contact border layer having a peripheral shape / peripheral shape / circumferential shape. The window can be centrally located with respect to the periphery of the adhesive skin contact layer. The border layer can comprise an outer periphery defining an outer shape of the border, for example a square, a rectangle, a circle. The border layer can comprise an inner periphery defining a shape of the window. The window can have the same or similar shape as the outer periphery of the border layer. In use, the wound dressing can be adhered to the skin surface such that the wound site is located within the window. In this way, the adhesive skin contact layer does not come into direct contact with the wound site, but rather partially or wholly surrounds the wound site. Thus, the adhesive skin contact layer can only come into contact with the intact skin surrounding the wound. Advantageously, this means that the wound dressing does not adhere directly to the wound site, and therefore, removing the wound dressing from the patient does not damage the wound and minimises discomfort to the patient. The window allows the adhesive skin contact layer to be adhered around the wound, such that the wound site is located within the window, and therefore, allows the patient's wound to come into contact or fluid communication with, for example and preferably the wound contact layer, when the wound dressing is applied to the patient's skin.

[0259] The area of the window can be about 900 mm 2 to about 50,000 mm 2 , about 1600 mm 2 to about 45,000 mm 2 , about 2500 mm 2 to about 40,000 mm 2 , about 3600 mm 2 to about 35,000 mm 2 , about 4900 mm 2 to about 30,000 mm 2 , about 6400 mm 2 to about 25,000 mm 2 , about 8100 mm 2 to about 20,000 mm 2 , about 10,000 mm 2 to about 15,000 mm 2 , or about 12,500 mm 2 .

[0260] The area of the window can be about 900 mm 2 , about 1200 mm 2 , about 1600 mm 2 , about 2000 mm 2 , about 2500 mm 2 , about 3000 mm 2 , about 3600 mm 2 , about 4000 mm 2 , about 4400 mm2 about 4900 mm 2 about 5400 mm 2 about 5900 mm 2 about 6400 mm 2 about 6900 mm 2 about 7500 mm 2 about 8100 mm 2 about 8700 mm 2 about 9300 mm 2 about 10,000 mm 2 about 12,500 mm 2 about 15,000 mm 2 about 17,500 mm 2 about 20,000 mm 2 about 22,500 mm 2 about 25,000 mm 2 about 27,500 mm 2 about 30,000 mm 2 about 32,500 mm 2 about 35,000 mm 2 about 37,500 mm 2 about 40,000 mm 2 about 42,500 mm 2 about 45,000 mm 2 about 47,500 mm 2 or about 50,000 mm 2 .

[0261] The area of the window can be at least about 900 mm 2 at least about 1200 mm 2 at least about 1600 mm 2 at least about 2000 mm 2 at least about 2500 mm 2 at least about 3000 mm 2 at least about 3600 mm 2 at least about 4000 mm 2 at least about 4400 mm 2 at least about 4900 mm 2 at least about 5400 mm 2 at least about 5900 mm 2 at least about 6400 mm 2 at least about 6900 mm 2 at least about 7500 mm 2 at least about 8100 mm 2at least about 8700 mm 2 at least about 9300 mm 2 at least about 10,000 mm 2 at least about 12,500 mm 2 at least about 15,000 mm 2 at least about 17,500 mm 2 at least about 20,000 mm 2 at least about 22,500 mm 2 at least about 25,000 mm 2 at least about 27,500 mm 2 at least about 30,000 mm 2 at least about 32,500 mm 2 at least about 35,000 mm 2 at least about 37,500 mm 2 at least about 40,000 mm 2 at least about 42,500 mm 2 at least about 45,000 mm 2 at least about 47,500 mm 2 or at least about 50,000 mm 2 .

[0262] The area of the window can be no more than about 900 mm 2 no more than about 1200 mm 2 no more than about 1600 mm 2 no more than about 2000 mm 2 no more than about 2500 mm 2 no more than about 3000 mm 2 no more than about 3600 mm 2 no more than about 4000 mm 2 no more than about 4400 mm 2 no more than about 4900 mm 2 no more than about 5400 mm 2 no more than about 5900 mm 2 no more than about 6400 mm 2 no more than about 6900 mm 2 no more than about 7500 mm 2 no more than about 8100 mm 2 no more than about 8700 mm 2 no more than about 9300 mm 2 no more than about 10,000 mm 2 no more than about 12,500 mm 2 no more than about 15,000 mm2 no more than about 17,500 mm 2 no more than about 20,000 mm 2 no more than about 22,500 mm 2 no more than about 25,000 mm 2 no more than about 27,500 mm 2 no more than about 30,000 mm 2 no more than about 32,500 mm 2 no more than about 35,000 mm 2 no more than about 37,500 mm 2 no more than about 40,000 mm 2 no more than about 42,500 mm 2 no more than about 45,000 mm 2 no more than about 47,500 mm 2 or no more than about 50,000 mm 2 .

[0263] The perforations can be distributed along a plurality of concentric circles formed about a center point of the skin contact layer. In some embodiments, the concentric circles can be uniformly spaced apart from one another, and / or the perforations in a same concentric circle can be uniformly distributed along the circle. The concentric circles can be uniformly spaced apart from one another.

[0264] The perforations can be distributed along a plurality of concentric polygons formed about a center point of the adhesive skin contact layer.

[0265] The perforations can be distributed along a plurality of concentric decagons formed about a center point of the adhesive skin contact layer.

[0266] The perforations can be distributed along a plurality of concentric squares, pentagons, hexagons, heptagons, octagons, or nonagons. The concentric polygons can be uniformly spaced apart from one another, and / or the perforations in a same concentric polygon can be uniformly distributed along the polygon.

[0267] The perforations can be cuts / indentations (i.e., elongated perforations) formed in the adhesive skin contact layer. The adhesive skin contact layer can have a circular shape, and the cuts can have at least partially circular or arcuate shapes. The cuts can define at least a portion of a plurality of concentric circles. The cuts can have shapes that at least partially extend parallel to an outer periphery of the adhesive skin contact layer. The adhesive skin contact layer can include one or more connecting portions extending between the cuts and / or include connecting portions of the adhesive skin contact layer that are separated by the cuts.

[0268] The plurality of perforations can be uniformly or substantially uniformly distributed throughout the adhesive skin contact layer. In some embodiments, the perforations can be non-uniformly distributed throughout the adhesive skin contact layer, such that the perforations are more concentrated in certain portions of the adhesive skin contact layer than in other portions of the adhesive skin contact layer. The perforations can be concentrated in a plurality of regions of the adhesive skin contact layer, defining a plurality of clusters of perforations. Each cluster can include the same number of perforations. Each cluster can include a different number of perforations. Each cluster can have the same or substantially the same size and / or shape. Each cluster can have a different size and / or shape. One or more clusters can have substantially the same shape as each perforation. The plurality of clusters can have one or more shapes selected from the group consisting of circular, triangular, square, rectangular, diamond, pentagonal, hexagonal, or octagonal. The perforations can be uniformly or substantially uniformly distributed within each cluster.

[0269] The adhesive skin contact layer can include an upper surface and a lower surface. The upper surface and / or the lower surface can be flat, or at least substantially flat, for example due to slightly raised or sunken portions in the adhesive skin contact layer around each perforation, such that the adhesive skin contact layer has a uniform, flat profile when viewed from the side.

[0270] At least a portion of the adhesive skin contact layer can be raised, or otherwise shaped unevenly, such that the adhesive skin contact layer has a non-uniform or non-planar profile when viewed from the side.

[0271] The plurality of perforations can include a plurality of first perforations and a plurality of second perforations.

[0272] The adhesive skin contact layer can include perforations that are the same shape but oriented differently. For example, the plurality of second perforations can have the same shape as the plurality of first perforations, but have a different orientation, such as being rotated 20 degrees, 30 degrees, 45 degrees, 60 degrees, 90 degrees, or 180 degrees from the orientation of the plurality of first perforations.

[0273] The plurality of first perforations and the plurality of second perforations can have different shapes. For example, the plurality of first perforations can have a circular shape, while the plurality of second perforations can have a square shape. In some embodiments, the plurality of first perforations and the plurality of second perforations can have the same or substantially the same shape. The plurality of first perforations and the plurality of second perforations can have different shapes.

[0274] The plurality of first perforations and the plurality of second perforations can have different sizes. For example, each of the plurality of first perforations can have a larger diameter than each of the plurality of second perforations. In some embodiments, the plurality of first perforations and the plurality of second perforations can each have the same or substantially the same size.

[0275] The diameter of each of the plurality of first perforations and each of the plurality of second perforations can be selected from: about 1.25 mm, about 1.30 mm, about 1.35 mm, about 1.40 mm, about 1.45 mm, about 1.50 mm, about 1.55 mm, about 1.60 mm, about 1.65 mm, about 1.70 mm, about 1.75 mm, about 1.80 mm, about 1.85 mm, about 1.90 mm, about 1.95 mm, about 2.00 mm, about 2.05 mm, about 2.10 mm, about 2.15 mm, about 2.20 mm, about 2.25 mm, about 2.30 mm, about 2.35 mm, about 2.40 mm, about 2.45 mm, about 2.50 mm, about 2.55 mm, about 2.60 mm, about 2.65 mm, about 2.70 mm, about 2.75 mm, about 2.80 mm, about 2.85 mm, about 2.90 mm, about 2.95 mm, about 3.00 mm, about 3.10 mm, about 3.20 mm, about 3.30 mm, about 3.40 mm, about 3.50 mm, about 3.60 mm, about 3.70 mm, about 3.80 mm, about 3.90 mm, about 4.00 mm, about 4.10 mm, about 4.20 mm, about 4.30 mm, about 4.40 mm, about 4.50 mm, about 4.60 mm, about 4.70 mm, about 4.80 mm, about 4.90 mm, or about 5.00 mm.

[0276] The diameter of each of the plurality of first perforations and each of the plurality of second perforations can be selected from at least about 1.25 mm, at least about 1.30 mm, at least about 1.35 mm, at least about 1.40 mm, at least about 1.45 mm, at least about 1.50 mm, at least about 1.55 mm, at least about 1.60 mm, at least about 1.65 mm, at least about 1.70 mm, at least about 1.75 mm, at least about 1.80 mm, at least about 1.85 mm, at least about 1.90 mm, at least about 1.95 mm, at least about 2.00 mm, at least about 2.05 mm, at least about 2.10 mm, at least about 2.15 mm, at least about 2.20 mm, at least about 2.25 mm, at least about 2.30 mm, at least about 2.35 mm, at least about 2.40 mm, at least about 2.45 mm, at least about 2.50 mm, at least about 2.55 mm, at least about 2.60 mm, at least about 2.65 mm, at least about 2.70 mm, at least about 2.75 mm, at least about 2.80 mm, at least about 2.85 mm, at least about 2.90 mm, at least about 2.95 mm, at least about 3.00 mm, at least about 3.10 mm, at least about 3.20 mm, at least about 3.30 mm, at least about 3.40 mm, at least about 3.50 mm, at least about 3.60 mm, at least about 3.70 mm, at least about 3.80 mm, at least about 3.90 mm, at least about 4.00 mm, at least about 4.10 mm, at least about 4.20 mm, at least about 4.30 mm, at least about 4.40 mm, at least about 4.50 mm, at least about 4.60 mm, at least about 4.70 mm, at least about 4.80 mm, at least about 4.90 mm, or at least about 5.00 mm.

[0277] The diameter of each of the plurality of first perforations and each of the plurality of second perforations can be selected from: no more than about 1.25 mm, no more than about 1.30 mm, no more than about 1.35 mm, no more than about 1.40 mm, no more than about 1.45 mm, no more than about 1.50 mm, no more than about 1.55 mm, no more than about 1.60 mm, no more than about 1.65 mm, no more than about 1.70 mm, no more than about 1.75 mm, no more than about 1.80 mm, no more than about 1.85 mm, no more than about 1.90 mm, no more than about 1.95 mm, no more than about 2.00 mm, no more than about 2.05 mm, no more than about 2.10 mm, no more than about 2.15 mm, no more than about 2.20 mm, no more than about 2.25 mm, no more than about 2.30 mm, no more than about 2.35 mm, no more than about 2.40 mm, no more than about 2.45 mm, no more than about 2.50 mm, no more than about 2.55 mm, no more than about 2.60 mm, no more than about 2.65 mm, no more than about 2.70 mm, no more than about 2.75 mm, no more than about 2.80 mm, no more than about 2.85 mm, no more than about 2.90 mm, no more than about 2.95 mm, no more than about 3.00 mm, no more than about 3.10 mm, no more than about 3.20 mm, no more than about 3.30 mm, no more than about 3.40 mm, no more than about 3.50 mm, no more than about 3.60 mm, no more than about 3.70 mm, no more than about 3.80 mm, no more than about 3.90 mm, no more than about 4.00 mm, no more than about 4.10 mm, no more than about 4.20 mm, no more than about 4.30 mm, no more than about 4.40 mm, no more than about 4.50 mm, no more than about 4.60 mm, no more than about 4.70 mm, no more than about 4.80 mm, no more than about 4.90 mm, or no more than about 5.00 mm.

[0278] The plurality of first perforations can be arranged in a border portion of the adhesive skin contact layer. The plurality of second perforations can be arranged in a central portion of the adhesive skin contact layer. The central portion can be surrounded by the border portion. The plurality of first perforations can each have a greater diameter than each of the plurality of second perforations.

[0279] In some embodiments, the plurality of first perforations and the plurality of second perforations can be distributed in different configurations. For example, the plurality of first perforations can be distributed in a plurality of columns, and the first perforations of adjacent columns can be staggered with respect to each other, such that the plurality of first perforations are distributed in a triangular arrangement layout, while the plurality of second perforations are distributed around each first perforation.

[0280] The absorbent structure can comprise a superabsorbent layer.

[0281] The superabsorbent layer defined in the present specification is a layer comprising a superabsorbent material that can absorb and hold at least about 15 grams per gram per 10 minutes when tested with Solution A, 15 g / g (g / g 10 min).

[0282] Advantageously, the superabsorbent layer has particularly advantageous fluid management capabilities, which means that the superabsorbent layer absorbs and holds a large amount of fluid (i.e. wound exudate). Advantageously, the superabsorbent layer has an absorption capacity of about 25 grams per gram per 10 minutes, at least about 15 grams per gram per 10 minutes when tested with Solution A, and an absorption capacity under compression (-80 mm Hg negative pressure) of about 0.85 g / cm 2 , and at least about 0.55 g / cm 2 .

[0283] Furthermore, the superabsorbent layer is flexible such that it can easily conform to the contours of the patient’s body at the wound site when in use, thus enhancing the comfort of the patient when wearing the wound dressing. In some wound dressings of the prior art, one or more layers of the wound dressing can not have the flexibility required to allow the wound dressing to easily conform to the contours of the patient’s body. In such cases, the wound dressing can be more likely to detach from the patient’s body compared to a wound dressing that conforms well to the contours of the patient’s body. Furthermore, the superabsorbent layer retains its structure when wet or damp, thus, the superabsorbent layer retains its strength and maintains its integrity within the absorbent structure of the wound dressing, thereby preventing the splitting and shredding of fibres when in use.

[0284] The superabsorbent layer can comprise an upper layer and a lower layer. The upper layer and the lower layer can encapsulate a first material comprising at least one of nonwoven fibres, absorbent material, and hot melt binder.

[0285] The amount of hot melt binder present can be about 40 g / m 2 to about 100 g / m 2 , about 45 g / m 2 to about 95 g / m 2 , about 50 g / m 2 to about 90 g / m 2 , about 55 g / m 2 to about 85 g / m 2 , about 60 g / m 2 to about 80 g / m 2 , about 65 g / m 2 to about 75 g / m 2 , or about 70 g / m 2 .

[0286] The amount of hot melt binder present can be about 40 g / m2 about 45 g / m 2 about 50 g / m 2 about 55 g / m 2 about 60 g / m 2 about 65 g / m 2 about 70 g / m 2 about 75 g / m 2 about 80 g / m 2 about 85 g / m 2 about 90 g / m 2 about 95 g / m 2 about 100 g / m 2 .

[0287] The amount of hot melt binder present can be at least about 40 g / m 2 about 45 g / m 2 about 50 g / m 2 about 55 g / m 2 about 60 g / m 2 about 65 g / m 2 about 70 g / m 2 about 75 g / m 2 about 80 g / m 2 about 85 g / m 2 about 90 g / m 2 about 95 g / m 2 about 100 g / m 2 .

[0288] The amount of hot melt binder present can be no more than about 40 g / m 2 about 45 g / m 2 about 50 g / m 2 about 55 g / m 2 about 60 g / m 2 about 65 g / m 2 about 70 g / m 2 about 75 g / m 2 about 80 g / m 2 about 85 g / m 2 about 90 g / m 2 about 95 g / m 2 about 100 g / m 2 .

[0289] The hot-melt binder can be a copolymer. It can be ethylene-vinyl acetate (EVA) or polylactic acid (PLA). In the manufacture of the superabsorbent layer, the superabsorbent layer can be heated to melt the hot-melt binder and bond the nonwoven fibers of the first material together. Advantageously, this prevents or at least significantly limits the amount of fiber shedding during use of the superabsorbent layer. Therefore, the presence of the hot-melt binder in the superabsorbent layer significantly increases the strength of the layer and prevents the separation of the absorbent structure.

[0290] Advantageously, the hot melt binder is at approximately 40 g / m 2 Approximately 100 g / m 2 The presence of this amount means that the superabsorbent layer is flexible when dry and retains the strength required to hold the absorbent structure together when wet. If the hot-melt binder is below 40 g / m², 2 If the amount of [amount missing] is present, the superabsorbent layer will lose its structure upon wetting and may at least partially separate. If the hot-melt binder is in a concentration greater than 100 g / m³, [the situation will worsen]. 2 If the amount of superabsorbent material is present, the superabsorbent structure will be inflexible and too rigid for the purpose of using the superabsorbent layer in wound dressings, where the wound dressing needs to be manipulated according to the contours of the user's body.

[0291] The superabsorbent layer can absorb exudate from the wound contact layer and allow fluid to pass through it.

[0292] The absorbent material can be a superabsorbent material, particularly one capable of absorbing wound exudate while allowing fluid to pass through it. The superabsorbent material can be a powder, foam, sponge, or fiber-based material. Advantageously, in embodiments where the superabsorbent material is a powder, its absorption properties are enhanced due to the high surface area to volume ratio.

[0293] Nonwoven fibers can be cellulose fibers. Cellulose nonwoven fibers can be arranged as a cellulose nonwoven fiber matrix. The cellulose nonwoven matrix can be a carrier on which absorbent material can be bonded, for example, absorbent material can be dispersed on the cellulose nonwoven matrix. The absorbent material can be uniformly or substantially uniformly dispersed throughout the nonwoven fiber, for example, in or on the cellulose nonwoven matrix.

[0294] Cellulose nonwoven fibers may contain only cellulose fibers, or may contain a certain proportion of non-cellulose textile fibers or gel-forming fibers. Cellulose fibers may include continuous filament yarns and / or staple fibers.

[0295] The nonwoven fibers of the first material can have a low bulk density, i.e. a loose packing. The nonwoven fibers can be arranged in a three-dimensional random fiber orientation. The nonwoven fibers can be cellulose fibers. Absorbent material, such as superabsorbent material, such as sodium polyacrylate, such as sodium polyacrylate in powder form, can be interspersed between the nonwoven fibers of the first material.

[0296] The upper layer and / or the lower layer can comprise cellulose fibers. In addition to or instead of cellulose fibers, the upper layer and / or the lower layer can comprise fibers formed from a hot melt binder, such as EVA or PLA. The fibers comprised in the upper layer and / or the lower layer can have a high bulk density and can have a greater bulk density than the fibers of the first material. The fibers comprised in the upper layer and / or the lower layer can be arranged substantially in a 2D orientation. The fibers comprised in the upper layer and / or the lower layer can be in an ordered orientation, or at least can be more ordered than the fibers of the first material. The upper layer and the lower layer can each have a thickness that is less than the thickness of the first material.

[0297] Advantageously, the first material, the upper layer and the lower layer of the superabsorbent layer show structural integrity of the superabsorbent layer, thus maintaining the integrity of the superabsorbent layer even when wetted, such as when wetted by exudate.

[0298] The first material can comprise gel-forming fibers. Gel-forming fibers are fibers that become wet, slippery and / or gel-like upon absorption of wound exudate, thus reducing the tendency of surrounding fibers to stick to the wound. The gel-forming fibers can be hygroscopic. Advantageously, the gel-forming fibers prevent or at least significantly prevent the superabsorbent layer from sticking to the wound in use, which can be uncomfortable for the patient, especially when the wound dressing is removed in order to replace it with a new wound dressing.

[0299] The gel-forming fibers can be of the type that maintain their structural integrity upon absorption of fluid, such as wound exudate, or can be of the type that lose their fibrous form and become amorphous or structureless gels.

[0300] The gel-forming fibers can be sodium carboxymethylcellulose fibers, chemically modified cellulose fibers, alkyl sulfonate-modified cellulose fibers, such as those described in WO2012 / 061225, pectin fibers, alginate fibers, chitosan fibers, hyaluronic acid fibers, or other polysaccharide fibers or fibers derived from gums. The cellulose fibers preferably have a degree of substitution of at least 0.05 carboxymethyl groups per glucose unit. The gel-forming fibers preferably have an absorbency of at least 2 grams of 0.9% saline solution per gram of fiber (measured by the free swell method).

[0301] The upper layer can be an upper fabric layer. The lower layer can be a lower fabric layer. The upper fabric layer can be a cellulosic fabric layer. The lower fabric layer can be a cellulosic fabric layer. The upper fabric layer and the lower fabric layer can be joined around their entire periphery to enclose / encapsulate the first material.

[0302] The upper layer and the lower layer can be formed from the same material as the first material and comprise nonwoven fibers, absorbent material, and hot melt binder.

[0303] The upper fabric layer and / or the lower fabric layer can comprise a hot melt binder.

[0304] In embodiments where the superabsorbent layer comprises gel-forming fibers, the gel-forming fibers can include a hot melt binder. The gel-forming fibers can be a carrier to which the hot melt binder can be bound, for example the hot melt binder can be dispersed throughout or on the gel-forming fibers. The absorbent material can be uniformly or substantially uniformly dispersed throughout or on the gel-forming fibers.

[0305] In embodiments where the superabsorbent layer comprises a cellulosic nonwoven substrate, the cellulosic nonwoven substrate can be a carrier on which a hot melt binder can be incorporated, for example the hot melt binder can be dispersed on the cellulosic nonwoven substrate. The hot melt binder can be uniformly or substantially uniformly dispersed throughout or on the nonwoven fibers, for example the cellulosic nonwoven substrate. The absorbent material can comprise sodium polyacrylate. The sodium polyacrylate can be a powder, foam, sponge, or fiber.

[0306] The superabsorbent layer can comprise one or more windows. The windows can be slits or openings in the superabsorbent layer. The windows can be in one or both of the upper layer and the lower layer. The one or more windows can be perforations. The slits or openings can be arranged in a direction that is planar to the longitudinal axis of the superabsorbent layer and transverse to the longitudinal axis of the superabsorbent layer. Advantageously, this arrangement helps to manage the flow of exudate through the superabsorbent layer of the wound dressing. In particular, the windows facilitate or enable wound exudate to travel or be absorbed in a preferred direction. The windows facilitate or enable wound exudate to travel laterally over the superabsorbent rather than axially. Beneficially, this means that wound exudate is spread over a greater surface area of the superabsorbent layer before being transferred to the wound dressing layer that is positioned directly above (in use) the superabsorbent layer, thus facilitating the flow of wound exudate away from the wound site. The windows can be formed mechanically, for example by cutting or mechanically punching the perforations. The windows are preferably slits of a length equal to about 80% of the length of the superabsorbent layer. The windows can be arranged in rows and columns alternating vertically and horizontally across the superabsorbent layer. Advantageously, the windows help to make the most of the absorbent capacity of the superabsorbent layer and also help to transmit negative pressure through the superabsorbent layer.

[0307] The superabsorbent layer can have a basis weight of about 300 g / m 2 to about 550 g / m2 about 320 g / m 2 to about 545 g / m 2 about 340 g / m 2 to about 540 g / m 2 about 350 g / m 2 to about 535 g / m 2 about 370 g / m 2 to about 530 g / m 2 about 380 g / m 2 to about 525 g / m 2 about 390 g / m 2 to about 525 g / m 2 about 400 g / m 2 to about 520 g / m 2 about 410 g / m 2 to 510 g / m 2 about 420 g / m 2 to about 500 g / m 2 about 430 g / m 2 to about 490 g / m 2 about 440 g / m 2 to about 480 g / m 2 about 450 g / m 2 to about 470 g / m 2 or about 460 g / m 2 .

[0308] The basis weight of the superabsorbent layer can be about 300 g / m 2 about 310 g / m 2 about 320 g / m 2 about 330 g / m 2 about 340 g / m 2 about 350 g / m 2 about 360 g / m 2 about 370 g / m 2 about 380 g / m 2 about 390 g / m 2 about 400 g / m 2 about 410 g / m 2 about 420 g / m 2 about 430 g / m 2 about 440 g / m 2 about 450 g / m 2 about 460 g / m 2 about 470 g / m 2about 480 g / m 2 about 490 g / m 2 about 500 g / m 2 about 510 g / m 2 about 520 g / m 2 about 530 g / m 2 about 540 g / m 2 about 550 g / m 2 .

[0309] The basis weight of the superabsorbent layer can be at least about 300 g / m 2 at least about 310 g / m 2 at least about 320 g / m 2 at least about 330 g / m 2 at least about 340 g / m 2 at least about 350 g / m 2 at least about 360 g / m 2 at least about 370 g / m 2 at least about 380 g / m 2 at least about 390 g / m 2 at least about 400 g / m 2 at least about 410 g / m 2 at least about 420 g / m 2 at least about 430 g / m 2 at least about 440 g / m 2 at least about 450 g / m 2 at least about 460 g / m 2 at least about 470 g / m 2 at least about 480 g / m 2 at least about 490 g / m 2 at least about 500 g / m 2 at least about 510 g / m 2 at least about 520 g / m 2 at least about 530 g / m 2 at least about 540 g / m 2 or at least about 550 g / m 2 .

[0310] The basis weight of the superabsorbent layer can be no more than about 300 g / m 2 no more than about 310 g / m 2 no more than about 320 g / m 2 no more than about 330 g / m 2 no more than about 340 g / m 2, not more than about 350 g / m 2 , not more than about 360 g / m 2 , not more than about 370 g / m 2 , not more than about 380 g / m 2 , not more than about 390 g / m 2 , not more than about 400 g / m 2 , not more than about 410 g / m 2 , not more than about 420 g / m 2 , not more than about 430 g / m 2 , not more than about 440 g / m 2 , not more than about 450 g / m 2 , not more than about 460 g / m 2 , not more than about 470 g / m 2 , not more than about 480 g / m 2 , not more than about 490 g / m 2 , not more than about 500 g / m 2 , not more than about 510 g / m 2 , not more than about 520 g / m 2 , not more than about 530 g / m 2 , not more than about 540 g / m 2 , or not more than about 550 g / m 2 .

[0311] Advantageously, a superabsorbent layer having a basis weight as described above provides sufficient fluid absorption and retention and, when in use, sufficient flexibility to conform to the body contours at the wound site of a patient. In particular, this advantageous effect is found with a superabsorbent layer having a basis weight in the range of about 340 g / m 2 to about 510 g / m 2 , in particular in the range of about 350 g / m 2 to about 500 g / m 2 . Below about 300 g / m 2 , the superabsorbent layer can not achieve sufficient absorption of fluids, i.e. wound exudate. Above about 520 g / m 2 , in particular above about 550 g / m 2 , the superabsorbent layer can be too thick and too dense, which can lead to processability problems during manufacturing and / or a non-flexible layer that does not conform to the body contours of a patient at the wound site when in use.

[0312] The superabsorbent layer can have a thickness of from about 1.40 mm to about 4.00 mm, from about 1.50 mm to about 3.90 mm, from about 1.60 mm to about 3.80 mm, from about 1.70 mm to about 3.70 mm, from about 1.80 mm to about 3.60 mm, from about 1.85 mm to about 3.50 mm, from about 1.90 mm to about 3.40 mm, from about 1.95 mm to about 3.30 mm, from about 2.00 mm to about 3.20 mm, from about 2.05 mm to about 3.10 mm, from about 2.10 mm to about 3.00 mm, from about 2.15 mm to about 2.90 mm, from about 2.20 mm to about 2.85 mm, from about 2.25 mm to about 2.80 mm, from about 2.30 mm to about 2.75 mm, from about 2.35 mm to about 2.70 mm, from about 2.40 mm to about 2.65 mm, from about 2.45 mm to about 2.60 mm, from about 2.50 mm to about 2.60 mm, or about 2.55 mm.

[0313] The superabsorbent layer can have a thickness of from about 1.40 mm, from about 1.45 mm, from about 1.50 mm, from about 1.55 mm, from about 1.60 mm, from about 1.65 mm, from about 1.70 mm, from about 1.75 mm, from about 1.80 mm, from about 1.85 mm, from about 1.90 mm, from about 1.95 mm, from about 2.00 mm, from about 2.05 mm, from about 2.10 mm, from about 2.15 mm, from about 2.20 mm, from about 2.25 mm, from about 2.30 mm, from about 2.35 mm, from about 2.40 mm, from about 2.45 mm, from about 2.50 mm, from about 2.50 mm, from about 2.55 mm, from about 2.60 mm, from about 2.65 mm, from about 2.70 mm, from about 2.75 mm, from about 2.80 mm, from about 2.85 mm, from about 2.90 mm, from about 2.95 mm, from about 3.00 mm, from about 3.05 mm, from about 3.10 mm, from about 3.15 mm, from about 3.20 mm, from about 3.25 mm, from about 3.30 mm, from about 3.35 mm, from about 3.40 mm, from about 3.45 mm, from about 3.50 mm, from about 3.55 mm, from about 3.60 mm, from about 3.65 mm, from about 3.70 mm, from about 3.75 mm, from about 3.80 mm, from about 3.85 mm, from about 3.90 mm, from about 3.95 mm, or from about 4.00 mm.

[0314] The thickness of the superabsorbent layer can be at least about 1.40 mm, at least about 1.45 mm, at least about 1.50 mm, at least about 1.55 mm, at least about 1.60 mm, at least about 1.65 mm, at least about 1.70 mm, at least about 1.75 mm, at least about 1.80 mm, at least about 1.85 mm, at least about 1.90 mm, at least about 1.95 mm, at least about 2.00 mm, at least about 2.05 mm, at least about 2.10 mm, at least about 2.15 mm, at least about 2.20 mm, at least about 2.25 mm, at least about 2.30 mm, at least about 2.35 mm, at least about 2.40 mm, at least about 2.45 mm, at least about 2.50 mm, at least about 2.50 mm, at least about 2.55 mm, at least about 2.60 mm, at least about 2.65 mm, at least about 2.70 mm, at least about 2.75 mm, at least about 2.80 mm, at least about 2.85 mm, at least about 2.90 mm, at least about 2.95 mm, at least about 3.00 mm, at least about 3.05 mm, at least about 3.10 mm, at least about 3.15 mm, at least about 3.20 mm, at least about 3.25 mm, at least about 3.30 mm, at least about 3.35 mm, at least about 3.40 mm, at least about 3.45 mm, at least about 3.50 mm, at least about 3.55 mm, at least about 3.60 mm, at least about 3.65 mm, at least about 3.70 mm, at least about 3.75 mm, at least about 3.80 mm, at least about 3.85 mm, at least about 3.90 mm, at least about 3.95 mm, or at least about 4.00 mm.

[0315] The thickness of the superabsorbent layer may be no more than approximately 1.40 mm, no more than approximately 1.45 mm, no more than approximately 1.50 mm, no more than approximately 1.55 mm, no more than approximately 1.60 mm, no more than approximately 1.65 mm, no more than approximately 1.70 mm, no more than approximately 1.75 mm, no more than approximately 1.80 mm, no more than approximately 1.85 mm, no more than approximately 1.90 mm, no more than approximately 1.95 mm, no more than approximately 2.00 mm, no more than approximately 2.05 mm, no more than approximately 2.10 mm, no more than approximately 2.15 mm, no more than approximately 2.20 mm, no more than approximately 2.25 mm, no more than approximately 2.30 mm, no more than approximately 2.35 mm, no more than approximately 2.40 mm, no more than approximately 2.45 mm, no more than approximately 2.50 mm, no more than approximately 2.50 mm, no more than approximately 2.55 mm, no more than approximately 2.60 mm, and no more than approximately 2.6 mm. 5mm, not exceeding approximately 2.70mm, not exceeding approximately 2.75mm, not exceeding approximately 2.80mm, not exceeding approximately 2.85mm, not exceeding approximately 2.90mm, not exceeding approximately 2.95mm, not exceeding approximately 3.00mm, not exceeding approximately 3.05mm, not exceeding approximately 3.10mm, not exceeding approximately 3.15mm, not exceeding approximately 3.20mm, not exceeding approximately 3.25mm, not exceeding approximately 3.30mm, not exceeding approximately 3.35mm, not exceeding approximately 3.40mm, not exceeding approximately 3.45mm, not exceeding approximately 3.50mm, not exceeding approximately 3.55mm, not exceeding approximately 3.60mm, not exceeding approximately 3.65mm, not exceeding approximately 3.70mm, not exceeding approximately 3.75mm, not exceeding approximately 3.80mm, not exceeding approximately 3.85mm, not exceeding approximately 3.90mm, not exceeding approximately 3.95mm, or not exceeding approximately 4.00mm.

[0316] Advantageously, the superabsorbent layer with the thickness described above provides sufficient fluid absorption and retention, and has sufficient flexibility to conform to the body contours at the patient's wound site during use. When the thickness is less than approximately 1.40 mm, the absorption capacity of the superabsorbent layer may be limited. When the thickness is greater than approximately 4.00 mm, the superabsorbent layer may be too thick to be processed during manufacturing, or at least not easily processed, and may not have sufficient flexibility to conform to the body contours at the patient's wound site during use.

[0317] More advantageously, in the case of having a basis weight as described above, for example, at about 300 g / m³ 2 Approximately 550 g / m 2Embodiments of the superabsorbent layer having a basis weight within the range of about 0.200 g / cm

[0318] The thickness of the superabsorbent layer can be measured using a Hampden soft material thickness gauge. A method for measuring the thickness of the superabsorbent layer using a Hampden soft material thickness gauge can include:

[0319] a. raising the bottom / feet of the thickness gauge to a height sufficient to place the test sample underneath it;

[0320] b. placing the feet on the test sample until the indicator light comes on;

[0321] c. from the time the indicator light comes on, let the feet contact the test sample for 10 seconds. If the light stays on, record the reading;

[0322] d. repeat the desired number of repetitions (e.g., 10 repetitions), ensuring that the instrument is zeroed between each repetition.

[0323] The density of the superabsorbent layer can be about 0.200 g / cm 3 to about 0.305 g / cm 3 , about 0.205 g / cm 3 to about 0.300 g / cm 3 , about 0.210 g / cm 3 to about 0.295 g / cm 3 , about 0.215 g / cm 3 to about 0.290 g / cm 3 , about 0.220 g / cm 3 to about 0.285 g / cm 3 , about 0.225 g / cm 3 to about 0.280 g / cm 3 , about 0.230 g / cm 3 to about 0.275 g / cm 3 , about 0.235 g / cm 3 to about 0.270 g / cm 3 , about 0.240 g / cm 3 to about 0.265 g / cm 3 , about 0.245 g / cm 3 to about 0.260 g / cm3 from about 0.250 g / cm 3 to about 0.260 g / cm 3 , or from about 0.255 g / cm 3 .

[0324] The density of the superabsorbent layer can be at least about 0.200 g / cm 3 , at least about 0.205 g / cm 3 , at least about 0.210 g / cm 3 , at least about 0.215 g / cm 3 , at least about 0.220 g / cm 3 , at least about 0.225 g / cm 3 , at least about 0.230 g / cm 3 , at least about 0.235 g / cm 3 , at least about 0.240 g / cm 3 , at least about 0.245 g / cm 3 , at least about 0.250 g / cm 3 , at least about 0.255 g / cm 3 , at least about 0.260 g / cm 3 , at least about 0.265 g / cm 3 , at least about 0.270 g / cm 3 , at least about 0.275 g / cm 3 , at least about 0.280 g / cm 3 , at least about 0.285 g / cm 3 , at least about 0.290 g / cm 3 , at least about 0.295 g / cm 3 , at least about 0.300 g / cm 3 , or at least about 0.305 g / cm 3 .

[0325] The density of the superabsorbent layer can be at least about 0.200 g / cm 3 , at least about 0.205 g / cm 3 , at least about 0.210 g / cm 3 , at least about 0.215 g / cm 3 , at least about 0.220 g / cm 3 , at least about 0.225 g / cm 3 , at least about 0.230 g / cm 3 , at least about 0.235 g / cm 3 , at least about 0.240 g / cm 3 , at least about 0.245 g / cm 3 , at least about 0.250 g / cm3 at least about 0.255 g / cm 3 at least about 0.260 g / cm 3 at least about 0.265 g / cm 3 at least about 0.270 g / cm 3 at least about 0.275 g / cm 3 at least about 0.280 g / cm 3 at least about 0.285 g / cm 3 at least about 0.290 g / cm 3 at least about 0.295 g / cm 3 at least about 0.300 g / cm 3 or at least about 0.305 g / cm 3 .

[0326] The density of the superabsorbent layer can be no more than about 0.200 g / cm 3 no more than about 0.205 g / cm 3 no more than about 0.210 g / cm 3 no more than about 0.215 g / cm 3 no more than about 0.220 g / cm 3 no more than about 0.225 g / cm 3 no more than about 0.230 g / cm 3 no more than about 0.235 g / cm 3 no more than about 0.240 g / cm 3 no more than about 0.245 g / cm 3 no more than about 0.250 g / cm 3 no more than about 0.255 g / cm 3 no more than about 0.260 g / cm 3 no more than about 0.265 g / cm 3 no more than about 0.270 g / cm 3 no more than about 0.275 g / cm 3 no more than about 0.280 g / cm 3 no more than about 0.285 g / cm 3 no more than about 0.290 g / cm 3 no more than about 0.295 g / cm 3 no more than about 0.300 g / cm 3 or no more than about 0.305 g / cm 3 .

[0327] The tensile strength of the superabsorbent layer (in dry condition) can be from about 30 N / 50mm to about 60 N / 50mm, from about 35 N / 50mm to about 55 N / 50mm, from about 40 N / 50mm to about 50 N / 50mm, or about 45 N / 50mm.

[0328] The tensile strength of the superabsorbent layer (in dry condition) can be about 30 N / 50mm, about 35 N / 50mm, about 40 N / 50mm, about 45 N / 50mm, about 50 N / 50mm, about 55 N / 50mm, or about 60 N / 50mm.

[0329] The tensile strength of the superabsorbent layer (in dry condition) can be at least about 30 N / 50mm, at least about 35 N / 50mm, at least about 40 N / 50mm, at least about 45 N / 50mm, at least about 50 N / 50mm, at least about 55 N / 50mm, or at least about 60 N / 50mm.

[0330] The tensile strength of the superabsorbent layer (in dry condition) can be no more than about 30 N / 50mm, no more than about 35 N / 50mm, no more than about 40 N / 50mm, no more than about 45 N / 50mm, no more than about 50 N / 50mm, no more than about 55 N / 50mm, or no more than about 60 N / 50mm.

[0331] Advantageously, a superabsorbent layer having a tensile strength as described above means that the superabsorbent layer is flexible and conforms well to the body contours of the patient at the wound site when in use.

[0332] The tensile strength of the superabsorbent layer can be increased by increasing the amount of hot melt binder present in the superabsorbent layer. The tensile strength of the superabsorbent layer can be decreased by decreasing the amount of hot melt binder present in the superabsorbent layer.

[0333] The absorbency capacity of the superabsorbent layer can be from about 15 grams per gram per 10 minutes to about 35 grams per gram per 10 minutes, from about 17.5 grams per gram per 10 minutes to about 32.5 grams per gram per 10 minutes, from about 20 grams per gram per 10 minutes to about 30 grams per gram per 10 minutes, from about 22.5 grams per gram per 10 minutes to about 27.5 grams per gram per 10 minutes, or about 25 grams per gram per 10 minutes.

[0334] Advantageously, the absorbency capacity of the superabsorbent layer can be from about 15 grams per gram per 10 minutes to about 35 grams per gram per 10 minutes, in particular about 25 grams per gram per 10 minutes, which means that the superabsorbent layer absorbs about 1 g / cm 2 This is much more advantageous than the absorbent layers used in known wound dressings.

[0335] The absorbent capacity of the superabsorbent layer can be about 15 grams per gram per 10 minutes, about 17.5 grams per gram per 10 minutes, about 20 grams per gram per 10 minutes, about 22.5 grams per gram per 10 minutes, about 25 grams per gram per 10 minutes, about 27.5 grams per gram per 10 minutes, about 30 grams per gram per 10 minutes, about 32.5 grams per gram per 10 minutes, or about 35 grams per gram per 10 minutes.

[0336] The absorbent capacity of the superabsorbent layer can be at least about 15 grams per gram per 10 minutes, at least about 17.5 grams per gram per 10 minutes, at least about 20 grams per gram per 10 minutes, at least about 22.5 grams per gram per 10 minutes, at least about 25 grams per gram per 10 minutes, at least about 27.5 grams per gram per 10 minutes, at least about 30 grams per gram per 10 minutes, at least about 32.5 grams per gram per 10 minutes, or at least about 35 grams per gram per 10 minutes.

[0337] The absorbent capacity of the superabsorbent layer can be no more than about 15 grams per gram per 10 minutes, no more than about 17.5 grams per gram per 10 minutes, no more than about 20 grams per gram per 10 minutes, no more than about 22.5 grams per gram per 10 minutes, no more than about 25 grams per gram per 10 minutes, no more than about 27.5 grams per gram per 10 minutes, no more than about 30 grams per gram per 10 minutes, no more than about 32.5 grams per gram per 10 minutes, or no more than about 35 grams per gram per 10 minutes.

[0338] The absorbent capacity of the superabsorbent layer can be measured using the Liquid Handling Direct Immersion Technique as follows:

[0339] GSM

[0340] a. Cut the sample to be tested into a 5 cm x 5 cm square (A1 = 25 cm 2 );

[0341] b. Weigh each sample in grams;

[0342] c. Calculate:

[0343]

[0344] Liquid Handling

[0345] a. Place the dressing test piece into a filter paper bag and weigh the sample in grams (W1);

[0346] b. Add 40 times the weight of the sample in a warm (37°C ± 1°C) hydration fluid (Solution A);

[0347] c. Incubate for 30 (± 1) minutes at 37°C (± 2°C);

[0348] d. Using tweezers, remove the sample and empty filter paper bag from the incubator and hang (hold one corner of the filter paper bag) on the petri dish for 30 seconds;

[0349] e. Re-weigh the sample (W2);

[0350] f. Repeat the above steps with 3 empty filter paper bags for calculating the average fluid uptake of the filter paper bags and subtract from the hydrated sample weight;

[0351] g. Calculate:

[0352]

[0353] Fluid Retention

[0354] a. Using tweezers, remove the sample from the balance as per step (e) above and lay flat on a dry perforated stainless steel plate;

[0355] b. Immediately cover the wet sample with a weight of 40 mm of mercury (a 5 x 5 cm weight is 1359.51 grams);

[0356] c. Let stand for 1 minute and then remove the weight;

[0357] d. Remove the sample from the perforated plate and weigh (W3);

[0358] e. Repeat the above steps with empty filter paper bags for calculating the average fluid retention of the filter paper bags and subtract from the sample weight;

[0359] f. Calculate:

[0360]

[0361] The compression under absorbency / absorbent capacity / absorbency of the superabsorbent layer can be from about 0.50 g / cm 2 to about 1.20 g / cm 2 , from about 0.55 g / cm 2 to about 1.15 g / cm 2 , from about 0.60 g / cm 2 to about 1.10 g / cm 2 , from about 0.65 g / cm 2 to about 1.05 g / cm 2 , from about 0.70 g / cm 2 to about 1.00 g / cm 2 , from about 0.75 g / cm 2 to about 0.95 g / cm 2 , from about 0.80 g / cm 2To approximately 0.90 g / cm 2 or approximately 0.85 g / cm³ 2 .

[0362] The compressible absorption capacity of the superabsorbent layer can be approximately 0.50 g / cm³. 2 Approximately 0.55 g / cm³ 2 Approximately 0.60 g / cm 2 Approximately 0.65 g / cm³ 2 Approximately 0.70 g / cm³ 2 Approximately 0.75 g / cm³ 2 Approximately 0.80 g / cm 2 Approximately 0.85 g / cm³ 2 Approximately 0.90 g / cm³ 2 Approximately 0.95 g / cm³ 2 Approximately 1.00 g / cm³ 2 Approximately 1.05 g / cm³ 2 Approximately 1.10 g / cm³ 2 Approximately 1.15 g / cm³ 2 or approximately 1.20 g / cm³ 2 .

[0363] The compressible absorption capacity of the superabsorbent layer can be at least about 0.50 g / cm³. 2 At least approximately 0.55 g / cm 2 At least approximately 0.60 g / cm 2 At least approximately 0.65 g / cm³ 2 At least approximately 0.70 g / cm 2 At least approximately 0.75 g / cm³ 2 At least approximately 0.80 g / cm 2 At least approximately 0.85 g / cm 2 At least approximately 0.90 g / cm 2 At least approximately 0.95 g / cm 2 At least approximately 1.00 g / cm 2 At least approximately 1.05 g / cm³ 2 At least approximately 1.10 g / cm³ 2 At least approximately 1.15 g / cm³ 2 or at least about 1.20 g / cm 2 .

[0364] The absorption capacity of the superabsorbent layer under compression may not exceed approximately 0.50 g / cm³. 2 Not exceeding approximately 0.55 g / cm 2 Not exceeding approximately 0.60 g / cm 2, not more than about 0.65 g / cm 2 , not more than about 0.70 g / cm 2 , not more than about 0.75 g / cm 2 , not more than about 0.80 g / cm 2 , not more than about 0.85 g / cm 2 , not more than about 0.90 g / cm 2 , not more than about 0.95 g / cm 2 , not more than about 1.00 g / cm 2 , not more than about 1.05 g / cm 2 , not more than about 1.10 g / cm 2 , not more than about 1.15 g / cm 2 , or not more than about 1.20 g / cm 2 .

[0365] The absorbency / absorptive capacity under compression can be measured using the following test:

[0366] 1. Cut the sample to be tested into 5 cm x 5 cm squares (A1 = 25 cm 2 ) (test samples);

[0367] 2. Place the test samples into filter paper bags and weigh each bag; record the weight in grams (W1);

[0368] 3. Place the test samples on a dry stainless steel perforated plate and then place a weight equivalent to 80 mm of mercury on each test sample;

[0369] 4. Repeat the above steps with three empty filter bags;

[0370] 5. Add enough hydration fluid (Solution A) to cover the stainless steel perforated plate at a temperature of 20 °C ± 2 °C and leave for 24 hours at a temperature of 20 °C ± 2 °C;

[0371] 6. Drain the hydration fluid (Solution A) and remove the combined weight;

[0372] 7. Remove the test samples with tweezers and weigh immediately (W2);

[0373] 8. Place the test samples on a dry stainless steel perforated plate and then place a weight equivalent to 80 mm of mercury on the test samples so that the load is evenly applied over the entire test sample surface;

[0374] 9. Leave for 15 minutes;

[0375] 10. Weigh the test samples again in grams (W3);

[0376] 11. Repeat the above steps with 3 empty filter paper bags for calculating the average fluid retained by the filter paper bags and subtracting it from the weight of the sample after hydration;

[0377] 12. Calculate:

[0378] a. The weight of solution absorbed per gram of sample: (W2 - W1) / W1 g / g

[0379] b. The weight of fluid retained per gram of sample: (W3 - W1) / W1 g / g

[0380] c. Fluid absorbed per unit area: (W2 - W1) / A1 g / cm 2

[0381] d. Retention per unit area: (W3 - W1) / A1 g / cm 2

[0382] e. The percentage of fluid immobilized: (W3 / W2) x 100.

[0383] The above test simulates the expected structural compression when a -80 mm Hg negative pressure is applied to a wound site, which is a typical pressure used in negative pressure wound dressings.

[0384] Advantageously, the superabsorbent layer having the above compression under absorption values sufficiently absorbs fluid (i.e., wound exudate) from a wound site such that the superabsorbent layer maintains an optimal environment for wound healing at the wound site.

[0385] The superabsorbent layer can be any shape, such as circular, oval, triangular, square, rectangular, hexagonal, or octagonal, or any irregular shape. Each layer of the absorbent structure can have the same or substantially the same shape.

[0386] The superabsorbent layer can be planar, or substantially planar.

[0387] The superabsorbent layer can comprise a plurality of superabsorbent layers, each layer comprising an upper layer and a lower layer that together enclose / encapsulate a first material comprising nonwoven fibers, absorbent material, and hot melt binder. Each layer of the plurality of superabsorbent layers can be identical. The plurality of superabsorbent layers can be disposed adjacent to each other within the absorbent structure of the wound dressing. The plurality of superabsorbent layers can comprise two, three, four, five, six, seven, eight, nine, or more superabsorbent layers.

[0388] The absorbent structure can comprise a transmission layer.

[0389] In embodiments comprising a superabsorbent layer, the transmission layer can be disposed between the wound contact layer and the superabsorbent layer.

[0390] The absorbent structure can comprise a first surface and a second surface. The first surface of the absorbent structure can be adjacent to and in contact with the second surface of the adhesive skin contact layer. The second surface of the absorbent structure can be adjacent to and in contact with the first surface of the backing layer.

[0391] The first surface of the absorbent structure can be the first surface of any layer of the absorbent structure, for example the first surface of the wound contact layer, the transmission layer or the superabsorbent layer. In particular, the first surface of the absorbent structure can be the first surface of the wound contact layer.

[0392] The wound contact layer can comprise a first surface and a second surface. In use, the first surface can face inwards towards the patient's body, while the second surface can face outwards away from the patient's body. The first surface of the wound contact layer can contact the wound when the wound dressing is adhered to the skin in the vicinity of the wound, i.e. when in use. The second surface of the wound contact layer can be adjacent to and in contact with the first surface of the transmission layer or the superabsorbent layer.

[0393] The transmission layer can comprise a first surface and a second surface. In use, the first surface can face inwards towards the patient's body, while the second surface can face outwards away from the patient's body. The first surface of the transmission layer can be adjacent to and in contact with the second surface of the wound contact layer or the second surface of the superabsorbent layer. The second surface of the transmission layer can be adjacent to and in contact with the first surface of the superabsorbent layer or the first surface of the backing layer.

[0394] The superabsorbent layer can comprise a first surface and a second surface. In use, the first surface can face inwards towards the patient's body, while the second surface can face outwards away from the patient's body. The first surface of the superabsorbent layer can be adjacent to and in contact with the second surface of the wound contact layer or the second surface of the transmission layer. The second surface of the superabsorbent layer can be adjacent to and in contact with the first surface of the transmission layer or the first surface of the backing layer.

[0395] The adhesive skin contact layer can provide an adhesive boundary. Advantageously, this means that the adhesive skin contact layer readily allows the wound dressing to be releasably adhered to the skin surface around the wound, rather than directly to the wound, which can cause discomfort to the user.

[0396] The adhesive skin contact layer can be configured to releasably adhere the dressing to the skin surface around the wound.

[0397] The adhesive skin contact layer can comprise a window. Advantageously, the window allows the adhesive skin contact layer to be adhered around the wound such that the wound site is located within the window, thus allowing the patient's wound to be in contact or fluid communication with, for example and preferably the wound contact layer, when the wound dressing is applied to the patient's skin.

[0398] The adhesive skin contact layer can overlap the absorbent structure. The adhesive skin contact layer can comprise an inner portion and an outer portion located radially outward of the inner portion. In use, the inner portion and the outer portion of the first surface can contact the skin of the patient and adhere to the skin of the patient. The inner portion of the second surface of the adhesive skin contact layer can be adjacent to and in contact with a portion of the first surface of the absorbent structure, in particular a portion of the first surface of the wound contact layer of the absorbent structure. The outer portion of the second surface of the adhesive skin contact layer can be adjacent to and in contact with a portion of the first surface of the backing layer. Advantageously, this helps to prevent the overflow of wound exudate from the confines of the wound dressing, which is unhygienic and can cause discomfort to the user. Furthermore, this also helps to maintain negative pressure at the wound site.

[0399] Each of the wound contact layer, the transport layer and the superabsorbent layer can be laminated together. Advantageously, this means that the manufacture of the absorbent structure of the present invention does not require any relatively rigid dressings and joining components. Thus, the present invention provides an absorbent structure which is flexible, thus beneficial to the comfort of the user, and which is less costly to manufacture than the absorbent structures of the prior art and negative pressure wound dressings. Furthermore, lamination does not require any complex equipment or manufacturing techniques. Thus, the present invention is easy to manufacture.

[0400] The at least two of the wound contact layer, the transport layer and the superabsorbent layer can be laminated by a laminator having a heating zone temperature of from about 50°C to about 200°C, from about 60°C to about 190°C, from about 70°C to about 180°C, from about 80°C to about 170°C, from about 90°C to about 160°C, from about 100°C to about 150°C, from about 110°C to about 140°C, from about 120°C to about 130°C, or of about 125°C.

[0401] The at least two of the wound contact layer, the transport layer and the superabsorbent layer can be laminated by a laminator having a heating zone temperature of from about 50°C, from about 60°C, from about 70°C, from about 80°C, from about 90°C, from about 100°C, from about 110°C, from about 120°C, from about 130°C, from about 140°C, from about 150°C, from about 160°C, from about 170°C, from about 180°C, from about 190°C, or from about 200°C.

[0402] The at least two of the wound contact layer, the transport layer and the superabsorbent layer can be laminated by a laminator having a heating zone temperature of at least about 50°C, at least about 60°C, at least about 70°C, at least about 80°C, at least about 90°C, at least about 100°C, at least about 110°C, at least about 120°C, at least about 130°C, at least about 140°C, at least about 150°C, at least about 160°C, at least about 170°C, at least about 180°C, at least about 190°C, or at least about 200°C.

[0403] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator, the heating zone temperature of the laminator can be no more than about 50°C, no more than about 60°C, no more than about 70°C, no more than about 80°C, no more than about 90°C, no more than about 100°C, no more than about 110°C, no more than about 120°C, no more than about 130°C, no more than about 140°C, no more than about 150°C, no more than about 160°C, no more than about 170°C, no more than about 180°C, no more than about 190°C, or no more than about 200°C.

[0404] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator, the heating zone temperature of the laminator can be about 0°C to about 50°C, about 5°C to about 45°C, about 10°C to about 40°C, about 15°C to about 35°C, about 20°C to about 30°C, or about 25°C.

[0405] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator, the cooling zone temperature of the laminator can be about 0°C, about 5°C, about 10°C, about 15°C, about 20°C, about 25°C, about 30°C, about 35°C, about 40°C, about 45°C, or about 50°C.

[0406] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator, the cooling zone temperature of the laminator can be at least about 0°C, at least about 5°C, at least about 10°C, at least about 15°C, at least about 20°C, at least about 25°C, at least about 30°C, at least about 35°C, at least about 40°C, at least about 45°C, or at least about 50°C.

[0407] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator, the cooling zone temperature of the laminator can be no more than about 0°C, no more than about 5°C, no more than about 10°C, no more than about 15°C, no more than about 20°C, no more than about 25°C, no more than about 30°C, no more than about 35°C, no more than about 40°C, no more than about 45°C, or no more than about 50°C.

[0408] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator with a web tension (for each unwound spool) of about 0 N to about 250 N, about 10 N to about 240 N, about 20 N to about 230 N, about 30 N to about 220 N, about 40 N to about 210 N, about 50 N to about 200 N, about 60 N to about 190 N, about 70 N to about 180 N, about 80 N to about 170 N, about 90 N to about 160 N, about 100 N to about 150 N, about 110 N to about 140 N, about 120 N to about 130 N, or about 125 N.

[0409] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator with a web tension (for each unwound spool) of about 0 N, about 10 N, about 20 N, about 30 N, about 40 N, about 50 N, about 60 N, about 70 N, about 80 N, about 90 N, about 100 N, about 110 N, about 120 N, about 130 N, about 140 N, about 150 N, about 160 N, about 170 N, about 180 N, about 190 N, about 200 N, about 210 N, about 220 N, about 230 N, about 240 N, or about 250 N.

[0410] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator with a web tension (for each unwound spool) of at least about 0 N, at least about 10 N, at least about 20 N, at least about 30 N, at least about 40 N, at least about 50 N, at least about 60 N, at least about 70 N, at least about 80 N, at least about 90 N, at least about 100 N, at least about 110 N, at least about 120 N, at least about 130 N, at least about 140 N, at least about 150 N, at least about 160 N, at least about 170 N, at least about 180 N, at least about 190 N, at least about 200 N, at least about 210 N, at least about 220 N, at least about 230 N, at least about 240 N, or at least about 250 N.

[0411] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator with a web tension (for each unwound spool) of no more than about 0 N, no more than about 10 N, no more than about 20 N, no more than about 30 N, no more than about 40 N, no more than about 50 N, no more than about 60 N, no more than about 70 N, no more than about 80 N, no more than about 90 N, no more than about 100 N, no more than about 110 N, no more than about 120 N, no more than about 130 N, no more than about 140 N, no more than about 150 N, no more than about 160 N, no more than about 170 N, no more than about 180 N, no more than about 190 N, no more than about 200 N, no more than about 210 N, no more than about 220 N, no more than about 230 N, no more than about 240 N, or no more than about 250 N.

[0412] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator with a nip roller pressure of about 10 N, about 25 N, about 50 N, about 75 N, about 100 N, about 125 N, about 150 N, about 175 N, about 200 N, about 225 N, about 250 N, about 275 N, about 300 N, about 325 N, about 350 N, about 375 N, about 400 N, about 425 N, about 450 N, about 475 N, about 500 N, about 525 N, about 550 N, about 575 N, about 600 N, about 625 N, about 650 N, about 675 N, about 700 N, about 725 N, about 750 N, about 775 N, about 800 N, about 825 N, about 850 N, about 875 N, about 900 N, about 925 N, about 950 N, about 975 N, or about 1000 N.

[0413] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator having a pressure roller pressure of at least about 10 N, at least about 25 N, at least about 50 N, at least about 75 N, at least about 100 N, at least about 125 N, at least about 150 N, at least about 175 N, at least about 200 N, at least about 225 N, at least about 250 N, at least about 275 N, at least about 300 N, at least about 325 N, at least about 350 N, at least about 375 N, at least about 400 N, at least about 425 N, at least about 450 N, at least about 475 N, at least about 500 N, at least about 525 N, at least about 550 N, at least about 575 N, at least about 600 N, at least about 625 N, at least about 650 N, at least about 675 N, at least about 700 N, at least about 725 N, at least about 750 N, at least about 775 N, at least about 800 N, at least about 825 N, at least about 850 N, at least about 875 N, at least about 900 N, at least about 925 N, at least about 950 N, at least about 975 N, or at least about 1000 N.

[0414] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator having a pressure roller pressure of no more than about 10 N, no more than about 25 N, no more than about 50 N, no more than about 75 N, no more than about 100 N, no more than about 125 N, no more than about 150 N, no more than about 175 N, no more than about 200 N, no more than about 225 N, no more than about 250 N, no more than about 275 N, no more than about 300 N, no more than about 325 N, no more than about 350 N, no more than about 375 N, no more than about 400 N, no more than about 425 N, no more than about 450 N, no more than about 475 N, no more than about 500 N, no more than about 525 N, no more than about 550 N, no more than about 575 N, no more than about 600 N, no more than about 625 N, no more than about 650 N, no more than about 675 N, no more than about 700 N, no more than about 725 N, no more than about 750 N, no more than about 775 N, no more than about 800 N, no more than about 825 N, no more than about 850 N, no more than about 875 N, no more than about 900 N, no more than about 925 N, no more than about 950 N, no more than about 975 N, or no more than about 1000 N.

[0415] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator at a web speed of about 1 m / min, about 2 m / min, about 3 m / min, about 4 m / min, about 5 m / min, about 6 m / min, about 7 m / min, about 8 m / min, about 9 m / min, or about 10 m / min.

[0416] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator at a web speed of at least about 1 m / min, at least about 2 m / min, at least about 3 m / min, at least about 4 m / min, at least about 5 m / min, at least about 6 m / min, at least about 7 m / min, at least about 8 m / min, at least about 9 m / min, or at least about 10 m / min.

[0417] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator at a web speed of no more than about 1 m / min, no more than about 2 m / min, no more than about 3 m / min, no more than about 4 m / min, no more than about 5 m / min, no more than about 6 m / min, no more than about 7 m / min, no more than about 8 m / min, no more than about 9 m / min, or no more than about 10 m / min.

[0418] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator at a web speed of about 5 m / min, about 10 m / min, about 15 m / min, about 20 m / min, about 25 m / min, about 30 m / min, about 35 m / min, about 40 m / min, about 45 m / min, or about 50 m / min when the laminator is not in operation.

[0419] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated by a laminator at a web speed of at least about 5 m / min, at least about 10 m / min, at least about 15 m / min, at least about 20 m / min, at least about 25 m / min, at least about 30 m / min, at least about 35 m / min, at least about 40 m / min, at least about 45 m / min, or at least about 50 m / min when the laminator is not in operation.

[0420] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated together by a lamination machine, when the lamination machine is not in operation, the web speed of the lamination machine is no more than about 5 m / min, no more than about 10 m / min, no more than about 15 m / min, no more than about 20 m / min, no more than about 25 m / min, no more than about 30 m / min, no more than about 35 m / min, no more than about 40 m / min, no more than about 45 m / min, or no more than about 50 m / min.

[0421] The at least two of the wound contact layer, the transmission layer, and the superabsorbent layer can be laminated together by a dispersion coated adhesive. The dispersion coated adhesive can be a hot melt dispersion coated adhesive.

[0422] The dispersion coated adhesive can be polylactic acid, polycaprolactone, polyethylene (LDPE, HDPE), polypropylene, polyester, polyamide, ethylene vinyl acetate, or polyurethane. Advantageously, each of these materials is inexpensive and readily available.

[0423] The melt flow index of the dispersion coated adhesive can range from about 5.2 grams / 10 minutes to about 11.3 grams / 10 minutes when tested with a 2.16 kilogram, 1 inch PVC die at 160 °C.

[0424] The maximum moisture content of the dispersion coated adhesive can be about 0.25% to about 0.45%, about 0.30% to about 0.40%, or about 0.35%. The maximum moisture content of the dispersion coated adhesive can be about 0.25%, about 0.30%, about 0.35%, about 0.40%, or about 0.45%.

[0425] The dispersion coated adhesive can have a maximum moisture content of at least about 0.25%, about 0.30%, about 0.35%, about 0.40%, or at least about 0.45%.

[0426] The dispersion coated adhesive can have a maximum moisture content of no more than about 0.25%, about 0.30%, about 0.35%, about 0.40%, or no more than about 0.45%.

[0427] The dispersion coated adhesive can include particles, at least 98% of the particles having a particle size of less than 600 pm, as measured by DIN EN ISO 4610.

[0428] The dispersion coated adhesive can include particles, at least 98% of the particles having a particle size of about 0.05 mm to about 0.80 mm, about 0.06 mm to about 0.75 mm, about 0.07 to about 0.70 mm, about 0.08 mm to about 0.65 mm, about 0.09 mm to about 0.60 mm, or about 0.10 mm to about 0.60 mm.

[0429] The dispersion-coated adhesive can include particles, at least 98% of the particles having a particle size of at most about 0.1 mm, at most about 0.2 mm, at most about 0.3 mm, at most about 0.4 mm, at most about 0.5 mm, or at most about 0.6 mm.

[0430] The dispersion-coated adhesive can include particles, at least 98% of the particles having a particle size of at least about 0.1 mm, at least about 0.2 mm, at least about 0.3 mm, at least about 0.4 mm, at least about 0.5 mm, or at least about 0.6 mm.

[0431] The dispersion-coated adhesive can include particles, at least 98% of the particles having a particle size of at most about 0.1 mm, at most about 0.2 mm, at most about 0.3 mm, at most about 0.4 mm, at most about 0.5 mm, or at most about 0.6 mm.

[0432] The dispersion-coated adhesive can have an average molecular weight of about 35,000 g / mol to about 65,000 g / mol, about 40,000 g / mol to about 60,000 g / mol, about 45,000 g / mol to about 55,000 g / mol, or about 50,000 g / mol.

[0433] The dispersion-coated adhesive can have an average molecular weight of about 35,000 g / mol, about 40,000 g / mol, about 45,000 g / mol, about 50,000 g / mol, about 55,000 g / mol, about 60,000 g / mol, or about 65,000 g / mol.

[0434] The dispersion-coated adhesive can have a melting point of about 55°C to about 65°C, or about 58°C to about 62°C, or about 60°C.

[0435] The dispersion-coated adhesive can have a solubility parameter of 9.30 calories per cubic centimeter (cal / cm 3 ) to 9.45 cal / cm 3 , for example, 9.34 cal / cm 3 to 9.43 cal / cm 3 .

[0436] The wound contact layer can be stitched to the transmission layer or the superabsorbent layer. The wound contact layer can be stitched to a layer of the absorbent structure that is adjacent to and contacts the second surface of the wound contact layer. In particular, the wound contact layer can be stitched to the transmission layer, which advantageously increases the bond strength between the wound contact layer and the transmission layer. More advantageously, the stitching process provides a plurality of apertures in the stitched layer that facilitate the application of negative pressure to the wound site.

[0437] As described herein, these advantageous effects are particularly advantageous in embodiments in which the wound contact layer comprises Hydrofiber (RTM) available from ConvaTec Limited of Deeside, United Kingdom or sodium carboxymethyl cellulose fibers having a degree of substitution of from about 0.05 carboxymethyl groups per glucose unit to about 0.50 carboxymethyl groups per glucose unit.

[0438] The transmission layer can be laminated or stitched to the wound contact layer on the first surface and laminated or stitched to the superabsorbent layer on the second surface.

[0439] The transmission layer can be disposed between the wound contact layer and the superabsorbent layer. Advantageously, this arrangement increases the absorbent capacity of the wound dressing and increases the amount of vapor transmitted by the wound dressing.

[0440] The transmission layer can be laminated to the wound contact layer on the first surface and laminated to the superabsorbent layer on the second surface. Advantageously, this means that the transmission layer adheres to the wound contact layer and the superabsorbent layer without the use of relatively rigid dressing and joining components. Thus, the manufacture of the absorbent structure is cheaper and simpler compared to the prior art and provides a flexible, and thus more comfortable, wound dressing.

[0441] The transmission layer can have a thickness of from about 1.0 mm to about 5.0 mm, from about 1.5 mm to about 4.5 mm, from about 2.0 mm to about 4.0 mm, from about 2.5 mm to about 3.5 mm, or about 30 mm.

[0442] The transmission layer can have a thickness of about 1.0 mm, about 1.5 mm, about 2.0 mm, about 2.5 mm, about 3.0 mm, about 3.5 mm, about 4.0 mm, about 4.5 mm, or about 5.0 mm.

[0443] The transmission layer can have a thickness of at least about 1.0 mm, at least about 1.5 mm, at least about 2.0 mm, at least about 2.5 mm, at least about 3.0 mm, at least about 3.5 mm, at least about 4.0 mm, at least about 4.5 mm, or at least about 5.0 mm.

[0444] The transmission layer can have a thickness of not more than about 1.0 mm, not more than about 1.5 mm, not more than about 2.0 mm, not more than about 2.5 mm, not more than about 3.0 mm, not more than about 3.5 mm, not more than about 4.0 mm, not more than about 4.5 mm, or not more than about 5.0 mm.

[0445] Advantageously, as described above, the relatively thin dimension of the transmission layer provides a wound dressing having a reduced thickness compared to prior art wound dressings. Thus, the wound dressing of the present application is flatter than many known wound dressings and is therefore more comfortable to the user than known wound dressings having a greater thickness.

[0446] The transmission layer can be formed from a polyurethane foam, a polyester foam, a hydrophilic polyurethane, a polysilicone, a gelatin, a polypropylene, a nitrile, or an EVA foam.

[0447] The transmission layer can have a density of from about 24 Kg / M 3 to about 30 Kg / M 3 , or from about 26 Kg / M 3 to about 28 Kg / M 3 .

[0448] The transmission layer can have a tensile strength of at least about 150 kPa, at least about 160 kPa, at least about 170 kPa, at least about 180 kPa, at least about 190 kPa, at least about 200 kPa, at least about 210 kPa, at least about 220 kPa, at least about 230 kPa, at least about 240 kPa, or at least about 250 kPa.

[0449] The transmission layer can have an elongation at break value of at least about 300%, at least about 310%, at least about 320%, at least about 330%, at least about 340%, at least about 350%, at least about 360%, at least about 370%, at least about 380%, at least about 390%, or at least about 400%.

[0450] The transmission layer can have a compression set / compression permanent set of 50% up to 100%.

[0451] The transmission layer can have a foam cell count of from 17 cells / cm to 26 cells / cm.

[0452] The transmission layer can have a 40% CLD (Compressive Load Deflection) hardness of from 2.5 kPa to 4.5 kPa.

[0453] The superabsorbent layer can include any one or more optional or other features of the present application according to any other aspect.

[0454] The wound contact layer can include any one or more features of the present application according to any other aspect, optional or otherwise.

[0455] Advantageously, in embodiments comprising a transmission layer disposed between the wound contact layer and the superabsorbent layer, particularly in embodiments wherein the wound contact layer comprises sodium carboxymethyl cellulose fibers having a degree of substitution of from about 0.05 carboxymethyl groups per glucose unit to about 0.50 carboxymethyl groups per glucose unit, the wound dressing of the present application prevents or at least significantly reduces lateral spreading of wound exudate at the wound contact layer. In this way, wound exudate is initially wicked upward through the wound contact layer and then spreads laterally across the transmission layer before being absorbed by the superabsorbent layer. Thus, improved wicking and movement of fluid away from the wound site is provided. Beneficially, this arrangement is more effective at removing wound exudate from the wound site, thus, making the wound site more sanitary and increasing the comfort of the user. More advantageously, this arrangement increases the ability of the wound dressing to transport vapour, thus, facilitating evaporation of fluids contained in the wound exudate.

[0456] In some embodiments, the wound dressing can describe an additional layer, for example a pressure dispersion layer, also known as a pressure distribution layer, which is used to distribute pressure or negative pressure laterally across the pressure dispersion layer. The pressure dispersion layer can be gas, liquid and moisture permeable and helps wound exudate reach a greater portion of the dressing by distributing negative pressure laterally across the dressing. In this way, the absorption of wound exudate by the dressing is maximised and the more uniform delivery of negative pressure to the wound or dressing is optimised. The pressure dispersion layer can be formed from a foam such as a polyester foam or a polyurethane foam.

[0457] According to a second aspect of the present application there is provided a method of manufacturing a negative pressure wound dressing, the method comprising the steps of:

[0458] a. providing an adhesive skin contact layer and a backing layer;

[0459] b. providing a wound contact layer and an absorbent structure, the absorbent structure comprising a transmission layer and a superabsorbent layer, wherein the wound contact layer comprises an antimicrobial agent, the antimicrobial agent comprising silver ions; and

[0460] c. disposing the absorbent structure between the wound contact layer and the backing layer.

[0461] The negative pressure wound dressing can be a negative pressure wound dressing according to the first aspect of the present application.

[0462] The present application according to this second aspect can of course include any one or more of the optional or other features of the present application according to the first and third aspects.

[0463] According to a third aspect of the present application there is provided a negative pressure wound exudate management system comprising a wound dressing of the general or first aspect and further comprising:

[0464] a negative pressure source; and

[0465] a conduit or tube for providing negative pressure to the wound dressing through an internal lumen of the conduit or tube and a hole in the wound dressing.

[0466] The negative pressure source can comprise a pump for generating negative pressure, and the conduit can connect the pump with the wound dressing.

[0467] The negative pressure source can be capable of generating a pressure of a minimum of 40 mm of mercury and a maximum of 200 mm of mercury, for example 125 mm of mercury, at the wound site.

[0468] The negative pressure source can further comprise a one-way valve in series between the pump and the wound dressing to maintain negative pressure within the wound dressing when the pump is disconnected from the conduit. Normal operation of the pump can comprise generating negative pressure, generating negative pressure in alternating cycles and / or not generating negative pressure.

[0469] The one-way valve can be connected to one of the pump and the conduit.

[0470] The conduit or tube can comprise a proximal end having an opening. The proximal end of the conduit or tube can be attached / adhered around the opening in the wound dressing backing layer such that the opening in the backing layer is in fluid communication with the opening in the proximal end of the conduit or tube. The attachment between the proximal end of the conduit or tube and the opening in the backing layer can form an air-tight or substantially air-tight seal between the conduit or tube and the backing layer.

[0471] The application according to the third aspect can of course include any one or more optional or other features of the application according to any preceding aspect.

[0472] According to a fourth aspect of the application there is provided a method of using a negative pressure wound dressing, the method comprising:

[0473] a. providing a negative pressure wound dressing, a negative pressure source and a conduit or tube for providing negative pressure to the wound dressing through an internal lumen of the conduit or tube;

[0474] b. connecting the conduit at a first end to the negative pressure source and at a second end to a port or airway in a backing layer of the negative pressure wound dressing;

[0475] c. securing the negative pressure wound dressing to the skin around the wound;

[0476] d. activating the negative pressure source to apply negative pressure to the wound.

[0477] The negative pressure wound dressing can comprise an adhesive skin contact layer. In step (c) the adhesive skin contact layer can be used to secure the wound dressing to the skin around the wound.

[0478] The negative pressure wound dressing can be a negative pressure wound dressing according to the first aspect.

[0479] The application according to the fourth aspect can of course include any one or more optional or other features of the application according to any of the preceding aspects. BRIEF DESCRIPTION OF DRAWINGS

[0480] For a more complete understanding of the present application, one or more embodiments thereof, reference is now made to the following descriptions taken in connection with the accompanying drawings in which:

[0481] Figure 1 is an exploded view of a first embodiment of a negative pressure wound dressing;

[0482] Figure 2 is a schematic view of a wound exudate management system according to some embodiments;

[0483] Figure 3 is a schematic view showing the apparatus for performing Assessment 1 ;

[0484] Figure 4 is a graph showing total viable cell counts for Example 1 ;

[0485] Figure 5 is a graph showing total viable cell counts for Example 2;

[0486] Figure 6 is a graph showing total viable cell counts for Example 3;

[0487] Figure 7 is a graph showing total viable cell counts for Example 4;

[0488] Figure 8 is a graph showing total viable cell counts for Example 5;

[0489] Figure 9 is a graph showing total viable cell counts for Example 6;

[0490] Figure 10 is a graph showing total viable cell counts for Example 7;

[0491] Figure 11 is a graph showing total viable cell counts for Example 8;

[0492] Figure 12 is a graph showing total viable cell counts for Example 9;

[0493] Figure 13 is a graph showing total viable cell counts for Example 10;

[0494] Figure 14 is a graph showing total viable cell counts for Example 11 ;

[0495] Figure 15 is a graph showing total viable cell counts for a polycarbonate test sample of Example 12;

[0496] Figure 16 is a graph showing the total viable cell count for the wound dressing of Example 12;

[0497] Figure 17 is a graph showing the total viable cell count for the polycarbonate sample of Example 13;

[0498] Figure 18 is a graph showing the total viable cell count for the wound dressing of Example 13;

[0499] Figure 19 is a graph showing the total viable cell count for the polycarbonate sample of Example 14; and

[0500] Figure 20 is a graph showing the total viable cell count for the wound dressing of Example 14. DETAILED DESCRIPTION

[0501] Referring to Figure 1 a negative pressure wound dressing 1 is shown.

[0502] The wound dressing 1 comprises an adhesive skin contact layer 20, a wound contact layer 4, a transmission layer 5, a superabsorbent layer 6, a backing layer 7 and a gas conduit 8.

[0503] The adhesive skin contact layer 20 can have a perimeter shape with a central window 9, and thus the adhesive skin contact layer 20 can be an adhesive skin contact border layer 20. The border layer 20 can comprise an outer perimeter defining an outer shape of the border layer 20, which in this embodiment is a square shape. The border layer 20 can comprise an inner perimeter defining a shape of the window 9. The window 9 can have the same or similar shape as the outer perimeter of the border layer 20.

[0504] The window 9 is a square shaped through hole in the adhesive skin contact layer 20. The window 9 is centrally / centrally located with respect to the perimeter of the adhesive skin contact layer 20. Each edge of the window 9 is arranged parallel to each respective edge of the adhesive skin contact layer 20. The area of the window can be 12,500 mm 2 A person skilled in the art will appreciate that the window 9 can be enlarged by any suitable means, for example by cutting the adhesive skin contact layer 20. The window 9 in the adhesive skin contact layer 20 enables a wound of a patient to be in contact or fluid communication with other layers of the wound dressing 1, for example the wound contact layer 4, when the wound dressing 1 is applied to the skin of the patient.

[0505] Adhesive skin contact layer 20 includes an upper surface 20b and a lower surface 20a. Lower surface 20a contacts a skin surface in use. In use, lower surface 20a of adhesive skin contact layer 20 is detachably adhered to a skin surface (not shown) of a patient such that a wound site (not shown) is located within window 9. In this way, adhesive skin contact layer 20 does not come into direct contact with the wound site, but rather completely surrounds the wound site. Thus, adhesive skin contact layer 20 only comes into contact with the skin surrounding the intact wound. Upper surface 20b can face outward away from the patient’s body.

[0506] A removable cover or “release layer” (not shown) can be attached to lower surface 20a of adhesive skin contact layer 20. The removable cover, which can include a folded grip section, can be removed from lower surface 20a of adhesive skin contact layer 20. Thus, when the removable cover is attached to adhesive skin contact layer 20, the removable cover protects adhesive skin contact layer 20, but when the removable cover is removed from lower surface 20a of adhesive skin contact layer 20 to use wound dressing 1, lower surface 20a is exposed and enables wound dressing 1 to be releasably secured to the skin of a patient.

[0507] Wound contact layer 4, transmission layer 5, and superabsorbent layer 6 form an absorbent structure arranged between adhesive skin contact layer 20 and backing layer 7.

[0508] Backing layer 7 can include a first surface 7a and a second surface 7b. In use, first surface 7a can face inward toward the patient’s body, while second surface 7b can face outward away from the patient’s body.

[0509] Absorbent structure 4, 5, 6 can include a first surface 4a and a second surface 6b. First surface 4a of absorbent structure 4, 5, 6 can be adjacent to and in contact with upper surface 20b of adhesive skin contact layer 20. An outer peripheral edge of second surface 6b of absorbent structure 4, 5, 6 can be adjacent to and in contact with first surface 7a of backing layer 7.

[0510] Wound contact layer 4 can include a first surface 4a and a second surface 4b. In use, first surface 4a can face inward toward the patient’s body, while second surface 4b can face outward away from the patient’s body. First surface 4a of wound contact layer 4 can contact a wound when wound dressing 1 is adhered to the skin near the wound (i.e., when in use). First surface 4a of wound contact layer 4 is substantially aligned with window 9 of adhesive skin contact layer 20. In this way, in use, first surface 4a contacts a wound through window 9. Second surface 4b of wound contact layer 4 can be adjacent to and in contact with first surface 5a of transmission layer 5 or first surface 6a of superabsorbent layer 6. In the described embodiment, second surface 4b of wound contact layer 4 is adjacent to and in contact with first surface 5a of transmission layer 5.

[0511] The transmission layer 5 can include a first surface 5a and a second surface 5b. In use, the first surface 5a can face inward toward the patient's body, while the second surface 5b can face outward away from the patient's body. The first surface 5a of the transmission layer 5 can be adjacent to and in contact with the second surface 4b of the wound contact layer 4 or the second surface 6b of the superabsorbent layer 6. The second surface 5b of the transmission layer 5 can be adjacent to and in contact with the first surface 6a of the superabsorbent layer 6 or the first surface 7a of the backing layer 7. In the described embodiment, the first surface 5a of the transmission layer 5 is adjacent to and in contact with the second surface 4b of the wound contact layer, and the second surface 5b of the transmission layer 5 is adjacent to and in contact with the first surface 6a of the superabsorbent layer 6.

[0512] The superabsorbent layer 6 can include a first surface 6a and a second surface 6b. In use, the first surface 6a can face inward toward the patient's body, while the second surface 6b can face outward away from the patient's body. The first surface 6a of the superabsorbent layer 6 can be adjacent to and in contact with the second surface 4b of the wound contact layer 4 or the second surface 5b of the transmission layer 5. The second surface 6b of the superabsorbent layer 6 can be adjacent to and in contact with the first surface 5a of the transmission layer 5 or the first surface 7a of the backing layer 7. In the described embodiment, the first surface 6a of the superabsorbent layer 6 is adjacent to and in contact with the second surface 5b of the transmission layer 5, and the second surface 6b of the superabsorbent layer 6 is adjacent to and in contact with the first surface 7a of the backing layer 7.

[0513] The adhesive skin contact layer 20 can overlap the absorbent structure 4, 5, 6 in a radial direction. The adhesive skin contact layer 20 can include an inner portion adjacent and surrounding the window 9 and an outer portion located radially outward of the inner portion. In use, the inner portion and the outer portion of the first surface 20a of the adhesive skin contact layer 20 can contact and adhere to the patient's skin. The inner portion of the second surface 20b of the adhesive skin contact layer 20 can be adjacent to and in contact with a portion of the first surface 4a of the wound contact layer 4. The outer portion of the second surface 20b of the adhesive skin contact layer 20 can be adjacent to and joined to a peripheral portion of the first surface 7a of the backing layer 7. Advantageously, this helps to prevent the escape of wound exudate from the confines of the wound dressing, which is unhygienic and can cause discomfort to the user. Furthermore, this also helps to maintain negative pressure at the wound site.

[0514] The outer portion of the second surface 20b of the adhesive skin contact layer 20 can be joined to the peripheral portion of the first surface 7a of the backing layer 7 by heat lamination, adhesion, fusion, or stitching.

[0515] The outer portion of the second surface 20b of the adhesive skin contact layer 20 can extend radially beyond the outer periphery of the absorbent structure by about 27.5 mm.

[0516] At least two of the wound contact layer 4, the transmission layer 5 and the superabsorbent layer 6 can be laminated together. In the described embodiment, each of the wound contact layer 4, the transmission layer 5 and the superabsorbent layer 6 are laminated together. Advantageously, this means that the manufacture of the absorbent structure of the present invention does not require any relatively rigid dressings and joining components. Thus, the present invention provides an absorbent structure which is flexible, thus beneficial for the comfort of the user, and which is less costly to manufacture than prior art absorbent structures and thus negative pressure wound dressings. Furthermore, lamination does not require any complex equipment or manufacturing techniques. Thus, the present invention is easy to manufacture.

[0517] Each of the wound contact layer 4, the transmission layer 5 and the superabsorbent layer 6 can be laminated together by a dispersion coated adhesive. The dispersion coated adhesive can be a hot melt dispersion coated adhesive. In the described embodiment, the dispersion coated adhesive is polycaprolactone and has the following properties:

[0518] - a melt flow index in the range of 5.2 g / 10 min to 11.3 g / 10 min, tested at 160 °C with a 2.16 kg, 1 inch PVC die;

[0519] - a maximum moisture content of 0.35%;

[0520] - an average molecular weight of 50,000;

[0521] - a melting point of 60 °C; and

[0522] - a solubility parameter of 9.34 cal / cm 3 to 9.43 cal / cm 3 .

[0523] The dispersion coated adhesive can comprise particles, at least 98% of the particles having a particle size of 0.6 mm.

[0524] The wound contact layer 4, the transmission layer 5 and the superabsorbent layer 6 can be laminated together by a laminator having the following processing properties:

[0525] - a heating zone temperature of 125 °C;

[0526] - a cooling zone temperature of 25 °C;

[0527] - a web tension of 125 N (for each unwound reel);

[0528] - a crushing roller pressure of 1000 N; and

[0529] - a web speed of 10 m / min.

[0530] The wound contact layer 4 can further comprise a central region 4c and a peripheral region 4d. The central region 4c can be substantially square shaped and can be bounded on each side by the peripheral region 4d.

[0531] In the described embodiment, the first surface 4a, which in use contacts the wound, can comprise warp stitches only (longitudinal to the plane of the wound contact layer 4), i.e. the first surface 4a does not comprise any weft stitches (transverse to the plane of the wound contact layer 4). Advantageously, this means that the amount of non-gelling fibres (which can comprise weft stitches) at the wound contact surface is minimised. Thus, the ratio of gelling fibres to non-gelling fibres is greater at the wound contact surface which is in contact with the wound and thus the wound exudate. As a result, the absorbent capacity of the wound contact layer is increased. In this way, the pooling of wound exudate at the wound site is prevented or at least significantly reduced and the optimal environment for wound healing is maintained at the wound site.

[0532] The warp stitches of the first surface 4a can have a pitch of 6.6 mm and a stitch density of 7.5 stitches per cm.

[0533] The second surface 4b, which is laminated to the first surface 5a of the transmission layer 5, can comprise warp stitches and weft stitches. The warp stitches and weft stitches of the second surface 4b can each have a pitch of 6.6 mm and a stitch density of 7.5 stitches per cm.

[0534] In a number of other embodiments, the central region 4c of the first surface 4a can comprise warp stitches only, while the peripheral region 4d of the first surface 4a can comprise warp stitches and weft stitches.

[0535] The wound contact layer 4 can have a thickness of 3.0 mm.

[0536] The wound contact layer 4 can comprise two layers (layers not shown in the Figures). Each layer can be substantially square shaped and have a thickness of about 1.5 mm. Each layer can be substantially planar. Each layer can be formed from a plurality of gel-forming fibres, which in the present embodiment are sodium carboxymethylcellulose fibres. The sodium carboxymethylcellulose fibres can have a degree of substitution of about 0.30 carboxymethyl groups per glucose unit, as measured by infrared spectroscopy (as defined in WO 00 / 01425). Each layer can have a basis weight of about 100 g / m 2 The antimicrobial agent comprising silver ions can be dispersed on the sodium carboxymethylcellulose fibres of each layer of the wound contact layer 4. The silver ions can be present in the antimicrobial agent at a concentration of about 1.20 wt.%. The two layers can be stitched together at the periphery of each layer with lyocell yarn (produced under the trade name Tencel TM yarn.

[0537] The layers can be arranged such that the first surface 4a of the wound contact layer 4 is the first surface of the first layer and the second surface 4b of the wound contact layer 4 is the second surface of the second layer. The second surface of the first layer and the first surface of the second layer can be arranged against each other. Thus, the two layers form a wound contact layer having a total basis weight of 200 g / m2 2

[0538] The sodium carboxymethyl cellulose fibers are hygroscopic fibers which turn gelatinous upon absorption of wound exudate. The sodium carboxymethyl cellulose fibers can be of the type which maintain their structural integrity upon absorption of exudate.

[0539] The absence of weft stitches at the first surface 4a means that a larger amount of gel-forming fibers (as described above) are exposed at the first surface and thus in contact with the wound. In this way, the present wound contact layer has a higher gelling capacity compared to the gel-forming fibers of the prior art, i.e. has a significantly greater absorption capacity and a stronger holding force. In this way, the wound contact layer 4 absorbs a larger amount of wound exudate. Thus, the pooling of wound exudate at the wound site is prevented or at least significantly reduced.

[0540] The sodium carboxymethyl cellulose fibers are prepared by carboxymethylation of a nonwoven cellulose fabric having an absorbency of 18 g / g solution A (sodium chloride / calcium chloride solution) measured by the method described in BS EN 13726-1 (2002) “Test methods for primary wound dressings”, section 3.2 “Free swell absorptive capacity”. Carboxymethylation is carried out by contacting the fabric with a base and a carboxymethylation agent such as chloroacetic acid in a mixed system of alcohol and water. The cellulose fabric comprises only cellulose fibers and comprises a continuous filament yarn.

[0541] The gel-forming fibers have an absorbency of 2 g of 0.9% saline solution per g of fiber (measured by the free swell method).

[0542] The wound contact layer can further comprise an anti-biofilm agent. The anti-biofilm agent can comprise ethylenediaminetetraacetic acid (EDTA). In a number of further embodiments, the anti-biofilm agent can comprise a salt of EDTA, such as the disodium or calcium disodium salt, or a combination of EDTA and one or more salts thereof. The EDTA can be present in an amount of about 2.0 wt.%.

[0543] The anti-biofilm agent can further comprise a quaternary ammonium surfactant. In the present embodiment, the quaternary ammonium surfactant is benzalkonium chloride. The benzalkonium chloride can be present in an amount of about 0.75 wt.%.

[0544] ​The antimicrobial agent can also comprise a buffer, which in the present embodiment can be citric acid.

[0545] In the present embodiment, the wound contact layer 4 does not comprise any silicone, i.e. comprises 0 wt.% of silicone.

[0546] The transmission layer 5 is substantially square, as are the wound contact layer 4 and the superabsorbent layer 6, and has a thickness of 1.8 mm and is made of polyurethane foam. The transmission layer 5 can have a density in the range of 26 Kg / M 3 to 28 Kg / M 3 and a tensile strength of 150 kPa. The transmission layer 5 has a value of elongation at break of 300% and a number of foam cells of 17 cells / cm to 26 cells / cm. Furthermore, the transmission layer 5 has a 40% CLD hardness of 2.5 kPa to 4.5 kPa.

[0547] The superabsorbent layer 6 comprises an upper layer having a second surface 6b and a lower layer having a first surface 6a. Between the upper layer and the lower layer, a first material comprising nonwoven fibers, absorbent material and hot melt binder is encapsulated.

[0548] The hot melt binder can be present in an amount of 70 g / m 2 . The hot melt binder can be a copolymer and in the described embodiment can be an ethylene-vinyl acetate copolymer (EVA). In the manufacture of the superabsorbent layer, the superabsorbent layer can be heated to melt the hot melt binder and bind the nonwoven fibers of the first material together. Advantageously, this prevents or at least significantly limits the amount of shedding of fibers of the superabsorbent layer in use. Thus, the presence of the hot melt binder in the superabsorbent layer significantly increases the strength of this layer, preventing the disintegration / separation of the absorbent structure.

[0549] The absorbent material can be a superabsorbent material, which is capable of absorbing wound exudate while allowing fluid to pass therethrough. The superabsorbent material can be sodium polyacrylate and be in powder form, which advantageously increases the ratio of surface area to volume of the superabsorbent material, thus enhancing the absorbent properties of the material.

[0550] The nonwoven fibers can be cellulose fibers. The cellulose nonwoven fibers can be arranged in a cellulose nonwoven matrix of fibers and can be a carrier onto which the absorbent material can be bound, e.g. in the described embodiment, the absorbent material is dispersed on the cellulose nonwoven matrix. The absorbent material can be dispersed evenly or substantially evenly throughout or on the nonwoven fibers, e.g. the cellulose nonwoven matrix.

[0551] The upper layer and the lower layer of the superabsorbent layer 6 can each be a cellulose fabric layer. The upper fabric layer and the lower fabric layer can be joined around their entire periphery to enclose / encapsulate the first material.

[0552] The superabsorbent layer 6 may include multiple openings (not shown). Each of the multiple openings may be a slit-like opening in the superabsorbent layer 6. The length of each opening may be equal to 80% of the length of the superabsorbent layer 6. Each of the upper and lower layers may include multiple openings. The openings may be arranged in a direction that is planar with and transverse to the longitudinal axis of the superabsorbent layer 6. Advantageously, this arrangement helps to manage the flow of exudate through the superabsorbent layer 6 of the wound dressing 1. The openings facilitate or enable the wound exudate to move laterally rather than axially on the superabsorbent layer 6 and facilitate the transmission of negative pressure through the superabsorbent layer 6.

[0553] Superabsorbent layer 6 can have 460 g / m 2 The basis weight, 2.55 mm thickness, and 0.255 g / cm³ 3 The density. Furthermore, the superabsorbent layer 6 can have a tensile strength of 45 N / 50 mm (in dry conditions), an absorption capacity of 25 g / g per 10 minutes, and a density of 0.85 g / cm³. 2 Absorbance capacity / absorbency under compression.

[0554] Each of the wound contact layer 4, transport layer 5, and superabsorbent layer 6 is essentially planar.

[0555] In use, the adhesive skin contact layer 20 adheres to the intact skin surrounding the wound. The wound is located within the window 9 of the adhesive skin contact layer 20. Before or after applying the dressing to the wound, the wound dressing 1 is connected to a negative pressure source. Upon leaving the wound, wound exudate contacts the first surface 4a of the wound contact layer 4 and is wicked upward toward the transport layer 5 away from the wound site. The high gelling capacity of the wound contact layer 4 facilitates the absorption and retention of wound exudate. An antimicrobial agent containing silver ions provides an antimicrobial effect at the wound site. The lamination of the wound contact layer 4, the transport layer 5, and the superabsorbent layer 6 means that each of these layers forms a reinforced absorption and retention structure. Wound exudate is wicked from the upper surface 4b of the wound contact layer 4 to the transport layer 5. Lateral movement of the exudate occurs in the transport layer 5 to disperse the wound exudate across the surface area of ​​the dressing. Then, the exudate is drawn upwards into the superabsorbent layer 6, where it is absorbed and retained before being transported out of the dressing 1 via vapor transport through the backing membrane 7.

[0556] Reference Figure 2wherein a negative pressure wound exudate management system 400 according to certain embodiments is shown. The negative pressure wound exudate management system 400 comprises a pump 410 for generating negative pressure, a wound dressing 420 (which can be the above described wound dressing 1) for covering and protecting a wound (not shown), an in-line / on-line filter 430, a first pressure tube 440 having a first inner lumen 442, a second pressure tube 450 having a second inner lumen 452 (which can be the above described air conduit 8), and a flexible connector 460. The first pressure tube 440 is arranged between the pump 410 and the on-line filter 430. The second pressure tube 450 is arranged between the on-line filter 430 and the flexible connector 460. The first pressure tube 440 and / or the second pressure tube 450 can comprise a one-way valve (not shown) (i.e. in-line / serially between the pump 410 and the wound dressing 420) to maintain negative pressure within the wound dressing 420 when the pump 410 is disconnected from the first and / or second pressure tube 440, 450. The flexible connector 460 is arranged between the second pressure tube 450 and a backing layer of the wound dressing 420. The backing layer comprises an aperture (not shown) and the flexible connector 460 is sealingly connected 480 to the backing layer around the perimeter of the aperture, e.g. by adhesive or a weld line, such that the pump 410 and the wound dressing 420 are in fluid communication via the inner lumina 442, 452.

[0557] The following evaluations were performed to demonstrate the antimicrobial efficacy of the negative pressure wound dressings according to the present application.

[0558] Evaluation 1 - Wound contact layer comprising an antimicrobial agent comprising silver ions

[0559] To demonstrate the antimicrobial efficacy of the negative pressure wound dressings according to the present application, as Figure 3 An apparatus was arranged as schematically illustrated in

[0560] Apparatus comprising a negative pressure wound dressing according to the present application

[0561] The apparatus comprises a negative pressure wound dressing 100, which is described above and illustrated in Figure 1The wound dressing 1 shown in FIG. 1 is the same. In particular, the wound dressing 100 is a negative pressure wound dressing 1 that includes a wound contact layer 4 having two layers. Each layer is substantially square in shape and has a thickness of about 1.5 millimeters. Each layer is substantially planar. Each layer is formed from a plurality of gel-forming fibers that are sodium carboxymethyl cellulose fibers. The sodium carboxymethyl cellulose fibers have a degree of substitution of about 0.30 carboxymethyl groups per glucose unit as measured by infrared spectroscopy (as defined in WO 00 / 01425). Each layer has a basis weight of about 100 grams per square meter. An antimicrobial agent comprising silver ions is dispersed on the sodium carboxymethyl cellulose fibers of each layer of the wound contact layer 4. The silver ions are present in the antimicrobial agent at a concentration of about 1.20 wt.%. The two layers are stitched together at the periphery of each layer with lyocell yarn (produced under the trade name Tencel®). TM The wound dressing 100 is stitched to the upper surface 210 of the test apparatus 200 by its adhesive skin contact layer. The test apparatus 200 includes four feet 300 attached to its lower surface 220 to provide a stable and flat surface for the wound dressing 100. The lower surface 220 of the test apparatus 200 includes a fluid inlet 400 to which a tube 850 is attached, the tube 850 having a syringe 800 at its distal end.

[0562] The wound contact layer also includes an anti-biofilm agent comprising a chelating agent. The chelating agent comprises about 2.0 wt.% of ethylenediaminetetraacetic acid (EDTA).

[0563] The anti-biofilm agent also includes a quaternary cationic surfactant. The quaternary cationic surfactant is benzalkonium chloride. The benzalkonium chloride is present in an amount of about 0.75 wt.%.

[0564] The antimicrobial agent also includes a buffering agent, which is citric acid.

[0565] The wound contact layer does not include any silicone, i.e., the wound contact layer includes 0 wt.% of silicone.

[0566] Other features of the wound dressing 100 are as described above and as shown in Figure 1 FIG. 1.

[0567] The wound dressing 100 is attached to the upper surface 210 of the test apparatus 200 by its adhesive skin contact layer. The test apparatus 200 includes four feet 300 attached to its lower surface 220 to provide a stable and flat surface for the wound dressing 100. The lower surface 220 of the test apparatus 200 includes a fluid inlet 400 to which a tube 850 is attached, the tube 850 having a syringe 800 at its distal end.

[0568] The pump 900 provides a source of negative pressure to the wound dressing 100 through the internal lumen of the conduit 950, which is attached to the air conduit (not shown) of the wound dressing 100.

[0569] Simulated wound fluid (SWF) is used to simulate wound exudate, which is a fluid consisting of equal parts of Maximum Recovery Diluent (MRD) and Fetal Bovine Serum (FBS). The composition of MRD and FBS is known in the art. SWF is pumped from syringe 800 to fluid inlet 400 at a rate of 0.898 ml per hour.

[0570] A 53 millimeter deep well 500 is used to simulate a wound site. Well 500 includes an agar plate 600 populated with challenge microorganisms. Agar plate 600 simulates a wound surface. Filter paper 700 is placed in a generally central location on the agar plate surface. In the evaluation, filter paper 700 is the medium in which bacterial growth is examined.

[0571] Comparative device

[0572] A comparative device is provided that includes the features of the above-described device, but differs in that the wound contact layer of the wound dressing does not contain an antimicrobial agent. Thus, the wound contact layer of the wound dressing of the comparative device does not contain any silver ions.

[0573] Evaluation

[0574] Wound dressing 100 is pre-conditioned with SWF for 7 days. At this time, well 500 is not inserted into test apparatus 200, so there are no challenge bacteria in contact with wound dressing 100.

[0575] After pre-conditioning, filter paper 700 is inoculated with 1 x 10 6 CFU / 10 μl of challenge microorganisms, as described below.

[0576] Well 500 is attached to the lower surface 220 of test apparatus 200 under a generally central portion of wound dressing 100, so that inoculated filter paper 700 is in contact with the wound contact layer of the wound dressing.

[0577] The device is incubated, and SWF is pumped to wound dressing 100 to represent a moderately exuding wound, while negative pressure is applied by activating pump 900. The negative pressure at the simulated wound site is 125 millimeters of mercury.

[0578] From the start of incubation, the total viable cell count of microorganisms present on filter paper 700 is taken at 0, 6, 24, 48, and 168 hours.

[0579] The acceptable "pass" standard established by regulatory agencies (e.g., the Food and Drug Administration (FDA) in the United States) is a 4-log reduction in total viable cell count within 48 hours of incubation.

[0580] Microorganisms

[0581] Individual tests were performed using different microorganisms: Pseudomonas aeruginosa NCTC 8506 (antibiotic resistant) (bacteria), Staphylococcus aureus ATCC BAA-1556 (MRSA) (bacteria) and Candida krusei NCPF 3876 (yeast).

[0582] Preparation of each agar plate 600:

[0583] - Preparation of a working suspension of about 1 x 10 8 CFU / ml in maximum recovery diluent using representative colonies of the challenge microorganism;

[0584] - Placing a TSA + 3% AB (bacterial agar) agar disc on top of the blotting paper in the test rig 200;

[0585] - Placing a 25mm Whatman filter paper on the agar disc and inoculating 10μl of working suspension (about 1 x 10 6 CFU / 10μl).

[0586] Analysis

[0587] Example 1

[0588] In this example, filter papers of both a device according to the application (wound contact layer comprising an antimicrobial agent comprising 1.20 wt.% silver ions) and a comparative device (wound contact layer not comprising an antimicrobial agent) were inoculated with Pseudomonas aeruginosa NCTC 8506 (antibiotic resistant) bacteria.

[0589] As shown in Figure 4 , the wound dressing of the application resulted in a sharp reduction in the total viable cell count of the bacteria after inoculation. Within 24 hours of inoculation, the total viable cell count of P. Aeruginosa NCTC 8506 was reduced by 4 log orders. From 24 hours after incubation to the completion of the test at 7 days (168 hours), the total viable cell count of P. Aeruginosa NCTC 8506 remained reduced by 4 log orders.

[0590] In contrast, Comparative Example 1, which did not comprise an antimicrobial agent, allowed the total viable cell count of P. Aeruginosa NCTC 8506 bacteria to increase by about 3 log orders (3-log) within 24 hours of incubation. The comparative example did not achieve a 4 log order reduction in total viable cell count after 48 hours of incubation.

[0591] Example 2

[0592] In this embodiment, filter paper from both the device comprising the wound contact layer according to the invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) and the control device (the wound contact layer does not contain an antimicrobial agent) was inoculated with Staphylococcus aureus ATCC BAA-1556 (MRSA) (MRSA ATCC BAA-1556).

[0593] like Figure 5 As shown, the wound dressing of the present invention resulted in a sharp reduction in the total number of viable bacterial cells after culture. Within 6 hours of culture, the total number of viable MRSA ATCC BAA-1556 decreased by 4 logarithmic orders. This 4 logarithmic reduction in the total number of viable MRSA ATCC BAA-1556 remained from 6 hours after culture until the completion of the test at 7 days (168 hours).

[0594] In contrast, Comparative Example 2, which did not contain antimicrobial agents, increased the total number of viable MRSA ATCCBAA-1556 bacteria by approximately three log units during a 48-hour culture period. This comparative example did not achieve the four log units reduction in the total number of viable cells after 48 hours of culture.

[0595] It is worth noting that Example 2 shows that the negative pressure wound dressing according to the present invention is more effective in eliminating MRSA ATCC BAA-1556 compared with the P. aeruginosa NCTC 8506 bacteria used in Example 1.

[0596] Example 3

[0597] In this embodiment, filter paper from both the device comprising the wound contact layer according to the invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) and the control device (the wound contact layer does not contain an antimicrobial agent) was inoculated with Candida krusei NCPF 3876 yeast.

[0598] like Figure 6 As shown, the wound dressing of the present invention resulted in a reduction in the total viable cell count of yeast after culture. Within 24 hours of culture, the total viable cell count of C. krusei NCPF 3876 decreased by four logarithmic orders. From 24 hours post-culture until the completion of the test at 7 days (168 hours), the total viable cell count of C. krusei NCPF 3876 maintained a reduction of four logarithmic orders.

[0599] In contrast, Comparative Example 3, which did not contain antimicrobial agents, allowed an increase in the total viable cell count of *C. krusei* NCPF 3876 yeast from the start of culture to approximately 48 hours. Comparative Example 3 did not achieve a four-log reduction in the total viable cell count after 48 hours of culture.

[0600] Conclusion

[0601] It has been found that for each of the three types of microorganisms tested, the negative pressure wound dressing according to the present invention provides a reduction of 4 logarithmic orders of the total number of viable cells of each bacteria within 48 hours of incubation.

[0602] The advantages of the present invention over negative pressure wound dressings having a wound contact layer not comprising an antimicrobial agent comprising silver ions are clearly shown in Examples 1-3.

[0603] The following evaluations were performed to demonstrate the antimicrobial activity of the negative pressure wound dressing according to the present invention against bacteria, yeast and mould.

[0604] Evaluation 2 - In vitro direct inoculation simulated wound fluid model

[0605] An in vitro direct inoculation simulated wound fluid model (based on adapted AATCC TM100 - Test for antimicrobial activity of textile products) has been used to evaluate the antimicrobial activity of the negative pressure wound dressing according to the present invention against bacteria, yeast and mould.

[0606] SUMMARY

[0607] As described below, a plurality of wound contact layers comprised in the negative pressure wound dressing of the present invention, as well as a plurality of samples of wound contact layers forming experimental controls, were prepared, pre-treated to simulate clinical conditions, and each sample was challenged with bacteria, yeast or mould.

[0608] METHOD

[0609] Microorganisms

[0610] Different microorganisms were used for separate tests: Vancomycin resistant Enterococcus faecalis NCTC 12201, Methicillin resistant Staphylococcus aureus ATCC® BAA-1556ᵀᴹ (MRSA), Staphylococcus pyogenes NCTC 10872, Acinetobacter baumannii NCTC 13421, ESBL producing Klebsiella pneumoniae NCTC 13465, Antibiotic resistant Pseudomonas aeruginosa NCTC 8506, Aspergillus brasiliensis NCPF® 2275 and Candida krusei NCPF® 3876.

[0611] Sample preparation

[0612] Samples of the negative pressure wound dressing according to the present invention of 4 cm x 4 cm were prepared. In each sample, the wound contact layer comprised two layers. The two layers were made of Lyocell yarn (under the trade name Tencel®) and polyurethane foam, respectively. The wound contact layer of the negative pressure wound dressing according to the present invention was prepared as described in Example 1. TMThe yarn production) are stitched together at the periphery of each layer. Each layer is substantially square in shape and has a thickness of about 1.5 millimetres. Each layer is substantially planar. Each layer is formed from a plurality of gel-forming fibres, which are sodium carboxymethylcellulose fibres. The sodium carboxymethylcellulose fibres have a degree of substitution of about 0.30 carboxymethyl groups per glucose unit, as measured by infrared spectroscopy (as defined in WO 00 / 01425). The basis weight of each layer is about 100 grams per square metre. An antimicrobial agent comprising silver ions is dispersed on the sodium carboxymethylcellulose fibres of each sample of the wound contact layer. The silver ions are present in the antimicrobial agent at a concentration of about 1.20 wt.%. The wound contact layer does not comprise any silicone, i.e. the wound contact layer comprises 0 wt.% silicone.

[0613] Another sample of a negative pressure wound dressing was prepared as described above, but the wound contact layer of this sample did not comprise silver ions. This sample formed a control for the experiment.

[0614] Each sample was transferred to a sterile container. Each sample (n=3) was then hydrated with 11.99 millilitres of simulated wound fluid (SWF) (50:50 Maximum Recovery Diluent (MRD): foetal bovine serum) and incubated at 35 ± 3 °C for 168 hours.

[0615] A working suspension of about 1 x 10 8 cfu / ml was prepared in MRD using representative colonies of the challenge organism. After incubation for 168 hours (pre-treatment), samples were inoculated with about 1 x 10 6 cfu and incubated again until their appropriate time point (0, 24, 48, 72, 96 and 168 hours).

[0616] At each time point, the appropriate samples were transferred to a stomach bag containing 40 ml of DENB and homogenised in the laboratory stomach bag at "high speed" for 4 minutes. Total viable counts (TVCs) were performed on the resulting suspension. Samples were incubated for at least 48 hours at 35 ± 3 °C (or 20-25 °C for A. brasiliensis NCPF 2275 and C. krusei NCPF 3876).

[0617] To determine the antimicrobial activity, the log reduction was calculated as follows:

[0618] Log reduction = log of control initial challenge level - log of challenge organism at specified timepoint 10 - log of challenge organism at specified timepoint 10 .

[0619] The accepted "pass" criteria established by regulatory agencies, such as the U.S. Food and Drug Administration (FDA), is a 4-log reduction in total viable cell count within 48 hours of incubation for bacteria, and 168 hours (7 days) for yeast and mold.

[0620] Analysis

[0621] Example 4

[0622] In this example, both the negative pressure wound dressing of the present application (wound contact layer comprising an antimicrobial agent comprising 1.20 wt.% silver ions) (Example 4) and a comparative example (experimental control without silver ions) were inoculated with vancomycin-resistant Enterococcus faecalis NCTC 12201 (E. faecalis NCTC 12201).

[0623] As shown in Table 2, the negative pressure wound dressing of the present application resulted in a sharp reduction in total viable cell count of vancomycin-resistant E. faecalis NCTC 12201 within 24 hours. The 4-log reduction in total viable cell count of vancomycin-resistant NCTC 12201 was maintained from 24 hours after incubation to 7 days (168 hours) of testing completion. Figure 7 In contrast, Comparative Example 4 (experimental control without silver ions) increased the total viable cell count of vancomycin-resistant NCTC 12201 by 2 orders of magnitude over the 24-hour incubation period. This comparative example did not achieve a 4-log reduction in total viable cell count after 48 hours of incubation.

[0624] Example 5

[0625] In this example, both the negative pressure wound dressing of the present application (wound contact layer comprising an antimicrobial agent comprising 1.20 wt.% silver ions) (Example 5) and a comparative example (experimental control without silver ions) were inoculated with methicillin-resistant Staphylococcus aureus ATCC® BAA-1556ᵀᴹ (MRSA).

[0626] As shown in Table 3, Example 5 resulted in a reduction in total viable cell count of methicillin-resistant Staphylococcus aureus ATCC® BAA-1556ᵀᴹ (MRSA), reaching a 4-log reduction by about 48 hours after incubation. The total viable cell count of methicillin-resistant Staphylococcus aureus ATCC® BAA-1556ᵀᴹ (MRSA) was further reduced as time increased, and the total viable cell count maintained at least a 4-log reduction prior to completion of the 7-day (168 hours) test.

[0627] Figure 8

[0628] ​​In contrast, Comparative Example 5 (experimental control), which did not contain silver ions, increased the total number of viable methicillin-resistant Staphylococcus aureus (MRSA) ATCC® BAA-1556ᵀᴹ by 3 logs during a 24-hour culture period. Comparative Example 5 did not achieve the 4 log reduction in the total number of viable cells after 48 hours of culture.

[0629] Example 6

[0630] In this embodiment, both the negative pressure wound dressing of the present invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) (Example 6) and the comparative example (an experimental control without silver ions) were inoculated with Staphylococcus pyogenes NCTC 10872.

[0631] like Figure 9 As shown, Example 6 resulted in a sharp decrease in the total viable cell count of Staphylococcus pyogenes NCTC 10872 within 24 hours. The four-log reduction in the total viable cell count of Staphylococcus pyogenes NCTC 10872 persisted from 24 hours post-culture until the test was completed at 7 days (168 hours).

[0632] In contrast, Comparative Example 6 (experimental control), which did not contain silver ions, allowed an increase in the total viable cell count of Staphylococcus aureus NCTC 10872 within 24 hours of culture. The total viable cell count in Comparative Example 6 did indeed decrease to culture levels at 48 hours and remained essentially constant during the test period, with a slight decrease at 168 hours. This comparative example did not achieve the four logarithmic reduction in total viable cell count after 48 hours of culture.

[0633] Example 7

[0634] In this embodiment, both the negative pressure wound dressing of the present invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) (Example 7) and the comparative example (experimental control example without silver ions) were inoculated with Acinetobacter baumannii NCTC13421.

[0635] like Figure 10 As shown, Example 7 resulted in a sharp decrease in the total viable cell count of Acinetobacter baumannii NCTC 13421 within 24 hours. The decrease in the total viable cell count of Acinetobacter baumannii NCTC 13421 by four logarithmic orders remained from 24 hours post-culture until the test was completed at 7 days (168 hours).

[0636] In contrast, Comparative Example 7 (experimental control), which did not contain silver ions, increased the total number of viable Acinetobacter baumannii NCTC 13421 cells by 3 logs within 24 hours of culture. Comparative Example 7 did not achieve the 4 log-order reduction in the total number of viable cells after 48 hours of culture.

[0637] Example 8

[0638] In this embodiment, both the negative pressure wound dressing of the present invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) (Example 8) and the comparative example (an experimental control without silver ions) were inoculated with ESBL-producing Klebsiella pneumoniae NCTC 13465.

[0639] like Figure 11 As shown, Example 8 resulted in a sharp decrease in the total viable cell count of ESBL-producing Klebsiella pneumoniae NCTC 13465 within 24 hours. From 24 hours post-culture to the completion of the test at 7 days (168 hours), the total viable cell count of ESBL-producing Klebsiella pneumoniae NCTC 13465 maintained a decrease of 4 logarithmic orders.

[0640] In contrast, Comparative Example 8 (experimental control), which did not contain silver ions, increased the total number of viable ESBL-producing Klebsiella pneumoniae NCTC 13465 cells by three logs within 24 hours of culture. Comparative Example 8 did not achieve the four log-order reduction in the total number of viable cells after 48 hours of culture.

[0641] Example 9

[0642] In this embodiment, both the negative pressure wound dressing of the present invention (the wound contact layer contains an antimicrobial agent containing 1.20 wt.% silver ions) (Example 9) and the comparative example (an experimental control without silver ions) were inoculated with antibiotic-resistant Pseudomonas aeruginosa NCTC 8506.

[0643] like Figure 12 As shown, Example 9 resulted in a sharp decrease in the total viable number of antibiotic-resistant Pseudomonas aeruginosa NCTC 8506 cells within 24 hours. From 24 hours post-culture to the completion of the test at 7 days (168 hours), the total viable number of antibiotic-resistant Pseudomonas aeruginosa NCTC 8506 cells maintained a decrease of 4 logarithmic orders.

[0644] In contrast, Comparative Example 9 (experimental control) without silver ions allowed a 3-log increase in the total number of antibiotic-resistant Pseudomonas aeruginosa NCTC 8506 cells after 24 hours of culture, and a 4-log increase after 48 hours. Comparative Example 9 did not achieve the 4-log decrease in the total number of viable cells after 48 hours of culture.

[0645] Example 10

[0646] In this example, both the negative pressure wound dressing of the application (wound contact layer comprising an antimicrobial agent comprising 1.20 wt.% silver ions) (Example 9) and the comparative example (experimental control without silver ions) were inoculated with Aspergillus brasiliensis NCPF® 2275.

[0647] As shown in Table 1, Example 10 resulted in a sharp decrease in the total viable cell count of Aspergillus brasiliensis NCPF® 2275 within 24 hours, with a further decrease in the total viable cell count observed at each measurement time point. After 168 hours of incubation, the total viable cell count of Aspergillus brasiliensis NCPF® 2275 reached a 4-log reduction. Figure 13 In contrast, Comparative Example 10 (experimental control without silver ions) allowed the total viable cell count of Aspergillus brasiliensis NCPF® 2275 to increase by 1 -log within 48 hours of incubation, and this was maintained until the end of the 7-day (168-hour) test. Comparative Example 10 did not achieve a 4-log reduction in the total viable cell count after 48 hours of incubation.

[0648] Example 11

[0649] In this example, both the negative pressure wound dressing of the application (wound contact layer comprising an antimicrobial agent comprising 1.20 wt.% silver ions) (Example 9) and the comparative example (experimental control without silver ions) were inoculated with Candida krusei NCPF® 3876.

[0650] As shown in Table 1, Example 11 resulted in a sharp decrease in the total viable cell count of Candida krusei NCPF® 3876 within 24 hours. From 24 hours after incubation to the completion of the 7-day (168-hour) test, the total viable cell count of Candida krusei NCPF® 3876 remained reduced by 4 logs.

[0651] Figure 14 In contrast, Comparative Example 11 (experimental control without silver ions) allowed the total viable cell count of Candida krusei NCPF® 3876 to increase within 24 hours, reaching a 2-log increase within 72 hours of incubation, and this was largely / essentially maintained until the completion of the 7-day (168-hour) test. Comparative Example 11 did not achieve a 4-log reduction in the total viable cell count after 48 hours of incubation.

[0652] Furthermore, the log reduction values of the antimicrobial activity of the negative pressure wound dressing of the application against the challenging organisms during the 168-hour test are shown in Table 1.

[0653]

[0654] ​​

[0655] Note that in Figures 7 to 14 In each of the figures of

[0656] Conclusion

[0657] Examples 4 to 9 and 11 demonstrate that the antimicrobial activity of the negative pressure wound dressings of the present application reduced the microbial population (total viable cell count) of Vancomycin resistant E. faecalis NCTC 12201, MRSA ATCC® BAA-1556ᵀᴹ, S. pyogenes NCTC 10872, A. baumannii NCTC 13421, ESBL producing K. pneumoniae NCTC 13465, antibiotic resistant P. aeruginosa NCTC 8506 and C. krusei NCPF® 3876 by more than 4 log orders (compared to the initial challenge organism count) within 48 hours and then maintained a reduction of more than 4 log orders for the remainder of the test period.

[0658] Example 10 demonstrates that the antimicrobial activity of the negative pressure wound dressings of the present application reduced the total viable cell count of A. brasiliensis NCPF 2275 by more than 4 log orders (compared to the initial challenge organism count).

[0659] The log reduction values for all of the challenge organisms at each time point during the test period are shown in Table 1 which also demonstrates that all of the bacterial cell counts achieved a 4 log reduction within 48 hours and the yeast and mould cell counts achieved a 4 log reduction within 168 hours.

[0660] The following assessments were carried out to demonstrate the anti-biofilm efficacy of the negative pressure wound dressings according to the present application against different microorganisms.

[0661] Assessment 3 - Anti-biofilm efficacy

[0662] An in vitro assessment was used to evaluate the anti-biofilm efficacy of the negative pressure wound dressings according to the present application against single species biofilms of three clinically relevant microorganisms. More specifically, using the CDC Biofilm model, using polycarbonate disc coupons, the ability of the dressings to reduce biofilm was evaluated.

[0663] SUMMARY

[0664] In vitro assessment tests the negative pressure wound dressings according to the present application against biofilm grown on polycarbonate coupons within the CDC Biofilm Reactor®. The CDC Biofilm Reactor® utilises continuous agitation to promote growth and microbial cell attachment to the polycarbonate coupons. The polycarbonate coupons are rinsed in saline to remove planktonic cells and are sandwiched between sections of the hydrated wound dressing according to the present application. After the required dressing exposure time, the coupons are removed and transferred to neutralising liquid media for sonication and vortexing and standard plate counts are performed to recover any residual organisms attached to the coupons. In addition, total viable counts are performed on the dressings. The test is performed for 7 days (168 hours).

[0665] Method

[0666] Microorganism

[0667] Separate tests (n=3) are performed using different microorganisms: Staphylococcus aureus NCIMB 9518, Pseudomonas aeruginosa NCIMB 8626 or Candida krusei NCPF® 3876.

[0668] Sample preparation

[0669] The bioreactors are inoculated using 1 millilitre of an overnight culture of Pseudomonas aeruginosa NCIMB 8626 and Staphyloc...

Claims

1. A negative pressure wound dressing comprising a backing layer, an adhesive skin contact layer, and an absorbent structure, wherein the adhesive skin contact layer is configured to releasably adhere the dressing to a skin surface, wherein the backing layer comprises an aperture for connection to a source of negative pressure, wherein the absorbent structure comprises a wound contact layer arranged to contact a wound when the adhesive skin contact layer is adhered to skin in the vicinity of the wound, and further wherein the wound contact layer comprises an antimicrobial agent comprising silver ions.

2. The negative pressure wound dressing of claim 1, wherein, the wound contact layer is formed of fibers of carboxyalkyl cellulose or a salt thereof having a degree of substitution of from about 0.05 carboxyalkyl groups per anhydroglucose unit to about 0.50 carboxyalkyl groups per anhydroglucose unit.

3. The negative pressure wound dressing of claim 2, wherein, the degree of substitution is about 0.30 carboxyalkyl groups per anhydroglucose unit.

4. The negative pressure wound dressing of claim 2 or 3, wherein, the antimicrobial agent is dispersed on the fibers of carboxyalkyl cellulose or a salt thereof.

5. The negative pressure wound dressing of any one of claims 2 to 4, wherein, the fibers of carboxyalkyl cellulose or a salt thereof are sodium carboxymethyl cellulose fibers.

6. The negative pressure wound dressing of any of the preceding claims, wherein, The basis weight of the wound contact layer is in the range of 160 g / m 2 to 480 g / m 2 .

7. The negative pressure wound dressing of claim 6, wherein, The basis weight of the wound contact layer is in the range of 160 g / m 2 to 240 g / m 2 .

8. The negative pressure wound dressing of claim 6 or 7, wherein, The wound contact layer has a basis weight of 200 g / m 2 .

9. The negative pressure wound dressing of any of the preceding claims, wherein, the wound contact layer comprises a plurality of layers, each layer being formed of fibers of carboxyalkyl cellulose or a salt thereof.

10. The negative pressure wound dressing of claim 9, wherein, The basis weight of each layer is in the range of 40 g / m 2 to 240 g / m 2 .

11. The negative pressure wound dressing of claim 10, wherein, The basis weight of each layer is in the range of 80 g / m 2 to 160 g / m 2 .

12. The negative pressure wound dressing of any one of claims 9-11, wherein, The combined basis weight of the plurality of layers is in the range of 160 g / m 2 to 480 g / m 2 .

13. The negative pressure wound dressing of claim 12, wherein, The combined basis weight of the plurality of layers is in the range of 160 g / m 2 to 240 g / m 2 .

14. The negative pressure wound dressing of claim 12 or 13, wherein, The combined basis weight of the plurality of layers is 200 g / m 2 .

15. The negative pressure wound dressing of any one of claims 9 to 14, wherein, the wound contact layer comprises only two layers.

16. The negative pressure wound dressing of claim 15, wherein, The basis weight of each layer was 100 g / m 2 .

17. The negative pressure wound dressing of any one of claims 9 to 16, wherein, the at least two layers are joined by stitching or lamination.

18. The negative pressure wound dressing of any of the preceding claims, wherein, the silver ions are present in the antimicrobial agent at a concentration of 0.10 wt.% to 10.0 wt.%.

19. The negative pressure wound dressing of claim 18, wherein, the silver ions are present in the antimicrobial agent at a concentration of 0.50 wt.% to 1.80 wt.%.

20. The negative pressure wound dressing of claim 18 or 19, wherein, the silver ions are present in the antimicrobial agent at a concentration of 1.20 wt.%.

21. The negative pressure wound dressing of any of the preceding claims, wherein, the absorbent structure comprises a superabsorbent layer and a transmission layer.

22. The negative pressure wound dressing of claim 21, wherein, the transmission layer is arranged between the wound contact layer and the superabsorbent layer.

23. The negative pressure wound dressing of Claim 22, wherein, the transmission layer is laminated or stitched to the wound contact layer on a first surface and to the superabsorbent layer on a second surface.

24. The negative pressure wound dressing of any of the preceding claims, wherein, the wound contact layer further comprises an anti-biofilm agent.

25. The negative pressure wound dressing of claim 24, wherein, the anti-biofilm agent comprises a chelating agent.

26. The negative pressure wound dressing of claim 25, wherein, the chelating agent is ethylenediaminetetraacetic acid (EDTA) or a salt thereof (e.g., disodium salt or calcium disodium salt).

27. The negative pressure wound dressing of claim 25 or 26, wherein, the chelating agent is present in an amount of 0.5 wt.% to 10 wt.%, preferably 1 wt.% to 3 wt.%.

28. The negative pressure wound dressing of any of claims 25-27, wherein, the anti-biofilm agent comprises a quaternary cationic surfactant.

29. The negative pressure wound dressing of claim 28, wherein, the quaternary cationic surfactant is a quaternary ammonium salt.

30. The negative pressure wound dressing of Claim 29, wherein, the quaternary ammonium salt has the following structural formula: wherein R 1 at least one of R 4 is an alkyl group having the structural formula C n H 2n+1 n is 8, 10, 12, 14, 16, or 18, and R 1 one of R 4 is an aryl group.

31. The negative pressure wound dressing of Claim 30, wherein, the quaternary cationic surfactant is benzyltrimethylammonium chloride.

32. The negative pressure wound dressing of any of claims 28-31, wherein, the quaternary cationic surfactant is present in an amount of at least 0.025 wt.%.

33. The negative pressure wound dressing of Claim 32, wherein, the quaternary cationic surfactant is present in an amount of 0.05 wt.% to 4.0 wt.%.

34. The negative pressure wound dressing of any of the preceding claims, wherein, the antimicrobial agent further comprises a buffering agent.

35. The negative pressure wound dressing of Claim 34, wherein, the buffering agent is selected from citric acid, disodium hydrogen phosphate, sodium citrate, acetic acid, sodium acetate, or a combination thereof.

36. The negative pressure wound dressing of any of the preceding claims, wherein, the wound contact layer is reinforced or stitched with cellulose yarn, preferably lyocell yarn.

37. The negative pressure wound dressing of any one of the preceding claims, wherein, the wound contact layer comprises less than 95 wt.% of a polysiloxane.

38. The negative pressure wound dressing of Claim 37, wherein, the wound contact layer comprises no more than 1 wt.% of a polysiloxane, preferably 0 wt.% of a polysiloxane.

39. A method of manufacturing a negative pressure wound dressing, the method comprising the steps of: a. providing an adhesive skin contact layer and a backing layer; b. providing a wound contact layer and an absorbent structure comprising a transmission layer and a superabsorbent layer, wherein the wound contact layer comprises an antimicrobial agent comprising silver ions; and c. arranging the absorbent structure between the wound contact layer and the backing layer.

40. The method of manufacturing a negative pressure wound dressing of claim 39, wherein, The negative pressure wound dressing is the wound dressing according to any of claims 1 to 38.

41. A negative pressure wound exudate management system comprising the negative pressure wound dressing according to any of claims 1 to 38, and further comprising: a. a negative pressure source; and b. a conduit or tubing for providing negative pressure to the wound dressing through an internal lumen of the conduit or tubing and an opening in the wound dressing.

42. The negative pressure wound exudate management system of Claim 41, wherein, The negative pressure source comprises a pump for generating negative pressure, and the tubing connects the pump and the wound dressing.

43. The negative pressure wound exudate management system of Claim 42, wherein, The negative pressure source further comprises a one-way valve in series between the pump and the wound dressing to maintain negative pressure within the wound dressing when the pump is disconnected from the tubing.

44. The negative pressure wound exudate management system of Claim 43, wherein, The one-way valve is connected to one of the pump and the tubing.

45. The negative pressure wound exudate management system of any of Claims 41-44, wherein, The opening in the wound dressing is in a backing layer of the wound dressing.

Citation Information

Patent Citations

  • Wound dressings and materials suitable for use therein

    WO2000001425A1

  • Gardnerella vaginalis assay

    WO2012061225A2